A comprehensive overview of evolutionary relationships and geographic distributions of cownose rays: more valid taxa needing protective measures - Yasmim Trindade C. Cunha; Renata Daldin Leite; Lucas Gabriel Pereira da Silva; Vanessa Paes Cruz; Jorge Luiz S. Nunes; Matheus Marcos Rotundo; Paola Palacios-Barreto; Píndaro Diaz-Jaimes; Ana P. Barbosa Martins; M. Aaron Macneil; Chris G. Mull; José Augusto Pires Bitencourt; et al. (Reviews in Fish Biology and Fisheries, 2026)
Rays of the family Rhinopteridae Jordan & Evermann, 1896 are highly migratory and widely distributed in warm tropical and temperate waters. Along the Brazilian coast, the presence of two species has been recorded: Rhinoptera bonasus Mitchill, 1815 and Rhinoptera brasiliensis Müller, 1836. These stingrays are commonly caught as bycatch in trawl fisheries, however, the two species lack distinctive external morphological features that allow for reliable differentiation—species identification is primarily based on the shape and arrangement of teeth in the buccal plates. This study aimed to investigate the evolutionary history of the genus Rhinoptera and to explore which evolutionary drivers, such as biogeographic events or behavioral traits, have influenced its diversification. To achieve this, we analyzed both mitochondrial and nuclear genetic markers, focusing on the species occurring along the Brazilian coast. Specimens of both species were collected across various locations in Brazil, and additional sequences from other Rhinoptera species were obtained from GenBank. Our results reveal the presence of multiple cryptic species within Rhinoptera , particularly within R. bonasus , and likely in Rhinoptera steindachneri Evermann & Jenkins, 1891 and Rhinoptera javanica Müller & Henle, 1841. Notably, R. bonasus does not occur in Brazilian waters nor in parts of the Caribbean where a distinct cryptic sister lineage was identified. Based on our findings, we propose the resurrection of Rhinoptera lalandii Müller & Henle, 1841 as the species representing the lineage found along the Brazilian coast and the Eastern Atlantic Ocean. We suggest that philopatric behavior may represent one of several factors potentially influencing diversification within Rhinopteridae, although this hypothesis requires direct behavioral and population level validation. These findings highlight the urgent need for a comprehensive taxonomic revision of the family, as well as a reassessment of current conservation strategies to better reflect the hidden diversity within this group of species. Graphical abstract

The COVID-19 pandemic influenced the temporal dynamics of antimicrobial resistance markers and bacterial community across urban wastewater treatment plants - Celso G. B. Filho; Francisca A. S. Oliveira; Victor L. M. Rodrigues; Denise C. Hissa; Maisa V. H. Barros; Allysson A. de Farias; Gabriel T. Dantas; André B. dos Santos; Julio C. M. Ximenes; Vânia M. M. Melo (Brazilian Journal of Microbiology, 2026)
Urban wastewater systems represent important interfaces between human activity and the environmental occurrence of antimicrobial resistance (AMR) markers. We assessed the temporal dynamics of intI1 , ermB , and the 16 S rRNA gene by quantitative PCR across three wastewater systems (EPC, CJC, and JW) in Fortaleza, Brazil, from November 2021 to November 2023. Bacterial communities were additionally characterized by 16 S rRNA gene metabarcoding in 18 samples collected in December 2021 and January 2022. A synchronized decline in 16 S rRNA gene and intI1 concentrations beginning in late 2022 was observed across all three wastewater systems, suggesting a shift toward lower microbial abundance. The ermB gene showed higher and more variable concentrations during part of the pandemic period, followed by convergence toward lower levels; however, the absence of antimicrobial-consumption data precluded attribution of this pattern to changes in macrolide selective pressure. Normalized antimicrobial resistance marker abundances were comparatively stable at EPC and JW but more variable at CJC. EPC exhibited the highest ASV richness, whereas CJC and JW showed greater diversity according to Shannon and inverse Simpson indices. Beta-diversity analyses identified wastewater system as the principal factor associated with bacterial community structure, while the effect of sampling period was smaller and metric-dependent. Neither ermB nor intI1 was individually associated with community composition, although intI1 showed a limited effect after adjustment for wastewater system in one model. Physicochemical parameters were not significantly associated with normalized marker abundances in the exploratory paired analysis. Arcobacter , Acinetobacter , and other potentially relevant genera were detected, but no direct associations between these taxa and the monitored AMR markers could be established. These findings highlight the value of integrating longitudinal qPCR, microbiome profiling, and environmental characterization to improve the interpretation of targeted AMR markers in One Health wastewater surveillance.

Molecular surveillance of Bordetella pertussis during the 2024 outbreak in Southeast Brazil: allelic profiles and comparison to vaccine strain - Thiago J. Sousa; Felipe D. Gatti; Joana Z. Nodari; Gabriela C. de Mendonça; Anna Clara G. Có; Thabata C. D. Damasceno; Nayara C. Silva; Lílian S. Lavagnoli; Danielle G. P. Lyra; Jaqueline P. Goulart; Rodrigo Ribeiro-Rodrigues (Brazilian Journal of Microbiology, 2026)

Cardiovascular outcomes following intrauterine and lactational exposure to cyantraniliprole in male Wistar rats - Kaio Y. Morimoto; Ana C.F. de Menezes; Kawane F. Moura; Carolina O. Gonçalves; Thais Z. Verlingue; Karen G. Luiz; Mayra Dias Rodrigues; Karine F.S. Rodrigues; Pedro H. Nascimento; Glaura S.A. Fernandes; Graziela S. Ceravolo (Regulatory Toxicology and Pharmacology, 2026)

Listeria monocytogenes dry surface biofilms: a comparative study of mono- and coculture with Enterococcus faecium - Raul Fernando Pereira; Joana Rodrigues Cerqueira Zioli Fernandes; Thais Helena de Camargo; Jéssica Aragão F.F. Finger; Maristela S. Nascimento (Food Research International, 2026)

Comprehensive characterization of walnut oil processing by-products: biochemical composition, bioactive properties, and polyphenol in vitro bioaccessibility and bioavailability - Rafael Mascoloti Spréa; Daniele Bobrowski Rodrigues; Tânia C.S. Pires; Ricardo C. Calhelha; María E. Brassesco; Manuela Pintado; Susana Santoyo; Elena Arranz; Miguel A. Prieto; Lillian Barros; Joana S. Amaral (Food Chemistry, 2026)

Optimizing soybean–maize intercropping through arbuscular mycorrhiza–rhizobia inoculation and fertilizer microdosing in Benin - Brice G. Sinhouenon; Pierre G. Tovihoudji; Rodrigue V.C. Diogo; Nourou S. Yorou; Pierre Bertin (Field Crops Research, 2026)

Assessing traffic-derived soil contamination: Insights from earthworm bioaccumulation and histomorphological responses - Nádia M.P. Coelho; Ricardo Camarinho; Patrícia Garcia; Armindo S. Rodrigues (Environmental Research, 2026)

Bioinspired pullulan-based adhesive coacervate films for targeted buccal delivery of peptides - Margarida M.A. Sacramento; Nazanin Z. Ezazi; Eleftheria Pantazoglou; Philip Mark Lund; Marco van de Weert; Zhongyang Zhang; Rui Vitorino; Floriane Bahuon; Ragna Berthelsen; Stephen T. Buckley; Gavrielle R. Untracht; Peter Eskil Andersen; et al. (Carbohydrate Polymers, 2026)

Dietary supplementation with algae-based ingredients modulates antioxidant defenses and immune response in sea urchin Paracentrotus lividus following a Vibrio parahaemolyticus challenge - Ana Filipa Rodrigues; S. Lourenço; A.S. Gomes; M. Vaz; H. Cardoso; A.P. Violante; T. Baptista (Animal Feed Science and Technology, 2026)

Micro-FTIR identifies osteodifferentiation markers in heterogeneous mesenchymal stem cell populations - João T.S. Martins; Clara Martins; João A. Rodrigues; Inês C.R. Graça; Daniela S. Bispo; Ana L.M. Batista de Carvalho; Brian J. Goodfellow; João F. Mano; Mariana B. Oliveira; Mariela M. Nolasco; Maria P.M. Marques; Paulo J.A. Ribeiro-Claro; et al. (Analytica Chimica Acta, 2026)

Kogia Records in Brazilian Equatorial and Southwestern Atlantic Oceans - Joao Pedro M. Mura; Raphael B. Machado; Yasmin P. Viana; Natalia Rodrigues‐Soares; Giovanne A. Ferreira; Larissa Kelmer L. Kascher; Barbara S. Silva; Lucia O. Alencar; Gabrieli M. Rodrigues; Franciele R. de Castro; Daniela F. Godoy; Jose L. Pizzorno; et al. (Marine Mammal Science, 2026)
The pygmy ( Kogia breviceps ) and dwarf ( Kogia sima ) sperm whales are cryptic cetaceans characterized by inconspicuous surfacing behavior, small group sizes, and deep‐diving habits, making visual detection particularly challenging. Here, we present the first broad‐scale passive acoustic monitoring (PAM) assessment of Kogia spp. occurrence along the Brazilian coast, spanning both the Equatorial Atlantic Ocean (EAO) and Southwestern Atlantic Ocean (SWAO). Across 25 survey campaigns, 504 survey days, and more than 6441 h of acoustic recordings, 94 acoustic detections were identified, predominantly within the Brazilian Equatorial Margin (BEM), resulting in substantially higher detection‐per‐unit‐effort values in the EAO than in the SWAO. Two rare visual‐acoustic encounters of Kogia sima were also documented, including one detection incorporated into the dataset. A total of 2796 echolocation clicks were analyzed, exhibiting the characteristic narrow‐band high‐frequency acoustic profile of Kogia spp. (mean peak frequency = 126.2 ± 3.8 kHz; mean −3 dB bandwidth = 4.7 ± 2.56 kHz; mean inter‐click interval = 141 ± 97 ms). Detections occurred across a broad bathymetric range (9–4411 m), and kernel density analyses revealed spatial heterogeneity in occurrence patterns, with recurrent detection areas concentrated within the BEM. Collectively, these findings demonstrate the effectiveness of PAM for studying elusive deep‐diving cetaceans and provide an important baseline for future ecological monitoring, impact assessment, and conservation efforts targeting Kogia spp. in the western Atlantic.

Intestinal Histomorphometric Alterations During Experimental Strongyloidiasis in Mice Treated with Rosmarinus officinalis Essential Oil - Lorena Q. A. Tanaka; Kamilla A. M. Dutra; Nicolas M. H. da Silva; Izadora M. Assis; Gabriela A. C. Duarte; João B. A. Souza; Eleuza R. Machado; Ana Paula S. Perez; Rosângela M. Rodrigues (Acta Parasitologica, 2026)
Purpose Strongyloidiasis is an intestinal helminthiasis that can induce structural alterations in the intestinal mucosa during infection. The present study evaluated histomorphometric alterations of the small intestine in mice experimentally infected with Strongyloides venezuelensis and treated with Rosmarinus officinalis essential oil. Methods Infected animals were treated orally with R. officinalis essential oil (200 or 400 mg/kg), ivermectin or control treatments. Histomorphometric parameters of the small intestine were evaluated, including villus height, epithelial height, crypt depth, muscular layer thickness, brush border height and goblet cell counts. Parasitological parameters were also assessed to characterize the infection model. Results Histomorphometric analysis demonstrated that treatment with essential oil at 200 mg/kg was associated with recovery of villus and epithelial height, increased brush border and goblet cell numbers, as well as attenuation of muscular layer hypertrophy, suggesting preservation of mucosal structure during infection. The 400 mg/kg dose, although associated with greater reduction in parasite burden, was accompanied by increased crypt depth, indicating more intense proliferative remodeling of the intestinal mucosa. Ivermectin promoted the greatest reduction in parasite burden with marked elimination of eggs and females. Conclusion These findings indicate that R. officinalis essential oil modulates intestinal mucosal architecture during experimental strongyloidiasis and highlight its potential influence on host intestinal responses during infection.

Influence of chemotype on the chemical composition, antioxidant activity and in vitro cytotoxicity of Ageratum conyzoides essential oil - Carla Janaina R.M. do Rosário; Amanda M. Teles; Klinger Antonio da F. Rodrigues; Pablo Luis B. Figueiredo; Viviane Correa S. Coimbra; Cláudia Q. da Rocha (South African Journal of Botany, 2026)

Mycobiome matters? Rethinking the role of fungi in depression and anxiety: a hypothesis-driven perspective - Dionisio Pedro Amorim-Neto; Paulla Vieira Rodrigues; Cesar Renato Sartori; Anderson S. Sant'Ana (Fungal Biology Reviews, 2026)

Fortifying Depurated Clams: Evaluation of the Antioxidant and Nutritional Impact of Microencapsulated Diets Containing Nannochloropsis sp. and Vitamin Supplementation - Vitória Pereira; Sílvia F. S. Pires; Pedro Bem-Haja; Andreia C. M. Rodrigues; Amadeu M. V. M. Soares; Luís E. C. Conceição; Mário Pacheco; Rui J. M. Rocha (Fishes, 2026)
Conventional bivalve depuration protocols may compromise organoleptic and nutritional quality, largely as a consequence of fasting. This study investigates an innovative post-depuration feeding strategy in the clam Ruditapes decussatus using microencapsulated diets containing Nannochloropsis sp. supplemented with either a standard dose of vitamins C and E (MV) or a high dose—4× the standard level—of these vitamins (MV+). A three-phase experiment was conducted comprising 24 h of depuration, 2 h of post-depuration feeding, and 6 days of refrigerated storage at 5 ± 1 °C. Clams were sampled after feeding (PF) and after refrigerated storage (PS) and assessed for condition index (CI), vitamin C and E contents, antioxidant defense markers, including catalase activity (CAT) and total glutathione (tGSH), and oxidative damage, assessed through lipid peroxidation (LPO). CI did not differ significantly among dietary treatments. At PF, dietary treatment modulated antioxidant-related responses, particularly in the MV+ group. In the digestive gland, MV+ showed significantly lower LPO than the Control at PF, whereas after refrigerated storage this response was reversed. These findings indicate that the potential benefits associated with vitamin-enriched post-depuration feeding were not fully retained, with increased LPO at PS indicating greater oxidative damage. Further research is required to optimize this feeding strategy and evaluate its feasibility at commercial scale.

eDNA-based assessment of microbial dynamics in response to persistent contaminants and degraded water quality in a hypereutrophic urban reservoir - Juliana S. M. Pimentel; Maria Clara V. M. Starling; Camila C. Amorim; Valquíria F. L. Viana; Alessandra S. Martins; Daniel A. S. Rodrigues; Luciana P. M. Brandão; Nadieh de Jonge; Niels O. G. Jørgensen; Louise Schlüter; Matt Simcik; Jeppe Lund Nielsen (Environmental Monitoring and Assessment, 2026)
Urban freshwater ecosystems are increasingly exposed to mixtures of pollutants, including per- and polyfluoroalkyl substances (PFAS). However, their ecological effects remain poorly understood, especially in tropical regions with limited sanitation infrastructure. This study investigated PFAS contamination, water quality, and microbial community structure in Pampulha Lake, a tropical urban reservoir in southeastern Brazil. Spatiotemporal patterns in prokaryotic and eukaryotic diversity were assessed over a year (2022–2023) using environmental DNA metabarcoding of 16S and 18S rRNA genes by integrating taxonomic data with PFAS concentrations and water quality. Physicochemical and multivariate analyses revealed strong seasonal and spatial heterogeneity, influenced by eutrophication, hydrological variability, and pollution gradients. Among the seven PFAS detected above quantification limits, PFBS and PFOA were the most common. Prokaryotic communities showed significant correlations with PFAS, especially with sulfonated forms, while eukaryotic communities were more stable. Diversity patterns highlighted microbial community sensitivity to environmental stress. Overall, results indicate that PFAS influenced microbial assemblages, supporting their inclusion in monitoring frameworks, and eDNA was proved effective for assessing ecological risks in tropical urban reservoirs.

Assessment of Exposure to Essential and Non-Essential Elements through Concentrations in Tissues of Chelonia mydas (Green turtles) from the South Atlantic, Northeast Brazil - Midiã S. Rodrigues; Iago J. S. da Silva; Cristina F. da Fonseca; Pierre C. Soares; Múcio L. B. Fernandes; Geraldo J. B. de Moura (Biological Trace Element Research, 2026)
This study aimed to evaluate the exposure of Chelonia mydas (green turtles) inhabiting the south coast of Pernambuco, Northeast Brazil, to essential and toxic elements. Concentrations of Al, Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, and Zn were determined in shell, muscle, liver, and kidney samples from 43 individuals using ICP-OES. Element concentrations varied according to tissue type. Specifically, the average concentrations of Al in shell (1064 mg kg −1 d.w.) and Fe in liver (2069 mg kg −1 d.w.) were the highest, whereas Al, Co, Cr, and Mo in muscle were the lowest and fell below the method's limit of quantification (LOQ). Meanwhile, Pb was above the LOQ only in muscle (average of 4.1 mg kg −1 d.w.). Cadmium levels were markedly elevated, with average concentrations of 0.15, 0.29, 12, and 49 mg kg −1 d.w. in shell, muscle, liver, and kidney, respectively; furthermore, concentrations in muscle, liver, and kidney were well above the limits established by Brazilian legislation (0.05, 0.5, and 1.0 mg kg −1 , respectively). High levels of Cd may be linked to the presence of fertilizers in coastal areas, the ingestion of contaminated food, and chronic exposure. Notably, fibropapillomatosis (FP) showed a significant relationship with shell Cu content, demonstrating that this metal is linked to the etiology and development of FP. Overall, multi-elemental profiling of sea turtle tissues can serve as a cost-effective surveillance tool for marine ecosystem monitoring and for detecting anthropogenic impacts on sea turtle health.

Beyond Tubipora musica: Phylogenomics unveils the overlooked diversity and endemism of the hermatypic octocoral genus Tubipora - Laura Macrina; Tullia I. Terraneo; Catherine S. McFadden; Andrea Sabino; Nicolas Oury; Federica Barreca; Silvia Vicario; Kaveh Samimi-Namin; Daniel Knop; Mattie Rodrigue; Vincent Pieribone; Andrew H. Baird; et al. (Molecular Phylogenetics and Evolution, 2026)

Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

Environmental assessment of antibiotic toxicity under climate change–related temperature and pH scenarios using Danio rerio - Bárbara S. Diogo; Sara Rodrigues; Oksana Golovko; Sara C. Antunes (Fish Physiology and Biochemistry, 2026)
Climate change induced temperature and pH shifts can alter aquatic environments, potentially intensifying antibiotic toxicity, disrupting the physiological balance of aquatic organisms. Few studies have examined combined effects of these abiotic environmental stressors and antibiotics on aquatic ecosystems in a potential climate change scenario. This study evaluated the toxicity of environmentally relevant concentrations of sulfamethoxazole (150 µg SMX/L), trimethoprim (30 µg TRIM/L), and their mixture (MIX: 150 µg SMX/L + 30 μg TRIM/L) in Danio rerio under two scenarios: standard (26 °C, pH 7.5) and climate changed (28 °C, pH 9.0). A multi-biomarker approach was performed to evaluate oxidative stress, lipid peroxidation, neurotransmission, energy metabolism, and DNA damage. Integrative assessment of an organism’s health showed that increasing pH and temperature intensified SMX and TRIM toxicity, shifting from marginally to highly toxic. Meanwhile, MIX toxicity increased from marginally to moderately toxic. Under standard conditions, SMX and TRIM caused major alterations (affecting antioxidant/detoxification mechanisms), while MIX induced severe alterations in D. rerio 's health status. Under a climate-changed scenario, all antibiotics led to severe alterations (lipid peroxidation, DNA damage, and energy metabolism disruption). These findings suggest that under a climate-changed scenario (higher temperature and pH increase), both individually and in mixtures, antibiotic toxicity leads to more severe effects on D. rerio . Given this, it is crucial to consider environmental factors when assessing antibiotic toxicity, as shifts in temperature and pH can significantly amplify their harmful effects. Understanding these interactions is essential for developing effective regulatory and conservation strategies to safeguard aquatic ecosystems from long-term ecological imbalances.

Testicular cryopreservation of prepubertal and adult Morada Nova rams: Slow freezing versus vitrification - R.H. Celiz; D.D. Guerreiro; D.C.C. Brito; M.A.S. Novaes; L.V.S. Ñaupas; N.A.R. Sá; G.J.Q. Palomino; F.D.R. Gomes; A.C.A. Ferreira; T.G. Mbemya; C.C.L. Fernandes; L.A.L. Rufino; et al. (Animal Reproduction Science, 2026)

Early-pregnancy exposure to air pollution and stillbirth in São Paulo, Brazil – results from the FetRisks case-control study - Rafael Buralli; Dario Ezequiel Elias; Cláudio Makoto Kanai; Lays Janaina Prazeres Marques; Osmara Alves dos Santos; Gizelton Pereira Alencar; Zilda Pereira da Silva; Gerusa Maria Figueiredo; Mara S. Hoshida; Laura Rodrigues; Rossana Pulcineli Vieira Francisco; Hillegonda Maria Dutilh Novaes; et al. (Air Quality, Atmosphere & Health, 2026)
Stillbirth remains a major public health concern, particularly in urban settings with persistent air pollution, while evidence remains limited in middle-income countries. This study aims to examine the association between prenatal exposure to fine particulate matter (PM2.5) PM2.5 and stillbirth in São Paulo, Brazil. Case-control study including 348 antepartum stillbirths and 419 live births recruited from 14 public hospitals. PM2.5 exposure was estimated using residential addresses linked to the nearest air quality monitoring station. We evaluated median PM2.5 levels during the first trimester of pregnancy and sustained higher PM2.5 exposure episodes (> 12.7 µg/m³ for ≥ 3 weeks). We explored the interaction between air pollution and maternal factors. Multiple logistic regression models were adjusted for maternal sociodemographics. All participants were exposed to PM2.5 concentrations substantially above the WHO Air Quality Guidelines. Sustained higher PM2.5 exposure was associated with higher odds of stillbirth (ORadj 1.51; 95% CI: 1.03–2.25) and showed a significant interaction with maternal age ≥ 35 years, increasing the odds of having a stillbirth (ratio of ORadj 2.55 [95% CI: 1.08–6.23]). Stillbirth was associated with episodes of sustained higher PM2.5 exposure in early pregnancy, in a context where all women experienced high pollutant levels. The coexistence of high baseline PM2.5 exposure and multiple maternal vulnerabilities underscore the need for integrated strategies addressing air quality, health equity, and perinatal care to reduce preventable stillbirths in highly polluted urban environments.

Spatial Scale Modulates the Effect of Habitat Amount on Diversity Patterns of Arachnid Assemblages Across Different Brazilian Ecosystems - André F. A. Lira; Adriano M. DeSouza; Thayna R. Brito‐Almeida; Hugo L. L. Neves; Gilberto G. Rodrigues; Carlos Henrique De‐Oliveira‐Nogueira; Ubiratã F. Souza; Alessandra R. S. Andrade; Rafael G. Jansen; Ana Lúcia Tourinho; Leonardo S. Carvalho; Laís M. Pordeus; et al. (Journal of Biogeography, 2026)
Aim We evaluated how native vegetation cover influences the diversity of arachnid assemblages across multiple spatial scales in major Brazilian ecosystems. Location Brazil (Amazon and Atlantic rainforests, Cerrado savanna and Caatinga dry forest). Taxon Arachnida (Opiliones, Pseudoscorpiones and Scorpiones). Methods We sampled arachnids at 120 sites using active search and litter sifting. Native vegetation cover was quantified at three spatial scales (100, 200 and 300 m buffers) using GIS data. Assemblage structure was assessed using abundance, species richness, and Hill numbers ( q = 0, 1 and 2). Generalized linear mixed models were used to evaluate responses across taxonomic groups and ecosystems. Results We recorded 3986 individuals from 179 species. Diversity responses to native vegetation cover were taxon‐, ecosystem‐ and scale‐dependent. Positive effects of vegetation cover were stronger and more consistent in rainforest than in savanna and dry forest ecosystems. In rainforests, most responses occurred at smaller spatial scales (100–200 m), whereas no significant effects were detected in the savanna. Opiliones richness showed limited variation with vegetation cover but differed in dominance structure among ecosystems. Scorpion assemblages were characterized by low richness and high dominance, while pseudoscorpions exhibited low evenness in more species‐rich sites, particularly in the Amazon. Main Conclusions Native vegetation cover plays an important role in structuring arachnid diversity in Brazil, but its effects vary across taxa, ecosystems and spatial scales. These findings highlight the need for taxon‐ and scale‐specific conservation strategies and reinforce the importance of multi‐scale approaches to biodiversity conservation in Neotropical landscapes under increasing anthropogenic pressure.

Inclusion of carotenoids and Eicosapentaenoic Acid (EPA) in sea urchin (Paracentrotus lividus) broodstock diets improves gonad development and oocyte quality - A. S. Gomes; A. F. Rodrigues; M. Neves; C. Roseiro; H. Cardoso; A. P. Violante; P. J. Gavaia; C. Suckling; S. Lourenço (Aquaculture International, 2026)

First drone‐based in situ observation of mating behaviour in the Groovebelly Stingray ( D. hypostigma ) in the Southwestern Atlantic - R. M. Ferreira; N. L. F. Araujo; L. N. dos Santos; A. F. S. Rodrigues (Journal of Fish Biology, 2026)
We report the first in situ observation of mating behaviour in the endangered Groovebelly Stingray ( Dasyatis hypostigma ), endemic to the Southwestern Atlantic. Recorded by drone in May 2025 off Ilhabela, Brazil, the event involved one female and four males, lasting ~3 min and comprising close following and pre‐copulatory biting, without agonistic interactions. The interaction comprised a partial behavioural sequence of close following and pre‐copulatory biting, without agonistic interactions between males. This record provides novel insights into the species' reproductive strategy and highlights the value of non‐invasive drone surveys for elasmobranch research.

Late Quaternary change in sources and burial of organic carbon off Northeastern Brazil - Alice Maria da S. Rodrigues; Rodrigo de L. Sobrinho; Patrícia Piacsek; Ioanna Bouloubassi; Arnaud Huguet; Ana Luiza S. Albuquerque; Igor M. Venancio; Thiago P. Santos; Joana F. Cruz; Marcelo C. Bernardes (Quaternary Science Reviews, 2026)

In vitro biological and functional properties of fermented roasted coffee extracts in the context of Parkinson's disease - Dionisio Pedro Amorim-Neto; Joao Victor Virgilio-da-Silva; Jaqueline Sousa Correia; Matheus Péricles Silva Láscaris; Jhonathan Vinícius Menezes Silva; Carla Alves Barbosa; Beatriz Dal Pian Machado; Mauricio Luis Sforça; Gustavo Henrique Rodrigues da Silva; Lilian Regina Barros Mariutti; Pedro Manoel Mendes Moraes-Vieira; Cesar Renato Sartori; et al. (Food Bioscience, 2026)

Quantifying variability and viability: A dual-modeling and cytometry approach to Salmonella survival in low-moisture conditions - Mayara M. Oliveira; Arthur Kael Rodrigues da Pia; Syllas B.S. Oliveira; Anderson S. Sant’Ana (Food Control, 2026)

Power dynamics in strategic environmental assessment: examining actors' relations in Portuguese urban planning processes - M. Pereira; M. Pereira; M.L. Fernandes; F. Teles; S. Moreno Pires; P. Silva; C. Rodrigues; C. Jalali; A. Polido (Environmental Impact Assessment Review, 2026)

Reproductive toxicity induced by a repeated 28-day oral exposure to a commercial mixture of the herbicides S-metolachlor and flumioxazin in male rats - Renata K. Carvalho; Diego S. Reis; Ana Luísa G. Santiago; Bruna M. Rodrigues; Jacqueline A. Leite; Walter D. Júnior; Virgínia Damin; Monica L. Andersen; Maingredy R. Souza; Paulo C. Ghedini; Hericles M. Campos; Daniela M. Silva; et al. (Chemico-Biological Interactions, 2026)

Effect of supplementation with different trace minerals sources and fibrolytic enzyme on the productive and reproductive performance of Nellore cows on pasture - Keuven S. Nascimento; Amanda C. M. Queiroz; Aline N. Rodrigues; Luiz F. Costa e Silva; Carlos R. Zilioti; James E. Pettigrew; Rodrigo S. Marques; Flávio D. Resende; Gustavo R. Siqueira (Tropical Animal Health and Production, 2026)

Assessment of Eucalyptus seedlings grown in biodegradable containers and their growth in clonal plantations - Vitor S. Brito; Emanuela F. Gama-Rodrigues; José L. M. Gonçalves; Alexandre V. Ferraz; José C. A. Júnior (New Forests, 2026)

Ecotoxicity assessment of dairy wastewater: environmental risks and regulatory needs - Magno Lange Albuquerque; Fernando Rodrigues-Silva; Alyson Rogério Ribeiro; Carollina M. Chávez; Gilcinéa de Cássia Santana; Alessandra da S. Martins; Camila C. Amorim; Maria Clara V. M. Starling (Ecotoxicology, 2026)

Brazil’s science–policy effort to monitor native vegetation restoration - André L. Giles; Marina G. Freitas; Ana L. V. Espada; Pedro Constantino; Bruno S. Francisco; Silvia B. Rodrigues; Alexandre B. Sampaio; Isis F. de Freitas; Gabriela C. S. Bueno; Raquel C. A. Lacerda; R. Edson; Kirsten Silvius; et al. (Ambio, 2026)
In its early years, the UN Decade on Ecosystem Restoration has mobilized unprecedented global commitments. Yet, measuring restoration success remains contested, particularly in megadiverse countries where the absence of standardized indicators and assessment protocols often leads to subjective decisions by environmental agencies. Here, we present a core set of leading indicators developed through a pioneering Brazil-led science–policy collaboration between environmental agencies and research institutions. The indicators capture early vegetation recovery within four years and whether restoration trajectories are sustained or at risk of reversal. The initiative also establishes a framework that bridges science and policy to deliver practical monitoring tools. It offers a model for other megadiverse countries with complex governance, showing how simple, standardized indicators can translate restoration pledges into measurable results for the UN Decade.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Expert consensus on passive heating interventions to promote skeletal muscle strength and mass: a delphi study - Elisa Lemos; Ian B. Stewart; Patrick Rodrigues; Shawnda A. Morrison; Lee Wharton; Christopher J. Tyler; Stephen S. Cheung; Sebastian Racinais; Ralph J. F. H. Gordon; Alex Lloyd; Julien D. Périard; Katsumasa Goto; et al. (European Journal of Applied Physiology, 2026)
Purpose Passive heating has emerged as a potential non‑exercise method to support muscle strength and mass, but its application is limited by inconsistent protocols and unclear dosage and safety guidelines. This study used a Delphi methodology to establish expert consensus on key parameters for passive heating interventions targeting neuromuscular and muscle morphology outcomes. Methods An international panel of academic experts (≥ 3 peer‑reviewed publications in passive heating and neuromuscular function) completed a two‑round Delphi process. Round 1 gathered open‑ended responses on passive heating strategies, intervention targets, and safety. In Round 2, experts ranked the importance of generated statements. Consensus was defined as ≥ 70% ranking a statement as either first or second in importance. Results Eleven experts completed Round 1 and ten in Round 2. From 177 qualitative responses, 130 statements were evaluated, with 11 reaching consensus (80–100% agreement; interquartile range = 0–1). Hot‑water immersion was prioritised as the most optimal passive heating modality. Experts agreed on targeting muscle temperatures of 39–40 °C, ~ 60-minute session durations, and once‑daily exposure as key intervention parameters. Strong consensus was also reached for monitoring core temperature and cardiovascular strain (e.g., heart rate, blood pressure) to ensure participant safety. No consensus was reached on a single target population or the total intervention duration. Conclusion This Delphi study provides a consensus‑based framework outlining key parameters and safety considerations for passive heating interventions. These findings do not establish efficacy but identify priority variables to inform future experimental research and cautious translation into applied and clinical contexts.

Monte San Nicola (Sicily): Gelasian GSSP and base Quaternary/Pleistocene - L. Capraro; S. Bonomo; A. Incarbona; F.J. Hilgen; E. Zanola; A. Di Stefano; F. Dela Pierre; S. Ferraro; P. Ferretti; E. Fornaciari; S. Galeotti; P. Macrì; et al. (Quaternary Science Reviews, 2026)

Microscale sealed vessel (MSSV) technique in petroleum systems: a review - Sandra B. Jorge; André L.S. Pestilho; Juliana M. Sousa; Antônia M. Corrêa; Hemmely G. de S. Severino; Alice Maria S. Rodrigues; Kátia Z. Leal; Cleverson J.F. de Oliveira; Daniel S. Dubois; Marcelo C. Bernardes (Organic Geochemistry, 2026)

Microbial networks and soil properties influence surface biodegradation of polyethylene terephthalate (PET) and polylactic acid (PLA) in soil - Z.K. Holt; G.J. Herrera; L.U.S. Faria; S. Lupini; C.A.O. Nascimento; D.F. Rodrigues (Journal of Hazardous Materials, 2026)

Differential drought tolerance in two commercial açaí cultivars: Insights from gas exchange, chlorophyll fluorescence, and antioxidant responses - Patricia C. A. Navegantes; Wagner Romulo L. Lopes Filho; Flavio Henrique S. Rodrigues; Rosane Patricia F. Chaves; Roberto L. Cunha; Lucas C. Costa; Hugo A. Pinheiro (Trees, 2026)

Detection and mitigation of Paraphysomonas sp., a chrysophycean responsible for the collapse of industrial Tisochrysis lutea cultures - Mélissa José; Cristina Paulino; Lisa M. Schüler; Bruno Pinto; Mariana Carneiro; Alexandre M. C. Rodrigues; Filipe Pereira; Hugo Pereira; João C. S. Varela (Journal of Applied Phycology, 2026)
Microalgae are increasingly recognized as a sustainable resource to address challenges associated with climate change and population growth, owing to their capacity to produce high-quality biomass for applications in feed, food, and cosmeceuticals. However, the expansion of microalgae-based industries remains constrained by harmful biological contaminants (HBCs), which can rapidly reduce productivity, often signalled by visible changes in culture appearance (e.g., cell aggregation and discoloration), and may ultimately lead to culture collapse and substantial economic losses. In this study, the grazer Paraphysomonas sp. (Chrysophyceae) was identified as the most likely cause of Tisochrysis lutea culture collapse in a large-scale production facility using high-throughput amplicon sequencing of the 18S rDNA gene. To enable early detection of this HBC during the scale-up process, a species-specific primer pair targeting the 18S rDNA gene was developed and optimized, allowing detection of Paraphysomonas sp. at relative abundances as low as 0.1%. The contaminant was first detected at the final stage of scale-up, in a tubular photobioreactor. To further characterize the impact of the grazer and support mitigation strategies, its feeding behaviour was examined. Laboratory-scale mitigation trials showed that treatment with germanium dioxide (GeO 2 ) at 1 mg L⁻ 1 effectively delayed contaminant proliferation and prevented culture collapse without adversely affecting T. lutea growth. These findings highlight the value of integrating molecular monitoring with targeted mitigation strategies to improve early detection and management of HBCs in industrial microalgae production systems.

Conversion of MDF waste into CoCl2-functionalized activated carbon for enhanced phosphate removal from landfill leachate - A. G. dos Santos; L. C. S. Coelho; D. A. Bertuol; M. A. S. Rodrigues; E. H. Tanabe (International Journal of Environmental Science and Technology, 2026)

Brazil as a Global Leader in Soybean Production: Historical Trends, Current Status, and Future Perspectives - Grazielle Rodrigues Araujo; Felipe Lopes da Silva; Fernado S. Adegas; Edivaldo D. Velini; Ricardo Alcántara-de la Cruz (International Journal of Plant Production, 2026)
Soybean ( Glycine max L.) is the most widely cultivated oilseed globally due to its nutritional value, versatility, and economic importance. It accounts for nearly 25% of global vegetable oil production and is a key component in animal feed, making it strategic for food and energy security. Brazil has emerged as the world leader in production and exports, contributing ~40% of the 2024/25 harvest with approximately 171.5 million tons over ~47.4 million ha. This expansion has been driven by public policies, research investments, territorial expansion, and the widespread adoption of genetically modified (GM) varieties, now covering over 99% of the cultivated area. The transformation of the Cerrado into a major agricultural frontier, combined with technological advances, has resulted in substantial increases in area, production, and yield (~3.6 t ha − 1 in 2024/25). Despite these gains, yields remain far below the crop’s potential (>8.9 t ha − 1 in experimental fields), highlighting the presence of a persistent yield gap between current and attainable productivity levels. This review synthesizes the historical evolution of soybean production in Brazil and examines the main production drivers, structural constraints, and emerging innovation pathways shaping future productivity. Particular attention is given to the challenges associated with climate variability, environmental regulation, and increasing global demand for sustainable supply chains. The analysis highlights that future production gains will depend on the transition from expansion-driven growth to sustainable intensification, supported by technological innovation, improved management strategies, and effective governance.

Ex vivo validation of osteogenic efficacy in a bioceramic dual drug-delivery system - Miguel A. Rodrigues; Liliana Grenho; Rita Araújo; João P. Borges; Maria H. Fernandes; Pedro S. Gomes; José D. Santos; Maria A. Lopes (Drug Delivery and Translational Research, 2026)

Supervised Learning for Collagen Segmentation in Bright-Field Histology: A Comparative Evaluation of U-Net and MLP - Evelyn R. Silva; Lívia B. Souza; Fernanda S. Tenorio; Nilsa R. Damaceno-Rodrigues; Rita C. Marqueti; Karina R. Casali; Tatiana S. Cunha; Matheus C. Moraes (Annals of Biomedical Engineering, 2026)
Purpose Quantifying collagen in histological slides is essential for diagnosing and monitoring fibrosis. However, the combination of PicroSirius Red staining with polarized light microscopy, one of the standard techniques, requires expensive equipment and time-consuming procedures. This study investigated whether supervised machine learning algorithms applied to bright-field images could provide an automated and accurate method for collagen segmentation, reducing the dependence on polarized imaging. Methods A total of 140 histological images of renal, cardiac, and tendinous tissues from mice and rats stained with PicroSirius Red were analyzed. The images were fragmented into smaller patches, and the green channel was selected for non-polarized analysis. The reference standard was generated from polarized images binarized using ImageJ. Two supervised models were evaluated: (1) a Multilayer Perceptron (MLP) trained using five features (RGB intensities, median filter, and Wavelet), and (2) a U-Net architecture adapted to the image dimensions. Results Both models performed well, with the best results observed in rat tendon samples (Dice and precision > 80%). Performance was lower in mouse kidney images, possibly due to weaker staining and thinner collagen fibers. Overall, the MLP slightly outperformed the U-Net, which still showed comparable results. Conclusion The proposed methodology proved effective for collagen segmentation highlighting the potential of supervised learning to reduce costs and processing time in histological analysis. Future improvements include expanding the dataset and refining the reference standard to enhance robustness in biological tissue evaluation.

Hybrid evolutionary meta-optimization assisted by recurrent neural networks for interpretable parametric symbolic models - Flavio Adalberto Gomes; Wanderson Rainer H. Araujo; Marcio R. Cunha Reis; Geovanne Pereira Furriel; Guilherme Alberto S. Ribeiro; Viviane M. Gomes Pacheco; Marcella Scoczynski R. Martins; Clóves Gonçalves Rodrigues; Antonio Paulo Coimbra; Wesley Pacheco Calixto (Swarm and Evolutionary Computation, 2026)

A framework for assessing the environmental safety of wastewater treated by advanced oxidation processes based on species sensitivity distribution - Fernando Rodrigues-Silva; Carla S. Santos; Ana I. Gomes; Vítor J.P. Vilar; Maria Clara V.M. Starling; Camila C. Amorim (Science of The Total Environment, 2026)

WITHDRAWN: Inflammatory markers levels and clinical characteristics in COVID-19 susceptibility and severity: A cross-sectional multicentric study - Lucas C. Pedro; Camila O. Arent; Flávia S. Niero; Caion A. Rodrigues; Margarete D. Bagatini; Gabriela G. de Oliveira; Zuleide Maria Ignácio; Larissa Joaquim; Fabricia Petronilho; João Quevedo; Alexandra I. Zugno; Luciane B. Ceretta; et al. (Next Research, 2026)

Do not despise the little ones: population-level responses of common gobies to seasonality along latitudinal cline show biased vulnerability of southern populations - Carolina Madeira; Madalena Missionário; Diana Madeira; Carla António; Ana M. Rodrigues; Pedro M. Costa; Mário S. Diniz; Joana F. Fernandes; Catarina Vinagre (Marine Environmental Research, 2026)

Coffee silverskin fermentation in a single step for sustainable production of carbohydrate-based mixture rich in pectic oligosaccharides - Ana Cordeiro; Andreia Fernandes; Andreia S. Ferreira; Elisabete Coelho; Manuel A. Coimbra; António M. Peres; Lígia R. Rodrigues; Cláudia Amorim (Food and Bioproducts Processing, 2026)

Synthesis and application of silver-doped glass waste pellets for drinking water treatment - J. S. C. Vieira; J. D. A. do Ano; A. R. Pereira; A. da Costa Reis; F. W. Carvalho; I. A. da Silva; M. R. de Melo Rodrigues; E. M. V. de Carvalho; D. L. P. Macuvele; G. J. Muchave (International Journal of Environmental Science and Technology, 2026)

On vertical plasma drift measurements made by a new medium power incoherent scatter radar (MP ISR) mode at the Jicamarca Radio Observatory - Alexander A. Massoud; Anthony A. Abubakar; Fabiano S. Rodrigues; Karim M. Kuyeng; Marcos Inoñán; Danny E. Scipión (Advances in Space Research, 2026)

Dry–Hot Compound Events Driving the 2024 Pantanal Wildfires - Liz B. C. Belém; Ronaldo Albuquerque; Leonardo F. Peres; Filippe L. M. Santos; Julia A. Rodrigues; Lucas S. Menezes; Patrícia S. Silva; Ricardo M. Trigo; Carlos C. DaCamara; Ana Russo; João Geirinhas; Geraldo A. Damasceno Junior; et al. (International Journal of Climatology, 2026)
The year 2024 was classified by the World Meteorological Organization (WMO) as the hottest on record, both globally and in Brazil. In the Pantanal, exceptional heat waves and intense droughts led to an early onset of the fire season in June, marked by high fire severity and large burned areas. Although the Pantanal has been increasingly affected by combined drought and heat events, the influence of these climatic extremes on fire activity and the associated atmospheric circulation patterns is not well understood. This study assesses the conditions prior to the fire and the simultaneous occurrence of heat waves and droughts based on satellite data and climate indices; 2024 was identified as the most severe drought year over the 1980–2024 period, where virtually the entire biome reached exceptional drought levels. Heat waves were accompanied by significant precipitation and soil moisture deficits, along with the absence of the flood pulse in the rivers, reinforcing the compound nature of the 2024 extreme events. Synoptic conditions revealed patterns favourable to persistent warming and intensified drought, while fire risk indices exceeded the 99th percentile. These results highlight the need for a holistic approach when analysing the climatic factors driving fires, thereby advancing understanding of compound events and supporting public policies aimed at both mitigating and adapting to the impacts of climate extremes in the Pantanal.

Thermal and oxidative stress responses of Paecilomyces species recovered from beverage processing environments - Mailah Ali Abdul Rahman Mahfouz; Arthur Kael Rodrigues Pia; Rafaella Santos Mori Bragil; Naara Aparecida Almeida; Anderson S. Sant’Ana; Benedito Corrêa; Rodrigo Savio Pessoa; Liliana de Oliveira Rocha (World Journal of Microbiology and Biotechnology, 2026)

American Useful Plants in Post-Medieval Europe: Integrating Archaeobotanical and Historical Evidence - J. Irmišová; M. Ballesteros; J. J. Garay-Vázquez; C. Moricca; J. Skružná; T. Majerovičová; L. Speleers; S. Preiss; M. Badura; J. Wiethold; O. Brinkkemper; J. P. V. Tereso; et al. (Ethnobotany and Economic Botany, 2026)
The arrival of Europeans in the Americas in 1492 initiated new transatlantic connections that, through colonial expansion and trade networks, brought useful plants to Europe. This study investigates archaeobotanical and historical evidence for the introduction of American plants to Europe from the late fifteenth to the twentieth century. We compiled 183 archaeobotanical records from 14 countries, representing 24 taxa from 11 botanical families. We examined which American plant species were introduced to Europe during the post-medieval period, and how their uses and significance varied across regions and social contexts. Archaeobotanical data indicate that early introductions occurred predominantly in elite secular and ecclesiastical settings across Europe. Historical sources identify Spain as the first entry point, though other European countries yielded more records. The large number of archaeobotanical finds in the Netherlands and at the Habsburg court in Prague reflects the current state of research, site coverage, preservation, and data accessibility. The significance of these plants in Europe was shaped by economic value, prestige, ritual use, and medicinal properties. Our study highlights the importance of integrating archaeobotanical and historical sources and provides the most comprehensive account to date of material evidence tracing the cultural trajectories of American plants in Europe.

Chemical and Bioactivity Profiling of the Invasive Macroalga Rugulopteryx okamurae Collected in Southern Portugal Supporting Biotechnological Valorisation Approaches - Amandine D’Unienville; Lucas Lasnel; Wadi Macquigneau; Riccardo Trentin; Adriana C. S. Pais; Maria João Rodrigues; Sónia A. O. Santos; Luísa Custódio (Journal of Marine Science and Engineering, 2026)
The invasive brown macroalga Rugulopteryx okamurae has rapidly expanded across the Mediterranean–Atlantic region, generating severe ecological impacts. Nevertheless, the considerable amount of biomass available creates opportunities for valorisation within circular bioeconomy frameworks. This study provides an integrated characterization of the chemical profile and bioactivities of freshly collected floating biomass of R. okamurae from southern Portugal. Proximate composition was determined, and lipophilic (hexane) and hydrophilic (water) extracts were analyzed by GC–MS and spectrophotometric methods. Antioxidant activity was assessed using complementary radical-scavenging, reducing power, and metal-chelation assays, and enzyme inhibition was evaluated against targets associated with neurodegenerative, metabolic, and dermatological disorders. The lipophilic fraction was dominated by long-chain alkanes (≈101 mg/g extract) and sterols, particularly fucosterol (≈43 mg/g extract), but exhibited low radical-scavenging capacity (no EC50 reached in DPPH or ABTS assays), and no relevant enzyme inhibition. In contrast, the water extract contained measurable phlorotannins (6.61 mg PGE/g extract) and showed moderate antioxidant (ABTS: EC50 = 5.17 mg/mL; FRAP: EC50 = 0.78 mg/mL) and enzyme inhibition activities (BChE: IC50 = 5.17 mg/mL; tyrosinase: IC50 = 0.78 mg/mL). Compared with previous studies on R. okamurae, this work applies a systematic fractionation of biomass from southern Portugal into polar and non-polar fractions and, for the first time, correlates the resulting detailed chemical profiles with multiple bioactivities. This approach revealed a clear functional differentiation between fractions, with bioactivity being mainly associated with polar metabolites. Overall, these findings highlight the value of structured extraction strategies for biomass valorisation and support the sustainable management of R. okamurae.

Exploring EnMAP hyperspectral images and ensemble deep learning for classifying forest land-cover types in Brazil - Matheus Pinheiro Ferreira; Matheus Santos Fuza; José M. S. M Viveiros; Tomás Ferranti; Dário Oliveira; Giulio Brossi Santoro; Paulo Guilherme Molin; Catherine Torres de Almeida; Angélica F. Resende; Danilo R. A. de Almeida; Yelu Zeng; Ricardo Ribeiro Rodrigues; et al. (International Journal of Remote Sensing, 2026)

Microbiological quality of plant-based cheese analogues and pathogen behavior in cashew nut-based varieties - Jaqueline Sousa Correia; Dionisio Pedro Amorim-Neto; Emilie Lang; Matheus Péricles da Silva Láscaris; Beatriz Machado Dal Pian; Larissa Pereira Margalho; Arthur Kael Rodrigues da Pia; Bárbara Cipulo Legabão; Angelica Zaninelli Schreiber; Giulia Paes Strabelo; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2026)

How climate stressors intensify antibiotic toxicity: A histopathological study in zebrafish - Bárbara S. Diogo; Sara Rodrigues; Sara C. Antunes (Environmental Toxicology and Pharmacology, 2026)

Design and Evaluation of the Antibacterial Peptide FK18: a Therapeutic Approach for Mastitis in Dairy Animals - Tamaeh Monteiro-Alfredo; Camila de O. Gutierrez; Claudiane V. Almeida; Vinicius C. da Silva; Patrícia Gomes; Caio F. R. de Oliveira; Elisângela S. Madalozzo; Edson Crusca; Raquel M. Q. Orozco; Lucas Lima; Marlon H. Cardoso; Octávio L. Franco; et al. (Probiotics and Antimicrobial Proteins, 2026)

Targeting hypertension through natural phenolics: The multifaceted role of cinnamic acid and its derivatives - Samuel S. P. de Araujo; Brenda L. B. dos Santos; Waldilleny R. A. de Moura; Leonardo G. Rodrigues; Luiz G. S. Branco; Helio C. Salgado; Renato N. Soriano; Marina de T. Durand; João Paulo J. Sabino (Pflügers Archiv - European Journal of Physiology, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Prebiotics attenuate depressive-like behavior, neuroinflammation and synaptic plasticity in Parkinson’s disease by modulating butyrate-producing gut bacteria - Ingrid Prata de Mendonça; Rodrigo Soares da Silva; Igor Henrique Rodrigues de Paiva; Belmira Lara da S. A. Costa; Karla Patrícia de Sousa Barbosa Teixeira; José Roberto Botelho de Souza; Christina Alves Peixoto (Inflammopharmacology, 2026)
Parkinson’s disease (PD) remains a challenging disease for treatment, which is usually polypharmacological. In addition to motor symptoms, non-motor symptoms such as depression are present in approximately 40% of patients, contributing to the loss of quality of life. In the last two decades, a growing body of evidence has emerged regarding the involvement of the microbiota-gut-brain axis in both PD and depression. Fructooligosaccharides (FOS) and galactooligosaccharides (GOS) are prebiotic fibers that can be fermented by the gut microbiota, which produce metabolites called short-chain fatty acids (SCFAs), whose effects can contribute to improvement in neurodegenerative and psychiatric conditions. This study analyzed the effects of FOS and GOS administration in a rotenone-induced PD model and demonstrated a relief of motor symptoms and depressive-like behavior, followed by an increase of brain serotonin and its respective receptor (SERT). FOS and GOS treatment also led to an increase in SCFAs-producing gut bacteria with significantly higher levels of serum and brain butyrate. Furthermore, in the intestine, prebiotics reduced the accumulation of α-synuclein, decreased inflammation, and improved the expression of zonula occludens and occludin. FOS and GOS also attenuated the loss of dopaminergic neurons and reduced neuroinflammation by decreasing α-synuclein, IBA-1, GFAP, iNOS, p-NFkB, and IL1-β levels in the substantia nigra and prefrontal cortex. In addition, these prebiotics improved neuroplasticity by promoting the expression of butyrate receptors (GPR43 and GPR109), BDNF, p-CREB, and synaptic protein PSD-95. In conclusion, FOS and GOS administration attenuatted depressive-like behavior, neuroinflammation, and synaptic plasticity in Parkinson’s disease by modulating butyrate-producing gut bacteria.

Experimental assessment of ambient gamma dose equivalent rates measured outdoors in the Republic of Benin from 2019 to 2020 - Arnaud A. Gbetchedji; Daniel S. Takou; N. Innocent Gbaï; Mahougnon B. Zinsou; Hubert C. Hounsossou; Thierry C. M. Medehouenou; Rodrigue S. Allodji (Environmental Monitoring and Assessment, 2026)

Forest residue removal undermines soil health and micronutrient transfer to trees, compromising sustainable productivity of Eucalyptus plantations - Antonio L. Florentino; Nariane de Andrade; Nikolas S. Mateus; Bruna E. Schiebelbein; Adam C. Rodrigues; Liamara S. Masullo; Alexandre V. Ferraz; Eduardo Mariano; Fernando D. Andreote; Carlos E.P. Cerri; Maurício R. Cherubin; Timothy R. Filley; et al. (Soil and Tillage Research, 2026)

Temporal and spatial metal contamination trends in the Estrela River Basin, Guanabara Bay, Brazil - Breno Q.A. Rodrigues; João Barreira; Sarah K. Rodrigues; Jérémie Garnier; Myller S. Tonhá; Christian J. Sanders; Wilson Machado (Regional Studies in Marine Science, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Modeling of Listeria monocytogenes and Staphylococcus aureus behavior in salted and cured meat products - Matheus P.S. Láscaris; Jaqueline S. Correia; Dionisio P. Amorim-Neto; Beatriz D.P. Machado; Emilie Lang; Leonardo P. Silva; Augusto C.C. Santos; Juliana A.L. Pallone; David S. Costa; Camila A. Akiyama; Adriana P.A. Bragotto; Mayana A.R.V. Tomaz; et al. (International Journal of Food Microbiology, 2026)

Photoelectrocatalytic degradation of carbendazim using titanium‑tungsten oxide in a pilot-scale flow reactor - Joyce F. de Carvalho; Juliana de Almeida; Helena R. Tambelli; Ana Julia S. Rego; Maria Luiza P. da Silva; Débora N. Okamoto; Milene C. Codolo; Christiane de Arruda Rodrigues (Chemical Engineering Journal, 2026)

Rehydrated ground corn silage as alternative to feedlot lambs: feeding behavior and performance - Leandro A. S. da Silva; Cláudia L. S. Lima; Gleidson G. P. de Carvalho; Henry D. R. Alba; Maria L. G. M. L. de Araújo; Cláudia H. da Cruz; Carlindo S. Rodrigues; Dalton H. Pereira; José E. de Freitas Júnior; Manuela S. L. Tosto; Douglas dos S. Pina (Tropical Animal Health and Production, 2026)

Layered zinc hydroxide–dipeptide hybrid integrated into silk-based 3D scaffolds aiming for biomedical applications - Denise Eulálio; Mariana Pires Figueiredo; Simone S. Silva; Luísa C. Rodrigues; Emanuel M. Fernandes; Albino Martins; Albina Franco; Diana Soares da Costa; Richard Landers; Fabrice Leroux; Christine Taviot-Gueho; Dalva Lúcia Araújo de Faria; et al. (Applied Clay Science, 2026)

Synthetic cannabinoids in hair: a review of recent findings and analytical methods by LC-MS/MS - Rafaela S. Pereira; Olívia B.O. Moreira; Marcone Augusto L. de Oliveira; Claudiane C. Canuto; Diogo O.C. Lemos; Lucas M. Duarte; Silvana V. Rodrigues (Analytica Chimica Acta, 2026)

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

IMTA Production of Pacific White Shrimp Integrated with Mullet, Sea Cucumber, Oyster, and Salicornia in a Biofloc System - Enrique A. Estévez Hernández; Ivanilson Santos; Laura Moraes; Morena Salala Kashane; Marcelo H. Okamoto; Luís André Sampaio; Dariano Krummenauer; César S. B. Costa; Ricardo V. Rodrigues; Silvia Martínez-Llorens; Luís H. Poersch (Fishes, 2026)
Integrated multitrophic aquaculture (IMTA) emerges as a sustainable strategy to control the excess of solids and inorganic nutrients that tend to increase in the biofloc system (BFT) cycle, since the model integrates organisms from different trophic levels sharing the same system and nutrients. Thus, this study compared a Penaeus vannamei monoculture system with an integrated biofloc system including Mugil liza, Holothuria grisea, Crassostrea tulipa, and Salicornia neei, focusing on water quality and the performance of organisms and systems. This study consisted of three monoculture systems (16 m3; 375 shrimp m−3) and three IMTA systems, composed of a shrimp tank (16 m3), a mullet tank (4 m3; 30 ind m−3), a combined tank (3 m3) for oysters (45 ind m−3) and sea cucumbers (3 ind m−2), and a Salicornia neei bed (2.78 m2; 37 ind m−2). All IMTA systems operated in recirculation without water exchange, using 10% of the established biofloc inoculum. The IMTA system had half the hydrated lime use (2.13 vs. 4.29 kg), lower solids (299.56 vs. 373.33 mg L−1), and reduced sludge production (9.37 vs. 15.87 kg). Shrimp growth was similar in both systems. Mullet grew adequately with a survival rate of 95.8%, but oysters showed a survival rate of 45.7%. Sea cucumber had a survival rate of 100% until day 28, when a marked decline appeared, strongly correlated with rising temperature (>28 °C; r = −0.71). This resulted in a significant increase in solids in the last weeks, suggesting that the population decline reduces solids control capacity. Furthermore, the biofloc in IMTA was dominated by coccoid forms, with lower proportions of filamentous and cyanobacterial forms.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Reforestation strategies integrating tropical timber production can offset costs and finance forest restoration in the Brazilian Atlantic Forest - João Paulo Bispo Santos; Pedro Henrique Santin Brancalion; Mark S. Ashton; Florencia Montagnini; Claudia Fontana; Allana Katiussya Silva Pereira; Mário Tomazello-Filho; Vinicius Castro Souza; Daniel Piotto; Ricardo Ribeiro Rodrigues (Forest Ecology and Management, 2026)

Cork stripping alters the seasonal carbon allocation patterns of Quercus suber in a dry year - Clara A. Pinto; Filipe Costa-e-Silva; Alexandra C. Correia; José Graça; Olfa Zarrouk; Teresa S. David; José C. Rodrigues; João S. Pereira; Maria Manuela Chaves; Carla Pinheiro (Forest Ecology and Management, 2026)

Scaling up bedload monitoring: a passive acoustic approach for large river systems - J. Le Guern; P. Jugé; F.G. Latosinski; A. Andréault; C.L. Wintenberger; S. Rodrigues (Science of The Total Environment, 2026)

Uncertainty analysis of a CFD solver for predicting ship motions in head waves - M.I.P. Rodrigues; S. Wang; H. Islam; H.S. Abdelwahab; Jialong Jiao; C. Guedes Soares (Ocean Engineering, 2026)

Protected areas influence fire regimes globally - A. Cardil; M. Rodrigues; D. Ascoli; M. Ortega; T. Quiñones; M. Erdozain; I. Oliveras Menor; G.L. Spadoni; J. Ramírez; J.R. Molina; F. Mouillot; C.A. Silva; et al. (Journal of Environmental Management, 2026)

Unveiling the hidden consequences of mining tailings on ecosystem processes: Disruption of decomposition of native species in the Rio Doce watershed - João Carlos Figueiredo; Yule Roberta Ferreira Nunes; Walisson Kenedy-Siqueira; Renata Maia; Yumi Oki; Milton Barbosa; Débora Lima-Santos; Flávio Mariano Machado Mota; Daniel Negreiros; Letícia Ramos; Marcos Paulo dos Santos; Rebeca Ferreira Reis; et al. (Forest Ecology and Management, 2026)

Forecasting global building internal heat gains to 2100: an applied XGBoost model driven by shared socioeconomic pathways - Eugénio Rodrigues; Jaden Tinseth; Luka Pajek; Marco S. Fernandes (Energy and Buildings, 2026)

Tackling CECs and antimicrobial resistant bacteria in hospital wastewater using biological and AOP hybrid technologies - Eloísa Stéphanie da Silva; Alessandra S. Martins; Lara Fabian S. Ribeiro; Jhonatha Rodrigo Cordeiro-Moura; Daniel A.S. Rodrigues; Renata Cristina Picão; Maria Clara V. M. Starling; Camila C. Amorim (Bioresource Technology, 2026)

Hemocyte Apoptosis as a Biomarker of Environmental Stress in Aeglid Species (Decapoda: Anomura) - Renan A. P. dos Santos; Graziela G. Romagnoli; George S. Yasui; Isabela R. R. Moraes; Mariana V. Capparelli; Gabriel F. B. Rodrigues; Larissa R. C. de Oliveira; Antonio L. Castilho (Bulletin of Environmental Contamination and Toxicology, 2026)

All Reforestation Methods Can Support Tropical Tree Diversity Recovery, but Drivers and Species Composition Vary - Laura E. Boeschoten; Joannès Guillemot; Juliano van Melis; Lourens Poorter; Ricardo R. Rodrigues; Frans Bongers; Paulo G. Molin; Marielos Peña‐Claros; Vinicius C. Souza; Cássio A. P. Toledo; Patrick Faria Fernandes; Marcelo P. Ferreira; et al. (Global Change Biology, 2026)
Tropical landscapes are undergoing rapid transformation due to human activities and global change. Forest restoration has emerged as a key strategy to mitigate biodiversity loss and climate warming. However, a standardized assessment of how different restoration methods contribute to biodiversity recovery and conservation remains lacking. Here, we present the first comprehensive comparison of tree diversity restoration and the drivers of recovery across five main reforestation methods (naturally regenerating forests, biodiverse restoration plantings, short‐ and long‐rotation tree monocultures, agroforests) relative to three reference systems (agropastoral lands, degraded and conserved forest remnants). Tree inventories were conducted in 519 plots (900 m 2 each) across two forest types (rainforest and seasonally dry forest) in the Atlantic forest of São Paulo state, Brazil, encompassing over 39,000 trees and 869 species. We found that: (1) all reforestation methods except short‐rotation monoculture plots supported tree diversity recovery. In the rainforest, conserved remnant plots maintained the highest average Shannon diversity (Hill 1 = 29 ± 14), while naturally regenerating forests and restoration plantings approached the diversity of degraded remnant plots (15 ± 5). In seasonally dry forest, biodiverse restoration plantings and agroforests reached diversity levels comparable to conserved remnants (15 ± 6). Additionally, (2) recovery was influenced by forest age, climate (water availability), soil fertility, and landscape context, though the relative importance of these factors varied by method. Climate and landscape context were more influential for recovery in naturally regenerating forests, while soil conditions played a greater role in biodiverse restoration plantings. Lastly, (3) species composition in naturally regenerating forests most closely resembled that of conserved remnants. Conversely, restoration plantings and agroforests exhibited high compositional overlap across sites, reducing overall species richness. Our findings underscore the wide variation in biodiversity outcomes among and within reforestation methods, emphasizing that goals and strategies must align with local conditions to maximize benefits in complex tropical landscapes.

Waterfowl Move Less in Heterogeneous and Human‐Populated Landscapes, With Implications for Spread of Avian Influenza Viruses - Claire S. Teitelbaum; Diann J. Prosser; Joshua T. Ackerman; Sakib Ahmed; A. B. M. Sarowar Alam; Kazi Zenifar Azmiri; Nyambaya Batbayar; Joël Bêty; Abigail Blake‐Bradshaw; Dmitrijs Boiko; Nelleke H. Buitendijk; Jeffrey J. Buler; et al. (Ecology Letters, 2026)
Animal movements contribute to the spread of infectious diseases and are driven in part by environmental conditions. We investigated the links among the environment, animal movement, and infectious disease dynamics in waterfowl, which are among the primary wildlife hosts of avian influenza viruses. By combining telemetry data on 4606 individuals from 26 waterfowl species with data on land cover, weather, and vegetation, we found that waterfowl moved less in areas of higher land cover heterogeneity and higher human population density. Moreover, predicted waterfowl movement distances were weakly but positively correlated with distances between detections of H5N1 highly pathogenic avian influenza in wild waterfowl, suggesting that environmental conditions might contribute to the spread of this disease via their effects on bird movements. By considering wildlife movements alongside other drivers of infectious disease dynamics, such as livestock production and human mobility, we move closer to predicting outbreaks and informing interventions.

Myrcene suppressed fever by downregulating systemic TNF-α levels in acute LPS-induced systemic inflammation in rats - Maycon T. Emilio-Silva; Vinicius P. Rodrigues; Mariana M. Fioravanti; Luiz G. S. Branco; Clelia A. Hiruma-Lima (Advances in Traditional Medicine, 2025)

Vitamins B9 and B12 supplementation protects olfactory function and nigral tyrosine hydroxylase expression in a rotenone model of Parkinson's disease - Daniel A. Macedo; Lais S. Rodrigues; Jéssica L. Ilkiw; Evellyn M. de Azevedo; Adriano D.S. Targa; Marcelo M.S. Lima (Next Research, 2025)

Valorisation of olive oil by-products into pectic- and glucuronoxylo-oligosaccharides via one-step fermentation - Ana Cordeiro; Andreia Fernandes; Andreia S. Ferreira; Elisabete Coelho; Manuel A. Coimbra; Sara C. Silvério; Vasco Cadavez; António M. Peres; Lígia R. Rodrigues; Cláudia Amorim (Food Chemistry, 2025)

Cryopreservation of fish ovarian tissue post-mortem: Solution for emergency genetic preservation - Thaiza R. de Freitas; Lis S. Marques; Raquel S. dos Santos; Renata V. Dantas; Thales S. França; Rômulo B. Rodrigues; Karel G. Torres Lozano; Eduardo Albuquerque; Diógenes H. Siqueira-Silva; Tiantian Zhang; Danilo P. Streit (Cryobiology, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

SpiderATLAS : A Database of Spider Traits and Distributions in the Brazilian Atlantic Forest - Gabriel X. Boldorini; Paulo M. Martins; Antonio D. Brescovit; Adalberto J. Santos; Leonardo S. Carvalho; Ubirajara Oliveira; Philip Russo; Joyce C. B. Brito; Aparecida P. Barbosa; André Celso Bezerra Rodrigues; Aníbal Silva Cantalice; Arthur A. B. Rodrigues; et al. (Journal of Biogeography, 2025)
Aim Biodiversity shortfalls related to limited knowledge about geographic distribution (Wallacean) and species traits (Raunkiæran) are extremely common in many animal groups and perhaps more evident in invertebrate groups such as spiders. This lack of knowledge could present challenges for researchers investigating the response and effects of spiders along large spatial scales, particularly in the Global South. The aim of the SpiderATLAS is to facilitate research that links macroecology, biogeography, trait‐based ecology and global change biology. Location Brazilian Atlantic Forest, spanning virtually the entire eastern coastline of Brazil, encompassing 1,620,000 km 2 , 30 degrees of latitude (3° 42′ S to 33° 31′ S), and 22 degrees of longitude (34° 50′ W to 56° 45′ W). Taxon Spiders (Class Araneae), including 1648 species from 63 families. Methods We compiled the spatial distribution (i.e., occurrence data) and data on morphological characteristics and derived traits for spider species from species descriptions, taxonomic revisions and personal collection. Species occurrences were extracted from several data sources spanning from the 1880s to 2023. Data on the morphological traits of species were compiled from taxonomic and diversity inventory papers published between 1833 and 2024. Results We provide 9369 georeferenced point locations and six morphological traits (body length, prosoma length, prosoma width, prosoma height, femur I length, and patella I length) for 1648 spider species. Most data are available for females and males. The dataset and code are available to download from Dryad, World Spider Trait database, and the ZooTraits app. Main Conclusions The SpiderATLAS can be useful to access information on the distribution and traits of spiders, contributing to the development of macroecological, biogeographical and trait‐based ecology. This dataset can also facilitate the biodiversity conservation of one of the most abundant and important arthropod predators on the planet, in a biodiversity hotspot.

Assessment of antimicrobial, antiproliferative, and chemotactic properties of ranatuerin 2-PMe from cutaneous secretion of Lithobates palmipes (Spix, 1824) (Anura, Ranidae) - Géssica Gomes Barbosa; Carlos José Correia de Santana; Tulíbia Laurindo Silva; Welthon de Souza Teotonio; Lucas Fontes; Raquel Takaya; Ricardo Bentes de Azevedo; Patrícia Maria Guedes Paiva; Osmindo Rodrigues Pires Júnior; Wagner Fontes; Mariana S. Castro; Thiago Henrique Napoleão (Toxicon, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Patterns of pharmaceutical contamination in streams of European cities across urbanisation gradients: Potential impacts on One Health - Fernanda Rodrigues; Ana R. Calapez; André M.P.T. Pereira; Liliana J.G. Silva; Andreia Freitas; Rayan Bouchali; Andree De Cock; Marie Anne Eurie Forio; Peter Goethals; Silje H. Henni; Adeline Loyau; Anne Moen; et al. (Journal of Hazardous Materials, 2025)

Ultrasound-enhanced bioaccessibility and pharmacological activities of curcumin in inclusion complexes - Matheus X. Oliveira; Irisvan S. Ribeiro; Francisca Vanessa C. Canafístula; Stephanie Ferreira M. Muniz; Lorena Maria F. Sampaio; Alyne Rodrigues A. Nobre; Fábio Oliveira S. Ribeiro; Raí E. Silva; Jessica Maria T. Souza; Erick Joniher B. Torres; José Delano Barreto M. Filho; Ana J. Araújo; et al. (Food Chemistry, 2025)

The use of electrodialysis for the removal of metals from aqueous solutions - C. L. S. dos Santos; M. S. Rodrigues; F. S. Moreira; V. L. Cardoso; M. M. de Resende (International Journal of Environmental Science and Technology, 2025)

Metabolomic profiles and antioxidant intake in female soccer players: a cross-sectional study - M. M. S. Gouveia; M. B. A. Nascimento; A. C. Crispim; E. R. da Rocha; M. P. P. Santos; E. S. Bento; T. M. Aquino; P. Balikian; N. A. Rodrigues; T. Ataide-Silva; G. G. de Araujo; F. A. B. Sousa (European Journal of Applied Physiology, 2025)

The Functional Role of Specific Habitats for the Daily Routine of Juvenile Spoonbills in Protected Coastal Wetlands - Manuela S. Rodrigues; Pedro M. Araújo; Jaime A. Ramos; Pedro C. Rodrigues; Afonso D. Rocha; João P. Silva; José A. Alves (Estuaries and Coasts, 2025)
Wetlands are decreasing globally and species that depend on these habitats must adjust their behaviour or may face population declines. Protected wetlands designed for the conservation of certain species may fail to meet their objectives if habitats critical for specific behaviours are degraded, even if other habitats remain unaffected. It is therefore important to better understand the functional role of specific coastal wetland habitats and when species need them. We investigated the behaviour of juvenile spoonbills ( Platalea leucorodia ) from two Portuguese protected wetlands: the Tagus estuary and Ria Formosa coastal lagoon. Forty-four juvenile spoonbills were equipped with GPS/GSM tags with a 3-axial accelerometer, which allowed integrating spatially explicit behaviour with land use data. We then explored how habitat use changes with diel and tidal cycles within these dynamic landscapes and assessed the functional role of habitats. Juvenile spoonbills vary their daily routines according to the composition of habitats in their natal wetland, with the diel cycle being more influential in the Tagus estuary, while in Ria Formosa both cycles (diel and tidal) were of similar relevance. Habitats were used differently within the study areas: intertidal flats accounted for 62.09% of feeding activity in Ria Formosa versus 47.16% in the Tagus estuary, where rice fields represented the highest feeding percentage (52.27%). This work highlights the need for species- and site-specific studies and can serve as a template for understanding habitat use by other species (or different life stages) to support the development of targeted conservation measures.

New records of frogs (Anura, Lissamphibia) from the Late Cretaceous Bauru Group of Brazil and its paleobiogeographic implications - Fellipe Muniz; Ariovaldo Giaretta; Thiago S. Fachini; Thiago da Silva Marinho; Pedro Buck; Sabrina Rodrigues; Agustín G. Martinelli (Cretaceous Research, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Recovery of tree species functional composition in eucalypt plantations with natural regeneration differs among canopy strata - Laura H.P. Simões; Marielos Peña-Claros; Joannès Guillemot; Rens Brouwer; Frans Bongers; Lourens Poorter; Catherine T. de Almeida; Danilo R.A. Almeida; Miguel Cooper; Mathieu Decuyper; José G. Fernandes Neto; Matheus S. Fuza; et al. (Forest Ecology and Management, 2025)

Twelve-year residual effect of sewage sludge on the biogeochemical cycling of potentially toxic elements in tropical Eucalyptus plantation - Antonio L. Florentino; Alexandre V. Ferraz; Adam C. Rodrigues; Nikolas S. Mateus; Paulo H.S. Cardoso; Timothy R. Filley; Eduardo Mariano; José Lavres; José L.M. Gonçalves; Cassio H. Abreu-Junior (Forest Ecology and Management, 2025)

Luteal features and serum concentrations of progesterone and hCG in dairy goats submitted to estrus induction followed by intrauterine or intramuscular hCG administration - Alice L. Martins; Luana R. Côrtes; Juliana N.D. Rodrigues; Paulo Sergio C. Rangel; Ana Lucia R. e S. Maia; Felipe Z. Brandão; Luiz Gustavo B. Siqueira; Bruna W. de Freitas; Jeferson F. Fonseca (Domestic Animal Endocrinology, 2025)

Chronic toxicity of antibiotics and global warming in Danio rerio: Biomarker responses and toxicological effects - Bárbara S. Diogo; Sara Rodrigues; Bent Speksnijder; Oksana Golovko; Sara C. Antunes (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Direct U–Pb dating of vitrinite in coal - Beilei Sun; Yuexing Feng; Sandra Rodrigues; Charlotte M. Allen; Joan S. Esterle (Chemical Geology, 2025)

Exploring In Vitro Mesenchymal Stem Cell Osteodifferentiation via Vibrational Microspectroscopy: A Review - Daniela S. Bispo; Inês C. R. Graça; João A. Rodrigues; João T. S. Martins; Mariela M. Nolasco; Maria P. M. Marques; Helena I. S. Nogueira; João F. Mano; Mariana B. Oliveira; Paulo J. A. Ribeiro-Claro; Ana M. Gil (Stem Cell Reviews and Reports, 2025)
The application of vibrational microspectroscopy to the study of in vitro mesenchymal stem cells (MSC) osteogenic differentiation is a promising approach towards the understanding of the molecular processes involved in bone fabrication. Both infrared (IR) and Raman microspectroscopies have been applied, with a clear predominance of the latter. Bone marrow MSC have been the target of most studies, followed by those originating from dental/oral and adipose tissues. Interests have increasingly addressed single cell and extracellular matrix characterization at the molecular level. Most studies have focused on the characteristics and maturity of time-course mineralization, attempting to localize mineral aggregates formed onto the evolving collagen strands. Some reports have focused on time-dependent changes in protein structure and other components of extracellular matrix components. Besides spectral band examination through position, linewidth and shape, selected band ratios have proved largely informative to assess mineral species evolution and mineral-to-organic matrix interactions over time. The increasing use of multivariate analysis (or chemometrics) and machine learning strategies to detect finer spectral variations is evident, as is the promise of more recent IR and Raman variations to provide higher sensitivity and spatial resolution conditions. The label-free non-invasive nature of vibrational microspectroscopy makes it particularly promising for rapid and effective selection of suitable MSC donors, to support scale-up procedures for translation to the clinic. Some of the challenges to be faced are briefly discussed. Graphical Abstract

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Climate change scenarios differentially modulate the impact of invasion in a native macrophyte species - Tauany Rodrigues; Joseph L. S. Ferro; Reinaldo L. Bozelli; Aliny P. F. Pires; Vinicius F. Farjalla (Limnology and Oceanography, 2025)
Biological invasion and climate change threaten freshwater ecosystems, potentially amplifying their impacts through interaction. However, empirical evidence on how future climate scenarios influence the invasion process and their interactive effects on native species remains limited. We conducted a full‐factorial experiment to evaluate the independent and interactive effects of Hydrilla verticillata invasion and future climate scenarios (baseline, mitigation, and business‐as‐usual) on the native macrophyte Cabomba caroliniana . We also assessed the response of the non‐native H. verticillata to these climate scenarios. The climate change mitigation scenario maintained the invasive potential of H. verticillata , as indicated by its vertical growth and colonization potential via vegetative propagules, which were comparable to baseline conditions. Simultaneously, the mitigation scenario supported the vertical growth and production of C. caroliniana at levels similar to those under the baseline. Under the business‐as‐usual scenario, H. verticillata exhibited enhanced vertical growth and colonization capacity via vegetative propagules. Interestingly, its presence under the business‐as‐usual scenario was associated with increased vertical production of the native species. Although invasion appeared to buffer the adverse effects of extreme climatic stress, it merely enabled C. caroliniana to recover vertical production to baseline and mitigation levels, rather than providing a long‐term advantage. Our findings highlight the ecological benefits of climate change mitigation and the complex outcomes arising from the interaction between invasion and future climate scenarios for native species.

P04-05 Time-resolved reprogramming of metabolism in rats exposed to air pollutants: a serum NMR metabolomics approach for the investigation of dose-response and hazard assessment - B. Métoyer; N. Chouan; B. Rival; M. Cherrière; A. Lecomte; F. Robidel; S. Rodrigues; M. Floreani; G. Barbier; G. Lacroix; T. Loret; M. Valente; et al. (Toxicology Letters, 2025)

Volcanic environments and thyroid disruption – A review focused on As, Hg, and Co - Nádia M.P. Coelho; Filipe Bernardo; Armindo S. Rodrigues; Patrícia Garcia (Science of The Total Environment, 2025)

Acid-modified titanate nanotubes for enhanced photocatalytic removal of contaminants of emerging concern in water - Guenther Carlos C. Viana; Djalma L.S. Maia; Daniel A.S. Rodrigues; Lara Fabian S. Ribeiro; Italo O. Mazali; Fernando Rodrigues-Silva; Maria Clara V.M. Starling; Thiago A. Neves; Camila C. Amorim (Journal of Water Process Engineering, 2025)

Redox structure of a saline lake during the Barremian-Aptian, Sanfranciscana Basin, southeast Brazil - Willian Alexandre Lima de Moura; Gabriel Jubé Uhlein; Fabricio de Andrade Caxito; Jonathas S. Bittencourt; René Rodrigues; Alcides N. Sial; Egberto Pereira (Journal of South American Earth Sciences, 2025)

Preservation and detection of carotenoid pigments of Deinococcus radiodurans on mineral substrates under UV irradiation - Tamires Gallo; Fabio Rodrigues; Evelyn A.M. Sanchez; Fabio S. de Vicente; Veronica C. Teixeira; Evandro P. Silva; Marcia Rizzuto; Gabriel S. Teofilo-Guedes; Douglas Galante (Icarus, 2025)

Microencapsulation of Pediococcus pentosaceus using cupuassu flour-based as wall material: Application and impact on petit suisse cheese - Katherine Gutiérrez-Álzate; Gabriele de Abreu Barreto; Bruna Samara S. Rekowsky; Letícia Alencar Pereira Rodrigues; Deborah Murowaniecki Otero; Marion Pereira da Costa (Food Bioscience, 2025)

Dual environmental stressors: How pH modulates antibiotic toxicity in Danio rerio? - Bárbara S. Diogo; Sara Rodrigues; Oksana Golovko; Sara C. Antunes (Environmental Toxicology and Pharmacology, 2025)

Trace elements and iron speciation analysis of Paleoproterozoic phyllite from the Gandarela Syncline: Implications for salinity and redox conditions in the Quadrilátero Ferrífero, Brazil - Janaina Rodrigues de Paula; Wei Wei; Fabricio A. Caxito; Katherine N. Snihur; Cody N. Lazowski; Kurt O. Konhauser; Erik A. Sperling; Daniel S. Alessi (Chemical Geology, 2025)

Co-fermentation of sugar-alcohol industry waste to produce hydrogen and value-added metabolites - Bruna S. Dionizio; Camila A.B.S. Rabelo; Caroline V. Rodrigues; Franciele P. Camargo; Edson L. Silva; Dulce H.F. de Souza; Maria Bernadete A. Varesche (Bioresource Technology Reports, 2025)

Enteric methane emissions and thermal comfort indexes of Nellore steers in a livestock-forestry system in the Amazon biome - Alyce Monteiro; Flabiele S. Silva; Adibe L. Abdalla; Maguy Eugène; Luciano Barreto-Mendes; Renato A. R. Rodrigues; Ciro A. Magalhães; Bruno C. Pedreira (Tropical Animal Health and Production, 2025)

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Application of graphene oxide incorporated into biopolymer microfibers as a novel adsorbent for removing pharmaceuticals from water - L. Pellenz; A. H. da Silva Júnior; C. R. S. de Oliveira; L. P. Mazur; L. H. I. Mei; N. M. Medeiros Rodrigues; A. A. U. de Souza; A. da Silva (International Journal of Environmental Science and Technology, 2025)

Phase relations and solidus temperature of garnet lherzolite at 5 GPa revisited - Rodrigo Freitas Rodrigues; Gregory M. Yaxley; Balz S. Kamber (Contributions to Mineralogy and Petrology, 2025)
Partial melting experiments on a mildly depleted peridotite (GKR-001) conducted in a piston-cylinder apparatus provide new insights into the solidus of anhydrous peridotite, melting relations and reactions, and residue compositions at 5 GPa. These have important implications for melting conditions relevant to cratonic lithosphere, the petrogenesis of komatiites and orthopyroxene-enriched peridotites. The solidus of GKR-001 was identified at 1575ºC. As melting progressed, clinopyroxene melted out at ~ 1650ºC, closely followed by garnet at ~ 1670ºC and orthopyroxene at ~ 1725ºC. Orthopyroxene remained stable throughout most of the melting interval. Clinopyroxene's incongruent melting initiated peritectic reactions (Ol + Cpx + Grt = Opx + Melt) at melting degrees ≥ 8%, forming additional orthopyroxene in the residue. Clinopyroxene exhausted at around 24% melting, while garnet-out was encountered at slightly higher melting degree (~ 34%). Orthopyroxene reached its maximum content in the residue after ~ 24% melting and was dissolved back at melting degrees > 45%. The melts formed at ≥ 8% melting are Ti-depleted komatiites (30.7–43.6 Al 2 O 3 /TiO 2 ), consistent with melting of a slightly depleted peridotitic source. Melts in equilibrium with a garnet-bearing residue have CaO/Al 2 O 3 ratios > 1, while those formed above the garnet-out curve have ratios < 1. Residues from GRK-001 exhibit higher SiO 2 contents than those produced after the partial melting of pyrolytic compositions (KR4003). However, high-pressure partial melting of GKR-001, albeit producing quite orthopyroxene-rich residues at moderate degrees of melting, cannot produce the silica-rich peridotites observed in many cratonic lithospheres worldwide. Comparison between thermodynamic modelling and experimental results reveals inconsistencies in the garnet and pyroxenes stability fields and the absolute temperature of the solidus.

A novel approach for assessments of radiofrequency electromagnetic fields exposure in buildings near telecommunication infrastructure - Ricardo Q. de F.H. Silva; Marcio E.C. Rodrigues; Fred S.R. Pinheiro; Gutembergue S. da Silva; Marília da C. Muniz; Leonardo S. Pinto; Halysson B. Mendonça; Vicente A. de Sousa (Science of The Total Environment, 2025)

Estimating the air quality standard exceedance areas and the spatial representativeness of urban air quality stations applying microscale modelling - F. Martín; V. Rodrigues; J.L. Santiago; J. Sousa; J. Stocker; S. Janssen; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; R. San José; et al. (Science of The Total Environment, 2025)

ESTIMET: Enhanced and Spatial-Temporal Improvement of MODIS EvapoTranspiration algorithm for all sky conditions in tropical biomes - Cinthia M.A. Claudino; Guillaume F. Bertrand; Rodolfo L.B. Nóbrega; Cristiano das N. Almeida; Ana Cláudia V. Gusmão; Suzana M.G.L. Montenegro; Bernardo B. Silva; Eduardo G. Patriota; Filipe C. Lemos; Jaqueline V. Coutinho; José Welton Gonçalo de Sousa; João M. Andrade; et al. (Remote Sensing of Environment, 2025)

Electrical stimulation of table grape berries as new alternative for postharvest Escherichia coli contamination management - Mariana P. Fernandes; Flávio Rodrigues; Vanessa F. Cardoso; Filipe S. Silva; Margarida M. Fernandes (Postharvest Biology and Technology, 2025)

Multistage treatment system integrating constructed wetlands and microalgae for wastewater reuse and bioenergy recovery - Gustavo S. Colares; Luana T. Junqueira; Fernanda N. Brum; Romualdo J.C. Wanderley; Tainá Conzatti; Lenin D. Garcia; Lucia H.R. Rodrigues; Carlos A. Lutterbeck; Ênio L. Machado; Odorico Konrad (Journal of Water Process Engineering, 2025)

Polymer-specific stress responses in planarians exposed to microplastics of similar size - Rone S. Barbosa; Ana L. Patrício Silva; Andreia C.M. Rodrigues; Amadeu M.V.M. Soares; Renato Almeida Sarmento; Carlos Gravato (Aquatic Toxicology, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Fermented brewer's spent grain as a sustainable feed ingredient impacts meagre (Argyrosomus regius) growth, intermediary metabolism, digestive enzymes, oxidative stress, and intestinal histology - T. Estevão-Rodrigues; H. Fernandes; S. Moutinho; A. Couto; I. Belo; C. Castro.; P. Pousão; J.M. Salgado; A. Oliva-Teles; H. Peres (Animal Feed Science and Technology, 2025)

Determinants of Cyanobacteria and Algae Diversity in Natural Freshwater Micro‐Ecosystems - Yasmin Rodrigues de Souza; Beatriz Melissa Campos; Fernando Miranda Lansac‐toha; Annika Busse; Jana S. Petermann; Gustavo Quevedo Romero; Pablo Augusto Poleto Antiqueira; Luzia Cleide Rodrigues (Environmental Microbiology, 2025)
In this context, estimating the contributions of single sites to overall beta diversity (LCBD—Local Contribution to Beta Diversity, i.e., indicator of site's ecological uniqueness) or partitioning overall beta diversity into contributions of individual species (SCBD—Species Contribution to Beta Diversity, i.e., degree of variation of individual species across the study area) has proven to be a good approach to improve the knowledge of drivers of beta diversity. The number of studies on beta diversity in hyperdiverse environments, such as the Neotropics, is still scarce. We explored the contributions of each site and species to the overall cyanobacteria and algae beta diversity of 77 natural freshwater micro‐ecosystems (i.e., tank bromeliads) of a neotropical ecosystem. We observed that LCBD was negatively related to Shannon diversity, turbidity and luminosity (% canopy cover). The negative relationship between LCBD and Shannon diversity indicates that micro ecosystems with less diversity reflect unique characteristics, and LCBD values can predict these environments. In our study, high LCBD values indicated environments in need of restoration, that is, poor in species richness and with greater turbidity and luminosity, showing that most bromeliad tanks presented high species diversity and low turbidity and luminosity.

Asparagopsis taxiformis Feed Supplementation as a Tool to Improve the Resilience of Farmed Diplodus sargus to Marine Heatwave Events—A Metabolomics Approach - Marta Dias; Isa Marmelo; Carla António; Ana M. Rodrigues; António Marques; Mário S. Diniz; Ana Luísa Maulvault (Fishes, 2025)
The need to maximize aquaculture production while addressing environmental and food security challenges posed by climate change has driven research towards the development of functional aquafeeds that enhance performance and immunity in farmed species. However, exposure to dietary and environmental stressors affects marine organisms, altering key metabolic pathways best understood through high-throughput “omics” tools. This study assessed the effects of Asparagopsis taxiformis supplementation on central metabolic pathways by analyzing changes in primary metabolite levels in the liver of farmed Diplodus sargus under optimal and suboptimal temperature conditions. Results showed that seaweed supplementation had a beneficial effect on the fish’s primary metabolome; however, inclusion levels and rearing conditions played a crucial role in determining outcomes. While 1.5% supplementation maintained a balanced primary metabolome under optimal temperature conditions, 3.0% supplementation most effectively mitigated the adverse effects of acute thermal stress during a marine heatwave. These findings highlight the nutritive and functional potential of A. taxiformis supplementation in aquafeeds for marine omnivorous fish species and emphasize the importance of evaluating functional aquafeeds under suboptimal rearing conditions. Overall, our results demonstrate the value of metabolomics in elucidating the molecular basis underlying biological pathways in farmed marine fish and optimizing production through climate-smart dietary strategies.

Plastic contamination and lesions observed in Cory’s shearwaters (C. Borealis) from the Azores archipelago - a pilot study - M. Pinto; M. Almeida; G. Carreira; S. Garcia; C. Rodrigues (Journal of Comparative Pathology, 2025)

Survival analysis of female dogs and cats with rare and uncommon malignant mammary tumours - preliminary results - J.N. Pontes; C. Pereira; J. Rodrigues-Jesus; A. Santos; A. Catarina Figueira; S. Guedes; F. Seixas; M. dos Anjos Pires; A. Alves; F. Ferreira; J. Correia; P. Faísca; et al. (Journal of Comparative Pathology, 2025)

Comprehensive machine learning assessment of zebrafish behaviour and biochemical markers in response to caffeine exposure - Cláudia Teixeira; Sara Rodrigues; João Amorim; Bárbara S. Diogo; Ivo Pinto; António Paulo Carvalho; Sara C. Antunes; Luís Oliva Teles (Ecotoxicology, 2025)
Environmental exposure to caffeine (CAF) poses potential risks to aquatic ecosystems, affecting non-target species. This study investigated the chronic effects of environmentally relevant CAF concentrations, ranging from 0.16–50 µg/L, on zebrafish behaviour. A Kohonen-type artificial neural network classified zebrafish behaviour into nine behavioural classes based on a set of movement descriptors (mean meander, mean velocity, instantaneous velocity, distance to centre point, mean angular velocity and instantaneous acceleration), while a comprehensive analysis integrated behavioural classes previously defined and biochemical markers of oxidative stress, lipid peroxidation, reserve energy content, energetic pathways, and neurotoxicity. The discriminant analysis demonstrated that behaviour descriptors and biomarkers individually explained 38% and 67% of data variation, respectively, while the combination resulted in 19 models with 100% correct diagnosis. One of the models (Model A) seemed to suit the best dose-response relationship, incorporating key biomarkers including superoxide dismutase, catalase, glutathione peroxidase activities, and behavioural characteristics such as movement distance and velocity. This suggested methodology offers a different approach to evaluating CAF’s ecological impact, highlighting behavioural analysis as a valuable complement to traditional ecotoxicological assessments. This study provides a novel framework for understanding organism-level responses to environmental stressors (e.g., several anthropogenic compounds), utilising Mahalanobis distance as an integrative response index. This approach shows promise for broader application in assessing the impact of various aquatic contaminants on aquatic organisms (from bacteria to fish), potentially extending to pharmaceuticals, pesticides, and industrial pollutants.

Unlocking biochemical profile of Chaetoceros calcitrans, Cylindrotheca fusiformis, and Nannofrustulum shiloi (Bacillariophyta) for nutritional and added-value applications - Ana S.P. Moreira; Helena R. Rocha; Susana Aveiro; Andreia S. Ferreira; Kayane Oliveira; Alexandra Conde; Marta Coelho; Alexandre M.C. Rodrigues; Natacha Coelho; Hugo Pereira; Ana Gomes; Manuela Pintado; et al. (Algal Research, 2025)

Comparisons of Hyperostotic Bones in Two Species of the Genus Oligoplites Gill, 1863 in the Southern Brazilian Coast - Fernando A. P. Tuna; Ana Paula C. de Rodrigues; Gustavo P Filgueira; Rebeca s da Bianca; Wilson T. V. Machado; Márcia C. Salomão; Helena P. Lavrado (Journal of Fish Diseases, 2025)
The description of skeletal disorders is commonly reported in fish species raised through aquaculture; however, wild marine fish may also exhibit high frequencies of anomalies, particularly the development of hyperostosis, a condition that causes thickening of the bones. Specimens of Oligoplites saliens ( n = 15) and Oligoplites palometa ( n = 14) were radiographed to verify hyperostotic bone occurrences. Hyperostosis was detected in all individuals (> 400 mm TL) analysed for both species, occurring in six distinct regions of the skeleton (supraoccipital bone, cleithrum, dorsal pterygiophores, anal pterygiophore, haemal spines, and neural spines), regardless of the sex of the individuals. No hyperostosis was found in the neural and haemal spines of O. palometa and in the anal pterygiophore of O. saliens . Histological sections of the supraoccipital bone of O. saliens were conducted, revealing high porosity characterised by the presence of vascular channels in bones with hyperostosis. The species exhibited species‐specific patterns for the condition, demonstrating differences even among species of the same genus occurring in the same geographic area. This is the first record of hyperostosis for both species in Brazilian waters.

Evidence of synbiotic potential of oat beverage enriched with inulin and fermented by L. rhamnosus LR B in a dynamic in vitro model of human colon - G.A. Fabiano; R.P.S. Oliveira; S. Rodrigues; B.N. Santos; K. Venema; A.E.C. Antunes (Food Research International, 2025)

Bacterial cellulose biosynthesis in the presence of raw moist olive pomace: A green sustainable approach that enhances biopolymer production and properties - Pedro J.L. Crugeira; Halima Khelifa; Luísa M.da S. Barreira; Noureddine Halla; António M. Peres; Tatiana B. Schreiner; Maria Filomena F. Barreiro; Paula Rodrigues (Biomass and Bioenergy, 2025)

LDL Exposure Disrupts Mitochondrial Function and Dynamics in a Hippocampal Neuronal Cell Line - Hémelin Resende Farias; Jessica Marques Obelar Ramos; Caroline Tainá Griesang; Lucas Santos; Osmar Vieira Ramires Junior; Debora Guerini Souza; Fernanda Silva Ferreira; Sabrina Somacal; Leo Anderson Meira Martins; Diogo Onofre Gomes de Souza; José Cláudio Fonseca Moreira; Angela T. S. Wyse; et al. (Molecular Neurobiology, 2025)

Unveiling the Genomic Landscape of Understudied Salmonella enterica Serovars from Poultry and Human: Implications for Food Safety - Valdinete P. Benevides; Mauro M. S. Saraiva; Viviane A. Ferreira; Michelli Inácio G. Funnicelli; Lucas B. Rodrigues Alves; Adriana M. Almeida; Henrik Christensen; John E. Olsen; Angelo Berchieri Junior (Current Microbiology, 2025)

The caatinga dry tropical forest: A highly efficient carbon sink in South America - Keila R. Mendes; Pablo E.S. Oliveira; José Romualdo S. Lima; Magna S.B. Moura; Eduardo S. Souza; Aldrin M. Perez-Marin; John Elton B.L. Cunha; Pedro R. Mutti; Gabriel B. Costa; Thales N. Martins de Sá; Paula A.A. Araujo; Rosaria R. Ferreira; et al. (Agricultural and Forest Meteorology, 2025)

Mitigating Shear Stress in Spray Drying for RNA-Loaded Lipid Nanoparticles through Process and Formulation Optimization - Susana Farinha; Rute Mota; Carolina Lopes; Ricardo Velez; Mara G. Freire; Ana Aguiar-Ricardo; Miguel Ângelo Rodrigues; Luís Marques; Joana S. Cristóvão; Paulo Roque Lino (AAPS PharmSciTech, 2025)

Deregulation of Neuroinflammatory and Neurotrophic Factors as Biological Events Triggered by D-Galactose Chronic Administration in Wistar Rats - Eduarda Behenck Medeiros; Sabrina da Silva; Francielle Mina; Adrielly Vargas Lidio; Amanda Boaventura; Laura Ceolin de Jesus; Michelle Lima Garcez; Gabriel Casagrande Zabot; Gabriela Piovesan Fenilli; Matheus Scarpatto Rodrigues; Jade de Oliveira; Samira S. Valvassori; et al. (NeuroMolecular Medicine, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effects of soybean molasses on ruminal fermentation pattern, performance and meat quality of feedlot sheep - Sérgio A.G. Pereira-Junior; Juliana A. Torrecilhas; Rayanne V. Costa; Edivilson S. Castro Filho; Maria Carolina G. Arruda; João Pedro A. Bertoco; Andresa L. Feliciano; Julia L. Rodrigues; Rosemary L. Galati; Angélica C. dos Santos; Marcos R. Chiaratti; Ricardo P. Nociti; et al. (Small Ruminant Research, 2025)

Exploring plant functional traits and their relationship to biomass dynamics in secondary forests in Eastern Amazonia - Luane Botelho; Fernando Elias; Beatriz V. Barbosa; Karoline C. Silva; Vanessa Negrão-Rodrigues; Euciney E.S. Barbosa; Jucelino S. Coutinho; Joice Ferreira; Jos Barlow; Grazielle Sales Teodoro (Flora, 2025)

Optimizing torrefaction of banana waste (peels and rachis) for sustainable biocoal production in rural communities - Igor F. Mendonça; Gabriel S. do Vale; Rafael B.W. Evaristo; Rômulo C. Dutra; Pedro Paulo de Oliveira Rodrigues; Edgar A. Silveira; Grace Ghesti (Biomass and Bioenergy, 2025)

Estimation of diurnal and nocturnal radiation balance in tropical ecosystems - D. O. Maionchi; I. J. C. de Paulo; S. R. de Paulo; J. B. Marques; A. L. P. Junior; H. J. A. da Silva; R. S. Palácios; T. R. Rodrigues; T. A. dos Santos; A. M. S. Lima; M. S. Biudes; L. Sanches; et al. (Theoretical and Applied Climatology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Correction to: Potential of Marine Strains of Pseudoalteromonas to Improve Resistance of Juvenile Sea Bass to Pathogens and Limit Biofilm Development - A. Rahmani; L. Parizadeh; M. Baud; Y. Francois; A. Bazire; S. Rodrigues; Y. Fleury; H. Cuny; E. Debosse; J. Cabon; L. Louboutin; L. Bellec; et al. (Probiotics and Antimicrobial Proteins, 2025)

Potential of Marine Strains of Pseudoalteromonas to Improve Resistance of Juvenile Sea Bass to Pathogens and Limit Biofilm Development - A. Rahmani; L. Parizadeh; M. Baud; Y. Francois; A. Bazire; S. Rodrigues; Y. Fleury; H. Cuny; E. Debosse; J. Cabon; L. Louboutin; L. Bellec; et al. (Probiotics and Antimicrobial Proteins, 2025)

Detection of an Alphacoronavirus in a Brazilian Bat (Molossus sp.) - C. L. Molina; M. M. Magalhães; A. C. Rodrigues; S. A. Taniwaki; S. O. de Souza Silva; G. A. König; P. E. Brandão (Journal of Molecular Evolution, 2025)

Recruitment of pulmonary intravascular macrophages in SARS-CoV-2 infected hamsters - Carolina Rego Rodrigues; Gurpreet Kaur Aulakh; Andrea Kroeker; Swarali S. Kulkarni; Jocelyne Lew; Darryl Falzarano; Baljit Singh (Cell and Tissue Research, 2025)

Accessibility of polycyclic aromatic hydrocarbon content in fishes from the region of the 2019 oil spill on the northeast Brazil coast - Abinoan S. Rodrigues; Thayane Cristina da S. Moreira; Rafael Garrett Dolatto; Jandyson Machado Santos; Marco T. Grassi; Licarion Pinto; Ana Paula S. Paim (Marine Pollution Bulletin, 2025)

Enhancing off-season maize production through tailored nitrogen management and advanced cultivar selection techniques - Bruno Rodrigues de Oliveira; Rafael Felippe Ratke; Fábio Steiner; Abdulaziz A. Al-Askar; Jorge González Aguilera; Amr H. Hashem; Mohamed S. Sheteiwy; Renato Lustosa Sobrinho; Mohamed A. El-Tayeb; Hamada AbdElgawad; Luis Morales-Aranibar; Luciano Façanha Marques; et al. (Agricultural Systems, 2025)

Biogeographical Origins of Caatinga Squamata Fauna - Castiele Holanda Bezerra; Antonio Rafael Lima Ramos; João Fabrício Mota Rodrigues; Fernanda A. S. Cassemiro; Robson Waldemar Ávila (Journal of Biogeography, 2025)
Aim Several lines of evidence have noted that open vegetation biomes in the Neotropics are younger than moist forests, leading us to question which historical processes shaped the current species distribution patterns in these new biome formations. Here we investigate the temporal patterns of speciation and colonisation from surrounding biomes (Amazonia, Atlantic Forest and Cerrado) in the Caatinga historical assembly of squamate species, to understand the role of geomorphological events and climate change in driving its diversification. Location Neotropics. Taxon Squamata (snakes, lizards and amphisbaenians). Methods We used a phylogenetic tree and occurrence data for 459 squamate species distributed throughout four different biomes (Amazonia, Atlantic Forest, Cerrado and Caatinga) to reconstruct ancestral geographic ranges using the R package BioGeoBEARS. We used BAMM to estimate the rates of species diversification. Results Our results indicate that the current diversity patterns of squamates in the Caatinga were a result of pervasive faunal exchanges from adjacent biomes since the Paleogene, with similar numbers of dispersal events in each source area. The Neogene period was determinant in the diversification process, leading to the current assembly patterns of this group in the Caatinga. Main Conclusions The landscape transformation and climate change that increased aridity in northeastern Brazil probably shaped the diversification of dry‐adapted squamates in the Caatinga, like tropidurid lizards. However, the Pleistocene climatic fluctuations associated with the highly heterogeneous gradients of topography, geology, soils, climatic conditions, and different vegetation physiognomies could have facilitated faunal exchange with their neighbouring forested biomes, explaining the current presence of some typical forested lineages inside the Caatinga domain and help us to clarify the current distribution patterns of squamates in this region.

Impact of cigarette butts elutriates on Artemia franciscana in a climate change context - S. Couto; S. Rodrigues; R. Patrão; M. Vieira; S.C. Antunes; C. Pinheiro (Marine Pollution Bulletin, 2025)

Evaluation of Scalibor® deltamethrin collar chronic exposure in dogs - Larissa T.P. Rodrigues; Andriele F. Qualhato; Carolle V.M. Sprícigo; Kelly C.A. Arantes; Rayanne H.S. da Silva; Alexandre C.M. Barros; Monica C. Vicente; Murilo R. Souza; Luiza G.F. de Paula; Danilo Roman-Campos; Artur S. Miranda; Danieli B. Martins; et al. (Research in Veterinary Science, 2025)

Contextualizing the Upper Paleolithic of the Armenian Highlands: New data from Solak-1, central Armenia - Tanner Z. Kovach; Artur Petrosyan; Keith N. Wilkinson; Yannick Raczynski-Henk; Kathleen Rodrigues; Ellery Frahm; Emily Beverly; Jayson P. Gill; Jennifer E. Sherriff; Boris Gasparyan; Hayk G. Avetisyan; Artak V. Gnuni; et al. (Journal of Human Evolution, 2025)

An engineered, biocide-grafted TiO2-based nanohybrid material with enhanced photocatalytic and antimicrobial activity - Olga Ferreira; Mafalda Gil; Ana Carapeto; Andreia Barreto; Manuela Pereira; Mário S. Rodrigues; Lucas Habib; Luciana C. Gomes; Rita Teixeira-Santos; Filipe J.M. Mergulhão; Elisabete R. Silva (Journal of Cleaner Production, 2025)

Direct and transgenerational effects of simvastatin on the metabolism of the amphipod Gammarus locusta - João A. Rodrigues; Raquel S. Chaves; Miguel M. Santos; Teresa Neuparth; Ana M. Gil (Aquatic Toxicology, 2025)

An automated technique and decision support system for lightning early warning - M. A. Alves; B. A. S. Oliveira; D. B. S. Ferreira; A. P. P. Santos; W. F. S. Maia; W. S. Soares; F. P. Silvestrow; L. F. M. Rodrigues; E. L. Daher; O. Pinto (International Journal of Environmental Science and Technology, 2025)

Impact of Drilling Fluids on Borehole Hydraulic Conductivity in Geotechnical Investigations - F. Schnaid; B. A. Rodrigues; D. E. Lourenço; G. M. A. do Patrocínio; S. Maghous; J. L. dos Santos; M. L. P. Alves; R. Fonseca; V. B. de Araújo (Geotechnical and Geological Engineering, 2025)

Ceftazidime-avibactam tolerance and persistence among difficult-to-treat KPC-producing Klebsiella pneumoniae clinical isolates from bloodstream infections - N. Abichabki; G. G. Gaspar; L. R. Bortolato; D. A. F. S. Lima; L. N. Silva; R. H. C. Pocente; J. C. Ferreira; T. C. Ogasawara; D. Pereira; R. R. Guerra; C. Wilhelm; P. Barth; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

HiDaFernPT : Historical data of spore availability for 121 fern and lycopod taxa in Portugal (1926–2013) - Sérgio Timóteo; Ruben Heleno; Filipe Covelo; Joaquim Santos; Pedro Lopes; António C. Gouveia; Arménio Matos; Agostinho Salgado; M. Teresa Girão da Cruz; João Farminhão; Marta Horta; Guilherme Barreto; et al. (Ecology, 2025)
Species phenology is being altered by ongoing climate changes with yet underappreciated consequences for ecological processes and ecosystem stability. Contrary to what happens with some key life events of flowering plants, comparatively little information exists about fern and lycophyte phenology and how it is affected by the current climatic changes. In part, this stems from the lack of long‐term datasets. Here we provide information on the collection day and site of the spores of 121 native and introduced fern (Polypodiopsida) and lycopod (Lycopodiopsida) taxa for the Index Seminum of the Botanic Garden of the University of Coimbra. Spores were collected from spontaneous and cultivated individuals across Portugal between 1926 and 2013. The database includes 3383 curated records with information on the species, or infraspecific taxa (including authority), and are fully georeferenced and provided with a confidence interval for the collection site. Taxonomy was first curated manually by in‐house botanists and then harmonized according to the Global Biodiversity Information Facility (GBIF) backbone taxonomy. The data are released under a Creative Commons Attribution Non Commercial (CC‐BY‐NC 4.0) license.

Landscape influences bat suppression of pine processionary moth: Implications for pest management - A.M. Augusto; S. Pereira; S. Rodrigues; F. Marques; O. Aizpurua; A. Alberdi; G. Jones; O. Razgour; T.A. Marques; D. Russo; H. Rebelo (Journal of Environmental Management, 2025)

Pre-exposure of Lactobacillus acidophilus to stress conditions impacts the metabolites and bioaccessibility of calcium and carotenoids in fermented dairy products - Juliana S. Graça; Joyce G.S. Silva; Laísa G. Dias; Ana Augusta Odorissi Xavier; Elenilson G. Alves-Filho; Tatiana C. Pimentel; Edy S. Brito; Sueli Rodrigues; Juliana A.L. Pallone; Lilian R.B. Mariutti; Adriana Z. Mercadante; Neura Bragagnolo; et al. (Food Research International, 2025)

Extraction of cell wall pectins and hemicellulose from agro-industrial wastes: A sustainable alternative source - Cristine S.V. de Menezes; Alexandre C.C. Sousa; Lorena M.A. Silva; Tigressa H.S. Rodrigues; Edy S. de Brito; Nágila M.P.S. Ricardo (Carbohydrate Polymers, 2025)

Schwann cells exposed to articaine display distinct toxic pathways compared to lidocaine - Gustavo H. Rodrigues da Silva; Luís F. Mendes; Gabriela Geronimo; Ludmilla D. de Moura; Juliana S. Ruas; Roger F. Castilho; Helon G. Cordeiro; Carmen V. Ferreira; Eneida de Paula; Iola F. Duarte (Chemico-Biological Interactions, 2025)

Thriving in salty environments: Aspergillus niger’s halotolerance and BTEX biodegradation potential - Kelly Rodrigues; Ricardo Salgado; Dina Galhanas; Victoria Maura S. Bermudez; Glória Maria Marinho Silva; Ana Maria Álvares Tavares da Mata; Luciana Pereira (World Journal of Microbiology and Biotechnology, 2025)

Current constraints to reconcile tropical forest restoration and bioeconomy - Pedro Medrado Krainovic; Diego Oliveira Brandão; Angélica Faria Resende; Stella Z. Schons; Leonardo Munhoz; Jean Paul Metzger; Nathália C. Nascimento; Ricardo Ribeiro Rodrigues; Pedro H. S. Brancalion; Joannès Guillemot; Sergio de-Miguel (Sustainability Science, 2025)
Large-scale forest restoration is vital for delivering a broad array of ecosystem services benefits to society. However, it is often perceived as an economically noncompetitive land use choice. Integrating economic opportunities into restoration aligns socioeconomic and environmental goals, reducing conflicts between forest production and conservation-oriented management decisions. Supply chains focusing on high-value goods can enhance the reach of forest restoration efforts and unite ecological and economic benefits in a multifunctional manner. The bioeconomy has emerged as a potential but critical driver for attracting investments in restoration. We outline the challenges and solutions to reconcile forest restoration and bioeconomy, specifically about (i) native timber production, (ii) non-timber forest products, (iii) biotechnological products, and (iv) intangible ecosystem services. This requires collaborative and multidisciplinary efforts to improve investment in large-scale projects. The intricacies of these issues intersect with research development, market dynamics, legal frameworks, and regulatory paradigms, underscoring the necessity for nuanced and tailored public policy interventions. These integrated approaches should enable tropical countries to lead the global forest-based economy and usher in a new era of forest restoration. Graphical abstract

Airborne DNA: State of the art – Established methods and missing pieces in the molecular genetic detection of airborne microorganisms, viruses and plant particles - C.-E. Pogner; C. Antunes; G.P. Apangu; N. Bruffaerts; S. Celenk; A. Cristofori; N. González Roldán; A. Grinn-Gofroń; B. Lara; M. Lika; D. Magyar; M. Martinez-Bracero; et al. (Science of The Total Environment, 2024)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Effects of different cold plasma treatments on chemical composition, phenolics bioaccessibility and microbiota of edible red mini-roses - Janne Santos de Morais; Lucélia Cabral; Thatyane Vidal Fonteles; Francyeli Araújo Silva; Anderson S. Sant'Ana; Marcos dos Santos Lima; Sueli Rodrigues; Fabiano André Narciso Fernandes; Marciane Magnani (Food Chemistry, 2024)

A multicommuted system using bacterial cellulose for urease immobilization and copper (II)-MOF colorimetric sensor for urea spectrophotometric determination in milk - Julyana C. Rodrigues; Caio S. Bezerra; Lidiane M.A. Lima; Danielle D. Neves; Ana Paula S. Paim; Wagner E. Silva; André F. Lavorante (Food Chemistry, 2024)

Microbiota diversity of three Brazilian native fishes during ice and frozen storage - Rafaela C. Baptista; Ilario Ferrocino; Matheus Pavani; Tatiane M. Guerreiro; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Rodrigo R. Catharino; Elenilson G. Alves Filho; Sueli Rodrigues; Edy S. de Brito; Magdevis Y.R. Caturla; et al. (Food Microbiology, 2024)

RecQ helicase expression in patients with telomeropathies - João Paulo L. Silva; Flávia S. Donaires; Fernanda Gutierrez-Rodrigues; Davi J. Martins; Vinicius S. Carvalho; Barbara A. Santana; Renato L. G. Cunha; Sachiko Kajigaya; Carlos F. M. Menck; Neal S. Young; Eigil Kjeldsen; Rodrigo T. Calado (Molecular Biology Reports, 2024)

Gender Differences on the Awareness of Human Papillomavirus Infection and Vaccination - Vivian Heimbecker; Santina C. Bordini; Ana Carolina Rodrigues; Nina M. de Alencar; Nicholas S. Blanco; Fernanda Fitz; Gabriela B. Moura; Marian Dumitru; Adriana F. Mercadante; Larissa M. Alvarenga; Cristina L. B. Monteiro; Camila Marconi (Journal of Cancer Education, 2024)

Corrigendum to “Plastic-degrading microbial communities reveal novel microorganisms, pathways, and biocatalysts for polymer degradation and bioplastic production” [Sci. Total Environ. 949 (2024) 174876] - Ellen Karen Barreto Roman; Murilo Antonio Ramos; Geizecler Tomazetto; Bruno Botega Foltran; Matheus Henrique Galvão; Iara Ciancaglini; Robson Tramontina; Felipe de Almeida Rodrigues; Larissa Soares da Silva; Ana Luiza Hernandes Sandano; Diógenes G. da S. Fernandes; Dnane Vieira Almeida; et al. (Science of The Total Environment, 2024)

Plastic-degrading microbial communities reveal novel microorganisms, pathways, and biocatalysts for polymer degradation and bioplastic production - Ellen Karen Barreto Roman; Murilo Antonio Ramos; Geizecler Tomazetto; Bruno Botega Foltran; Matheus Henrique Galvão; Iara Ciancaglini; Robson Tramontina; Felipe de Almeida Rodrigues; Larissa Soares da Silva; Ana Luiza Hernandes Sandano; Diógenes G. da S. Fernandes; Dnane Vieira Almeida; et al. (Science of The Total Environment, 2024)

Landfill-gas-to-biomethane via a new carbon capture and utilization technology: One-pot sodium chloride batch mineralization - Igor Nunes Rodrigues; José Luiz de Medeiros; Israel Bernardo S. Poblete; Alex Miranda Constantino; Ofélia de Queiroz F. Araújo (Journal of Cleaner Production, 2024)

Has unsustainable groundwater use induced low flow regimes in the Urucuia Aquifer System? An urgent call for integrated water management - André F. Rodrigues; Bruno M. Brentan; Marta V. Ottoni; Jhones S. Amorim; Maria A.A. Mourão; Nilton Curi; Junior C. Avanzi; Carlos R. de Mello (Journal of Environmental Management, 2024)

Comprehensive dynamics of bacterial and fungal diversity throughout concentrated chicken broth processing: Integrating culture-dependent and independent techniques - José T.D. Rodrigues; Larissa P. Margalho; Arthur K.R. Pia; Héctor Sierra; Louise Tavares; Míriam G. Marquezini; Melline Fontes Noronha; Lucélia Cabral; Wilson José Fernandes Lemos Junior; Anderson S. Sant'Ana (International Journal of Food Microbiology, 2024)

Characterization and kinetics of whey protein isolate amyloid fibril aggregates under moderate electric fields - Rita T. Leal; Ricardo S. Pereira; Rui M. Rodrigues; Ricardo N. Pereira (Food Research International, 2024)

Plastic ingestion by odontocetes from the Western South Atlantic: A particular concern to a threatened species - Marina Zimmer-Correa; Maíra Carneiro Proietti; Juliana Couto Di Tullio; Lucas dos S. Rodrigues; Eliezer Quadro Oreste; Felipe Kessler; Manuela Bassoi; Silvina Botta (Environmental Pollution, 2024)

Juvenile-related tolerance to papaya sticky disease (PSD): proteomic, ultrastructural, and physiological events - Silas P. Rodrigues; Eduardo de A. Soares; Tathiana F. Sá Antunes; Marlonni Maurastoni; Leidy J. Madroñero; Sabrina G. Broetto; Lucas E. C. Nunes; Brunno R. F. Verçoza; David S. Buss; Diolina M. Silva; Juliany C. F. Rodrigues; José A. Ventura; et al. (Plant Cell Reports, 2024)

Patterns and Drivers of Taxonomic and Functional Change in Large Oceanic Island Bird Assemblages - Filipa C. Soares; Ricardo F. de Lima; Ana S. L. Rodrigues; Pedro Cardoso; Thomas J. Matthews; Jorge M. Palmeirim (Global Ecology and Biogeography, 2024)
Aim We map global patterns of taxonomic and functional change between past (pre‐human impacts) and present (after anthropogenic extinctions and introductions) in large oceanic island bird assemblages and investigate if these patterns can be explained by island characteristics and anthropogenic factors. Location Sixty‐four oceanic islands (>100 km 2 ). Time Period Late Holocene. Major Taxa Studied Terrestrial and freshwater bird species. Methods We compiled information on extinct, extant native and introduced bird species for all islands and used a probabilistic hypervolume approach to build a multi‐dimensional trait space and calculate several functional diversity metrics before and after extinctions and introductions. We identified which islands are global hotspots of human‐induced transformation by mapping multiple facets of biotic change and investigated intrinsic island characteristics and anthropogenic factors as drivers for these observed patterns. Results The Hawaiian and Mascarene islands stand out as hotspots of taxonomic and functional change, but all islands changed taxonomically and functionally, mostly gaining species but losing functional richness. Taxonomic and functional changes vary across islands but are often consistent within the same archipelago. Island isolation and surface can explain some of the observed variations, but anthropogenic factors, namely human occupation, also shaped both taxonomic and functional changes. Islands with higher human pressure, as well as larger islands with high elevation ranges, tended to have greater losses in functional richness. Main Conclusions Most biodiversity change assessments are still largely based exclusively on taxonomic diversity, which is particularly worrying in the case of oceanic islands given that the magnitude of functional diversity change is often considerably larger. We call for comprehensive assessments of changes in both taxonomic and functional diversity across oceanic islands in order to better understand the drivers of these changes and, in turn, predict future trends.

Multi‐Taxa Responses to Climate Change in the Amazon Forest - Carlos A. S. Rodrigues‐Filho; Flávia R. C. Costa; Juliana Schietti; Anselmo Nogueira; Rafael Pereira Leitão; Juliana Menger; Gabriel Borba; Caian Souza Gerolamo; Stefano S. Avilla; Thaise Emilio; Carolina Volkmer de Castilho; Douglas Aviz Bastos; et al. (Global Change Biology, 2024)
Tropical biodiversity is undergoing unprecedented changes due to the hydrological cycle intensification, characterized by more intense droughts and wet seasons. This raises concerns about the resilience of animal and plant communities to such extremes and the existence of potential refugia—areas theorized to safeguard biological communities from adverse climate impacts. Over 20 years of monitoring in Central Amazonia, we investigated the short‐term and long‐term effects of hydrological cycle intensification on bird, fish, ant, and palm communities. We explored whether the ‘insurance effect’ of climate trends (droughts buffered by preceded wet seasons) or ‘environmental refugia’ (droughts or floods buffered by topographic features) could lessen the impact of climate events on community composition, richness, evenness, and species rank. Pronounced abundance changes were observed among animal species, whereas palm species showed relative temporal stability. Birds and fish were more affected by the immediate and long‐term severity of droughts and wet periods, while ants responded primarily to short‐term drought impacts. Conversely, palm communities exhibited delayed responses to climate extremes, primarily in long‐term comparisons. As expected, the proposed ‘insurance effect’ mitigates the long‐term impacts of extreme climate events on animal and plant community trends. However, less extreme hydrological conditions linked to topographic features did not provide effective ‘environmental refugia’ for animals or plants during adverse climate conditions. These outcomes underscore the complex and varied biological responses to ongoing climate change, challenging the prevailing assumptions about the efficacy of environmental refugia and highlighting the nuanced resilience of biodiversity in Central Amazonia.

Hydrocarbon composition of oils spilt on the Brazilian coast in 2019 and 2022 - Antônia M. Corrêa; Felipe F. Campos; Marcus F. Tenório; Alice M.S. Rodrigues; Carlos D. Pérez; Fabiano Thompson; Andressa S. Batista; Pedro V. Gatts; Carlos E. de Rezende; Kátia Z. Leal; Marcelo C. Bernardes (Marine Pollution Bulletin, 2024)

The ADnet Bayesian belief network for alder decline: Integrating empirical data and expert knowledge - Inês Gomes Marques; Cristina Vieites-Blanco; Patricia M. Rodríguez-González; Pedro Segurado; Marlene Marques; Maria J. Barrento; Maria R. Fernandes; Arthur Cupertino; Helena Almeida; Idoia Biurrun; Tamara Corcobado; Filipe Costa e Silva; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Pennsylvanian epicontinental sea dynamics in Western Gondwana: Stratigraphic, petrographic, and C, O, and Sr isotopic insights from the Itaituba Formation, Amazonas Basin - Maria D. Traslaviña-Bueno; Juliana C. Marques; Afonso C. Nogueira; Pedro A. Silva; Juan S. Gomez-Neita; Amanda G. Rodrigues; André A. Martins; Paulo A. Souza; Ana K. Scomazzon; Marcia E. Longhim (Journal of South American Earth Sciences, 2024)

First climatology of F-region UHF echoes observed by the AMISR-14 system at the Jicamarca radio observatory and comparison with the climatology of VHF echoes observed by the collocated JULIA radar - Alexander A. Massoud; Fabiano S. Rodrigues; Jonas Sousasantos; Marco A. Milla; Danny E. Scipion; Joab M. Apaza; Karim M. Kuyeng; Carlos Padin (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

The role of culture in the representation of probiotic foods - Michele Christine Machado-Oliveira; Heber Rodrigues; Antonio Bisconsin-Junior; Gustavo H.T.A. Camillo; Héctor Sierra; Oluwadara Alegbeleye; Carlos Gomez-Corona; Dusanka Micetic-Turk; Luz Maria Paucar-Menacho; Alexandra A.I.A. Chincha; Andrea Gomez-Zavaglia; Mara Virginia Galmarini; et al. (Food Research International, 2024)

Analysis of environmental variables and deforestation in the amazon using logistical regression models - Helder J. F. da Silva; Weber A. Gonçalves; Bergson G. Bezerra; Cláudio M. Santos e Silva; Cristiano P. de Oliveira; Jório B. Cabral Júnior; Daniele T. Rodrigues; Fabrício D. S. Silva (Environmental Monitoring and Assessment, 2024)

Sonification of electronic dynamical systems: Spectral characteristics and sound evaluation using EEG features - G. Acosta Martínez; E. Guevara; E. S. Kolosovas-Machuca; P. G. Rodrigues; D. C. Soriano; E. Tristán Hernández; L. J. Ontañón-García (Cognitive Neurodynamics, 2024)

Setting up a CFD model to evaluate the impact of green infrastructures on local air quality - V. Rodrigues; B. Augusto; K. Oliveira; A. Ascenso; S. Rafael; D. Nascimento; A. I. Miranda (Air Quality, Atmosphere & Health, 2024)
Green infrastructures have been pointed out as innovative solutions to deal with current and future challenges related to air pollution and climate change. Although the potential of green infrastructures, such as green walls and green roofs, to mitigate air pollution has been documented, evidence at a local scale is still limited. This work aims to increase knowledge about the potentialities of green infrastructures in improving local air quality, focusing on particulate matter, nitrogen dioxide and ozone pollutants, and by using a local-scale computational fluid dynamics model. The ENVI-met model was applied to a particular hour of a summer day over a built-up environment centred on a main avenue in the city of Lisbon (Portugal). The dimensions of the computational domain are 618 m × 594 m × 143 m, and it contains 184 buildings, with the tallest building being 56 m. In addition to the baseline simulation, modelling was also done considering the application of green walls and green roofs to specific buildings located near the main avenue, together with a green corridor. The overall results show no disturbances exerted by green walls on the turbulent flow dynamics and on the air quality levels when compared to the baseline scenario (without green walls). The integrated scenario, which includes green walls, green roofs and a green corridor, will lead to potential local benefits of green infrastructures on O 3 concentrations, followed by variable impacts on NO 2 and particulate matter concentrations.

Interaction Between Climate Change Scenarios and Biological Invasion Reveals Complex Cascading Effects in Freshwater Ecosystems - Tauany Rodrigues; Pavel Kratina; Rayanne B. Setubal; Joseph L. S. Ferro; Douglas Hideki Abe; Luiza O. Costa; Clarice Casa Nova; Vinicius F. Farjalla; Aliny P. F. Pires (Global Change Biology, 2024)
Climate change often facilitates biological invasions, leading to potential interactive impacts of these global drivers on freshwater ecosystems. Although climatic mitigation efforts may reduce the magnitude of these interactive impacts, we are still missing experimental evidence for such effects under multiple climate change scenarios within a multi‐trophic framework. To address this knowledge gap, we experimentally compared the independent and interactive effects of two climate change scenarios (mitigation and business‐as‐usual) and biological invasion on the biomass of major freshwater trophic groups (phytoplankton, zooplankton, periphyton, macroinvertebrates, and a native macrophyte) and the decomposition rate of allochthonous material. Among the independent effects, we found that the business‐as‐usual climate treatment resulted in lower native macrophyte biomass and higher periphyton biomass compared to the climatic baseline and mitigation treatments. This indicates the potential of climate change to alter the relative dominance of different freshwater producers and demonstrates that climate mitigation efforts can counteract these effects. Biological invasion alone increased the biomass of chironomids, a dominant macroinvertebrate group in tropical freshwater ecosystems, demonstrating a compensatory effect on climate change. Climate change and biological invasion interactively reduced the decomposition rate of allochthonous detritus, likely mediated by the feeding preference of abundant chironomids for periphytic algae associated with the presence of non‐native macrophytes. We concluded that (i) climatic mitigation can maintain climate baseline conditions in freshwater ecosystems, and (ii) the interactive effects between future climate scenarios and biological invasion are related to complex cascading interactions among trophic groups on ecosystem processes.

P02-28 Microfluidics technology as a tool to improve maturation and drug metabolism capacity of stem cell-derived hepatocytes in vitro - J.S. Rodrigues; S. Relvas; P.G. Condelipes; B. Silva; R. Bozzo; P. Guedes de Pinho; V. Chu; F. Remião; J.P. Conde; J.P. Miranda (Toxicology Letters, 2024)

Joining forces to fight wildfires: Science and management in a protected area of Pantanal, Brazil - Patrícia S. Silva; Julia A. Rodrigues; Joana Nogueira; Livia C. Moura; Alexandre Enout; Cristina Cuiabália; Carlos C. DaCamara; Allan A. Pereira; Renata Libonati (Environmental Science & Policy, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Resistance training improves cardiac function in older women: a randomized controlled trial - Ricardo J. Rodrigues; Paolo M. Cunha; João P. Nunes; Lauro C. Vianna; Patrícia C. Brum; Danilo S. Bocalini; Andrei C. Sposito; Luis C. Miguita Junior; Max D. Oliveira; Elaine Batistella; Rodrigo R. Fernandes; Paulo S. Junior; et al. (GeroScience, 2024)

From bacteria to fish: ecotoxicological insights into sulfamethoxazole and trimethoprim - Bárbara S. Diogo; Sara Rodrigues; Oksana Golovko; Sara C. Antunes (Environmental Science and Pollution Research, 2024)
Sulfamethoxazole (SMX) and trimethoprim (TRIM) are two of the most used antibiotics in the last 50 years, to prevent and treat bacterial infections; however, the available literature about toxicity to non-target organisms is quite discrepant and incomplete. This study aims to assess the SMX and TRIM ecotoxicological effects in standard species: Aliivibrio fischeri (bioluminescence inhibition), Escherichia coli ATCC 25922 (growth inhibition), Lemna minor (growth inhibition and biochemical biomarkers), Daphnia magna (immobilization/mortality, life history traits, and biochemical biomarkers), and Danio rerio (survival, hatching, abnormalities, and biochemical biomarkers). The species tested showed different acute sensitivities to SMX ( A. fischeri < D. magna < E. coli < L. minor ) and TRIM ( L. minor < A. fischeri < D. magna < E. coli ) . Overall, TRIM reveals less toxicity than SMX, except for E. coli (Ecotoxicological approach based on Antimicrobial Susceptibility Testing – EcoAST procedure). Both antibiotics affect individually (e.g., growth and survival) and sub-individually (e.g., antioxidant defenses) L. minor , D. magna , and D. rerio . This study allowed us to generate relevant data and fill gaps in the literature regarding the effects of SMX and TRIM in aquatic organisms. The here-obtained results can be used to (i) complete and re-evaluate the Safety Data Sheet to improve the assessment of environmental safety and management of national and international entities; (ii) clarify the environmental risks of these antibiotics in aquatic ecosystems reinforcing the inclusion in the 4th Watch List of priority substances to be monitored in whole inland waters by the Water Framework Directive; and (iii) combat the development of antimicrobial resistance, as well as supporting the definition of environmental measurements in the context of European One Health Action Plan. However, it is essential to continue studying these antibiotics to better understand their toxicity at ecologically relevant concentrations and their long-term effects under different climatic change scenarios.

Assessing interpreter’s disagreements in land cover reference data collection from historical Landsat time series in Amazon - Mariane S. Reis; Lucélia S. de Barros; Manoel R. Rodrigues Neto; Dayane Rafaela V. de Moraes; Noeli Aline P. Moreira; Gabriel Mikael R. Alves; Bruno V. Adorno; Cassiano Gustavo Messias; Luciano V. Dutra; Camilo D. Rennó; Sidnei João S. Sant’Anna; Maria Isabel S. Escada (International Journal of Remote Sensing, 2024)

Continuous UV-C/H2O2 and UV-C/Chlorine applied to municipal secondary effluent and nanofiltration retentate: Removal of contaminants of emerging concern, ecotoxicity, and reuse potential - Fernando Rodrigues-Silva; Carla S. Santos; Joaquín A. Marrero; Rosa Montes; José Benito Quintana; Rosario Rodil; Olga C. Nunes; Maria Clara V.M. Starling; Camila C. Amorim; Ana I. Gomes; Vítor J.P. Vilar (Chemosphere, 2024)

Temporal evaluation of soil chemical quality using VNIR and XRF spectroscopies - Henrique Oldoni; Tiago Rodrigues Tavares; Thiago Luis Brasco; Maurício Roberto Cherubin; Hudson W. Pereira de Carvalho; Paulo S. Graziano Magalhães; Lucas Rios do Amaral (Soil and Tillage Research, 2024)

Understanding the Atlantic influence on climate and vegetation dynamics in western Iberia over the last 2000 years - Ricardo N. Santos; Teresa Rodrigues; Filipa Naughton; Enno Schefuß; Dulce Oliveira; João Moreno; Pedro M. Raposeiro; Graciela Gil-Romera; Alistair Morgan; Manel Leira; Sandra D. Gomes; S. Nemiah Ladd; et al. (Quaternary Science Reviews, 2024)

Intake, digestibility, serum metabolites, and growth performance of male feedlot lambs fed different fat sources - Henry D.R. Alba; José E. de Freitas; Laudí C. Leite; José A.G. Azevêdo; Stefanie A. Santos; Douglas dos S. Pina; Luis G.A. Cirne; Carlindo S. Rodrigues; Manuela S.L. Tosto; Silvia C. Bento; Amanda B. Grimaldi; Gleidson G.P. de Carvalho (Livestock Science, 2024)

One size does not fit all: Methodological considerations and recommended solutions for intramuscular temperature assessment - Patrick Rodrigues; Lucas B.R. Orssatto; Anne Hecksteden; Gabriel S. Trajano; Geoffrey M. Minett (Journal of Thermal Biology, 2024)

Insights on the regional thermal evolution from semianthracite petrology of the Fengfeng coalfield, China - Na Wang; Joan S. Esterle; Sandra Rodrigues; James C. Hower; Shifeng Dai (International Journal of Coal Geology, 2024)

Depth, hard coral, and turf cover as predictors of micro-scale spatial distribution of fishes in a subtropical rocky reef - Thiago E. Rodrigues; Vinícius J. Giglio; Fernando Z. Gibran; Fernanda A. Rolim; Leonardo M. Neves; Guilherme Henrique Pereira-Filho; Gustavo Shintate; Gabriel R. S. Souza; Domingos Garrone-Neto; Fabio S. Motta (Environmental Biology of Fishes, 2024)

Organ-specific proteomes of Selaginella convoluta provide insights into its desiccation tolerance mechanisms - Fernanda Priscila Santos Reginaldo; Luiz Fernando Rodrigues de Souza; Daisy Sotero Chacon; Marlon Dias Mariano Santos; Taffarel Melo Torres; Ivanice Bezerra da Silva; Alan de Araújo Roque; Carlos André O. Ricart; Mariana S. Castro; Paulo Costa Carvalho; Wagner Fontes; Marcelo Valle de Sousa; et al. (Plant Biosystems, 2024)

Assessing nine devices to reduce bycatch in the pink shrimp Penaeus paulensis fisheries: Lessons from field experiments with fyke nets - Samanta Silveira; Dérien L.V. Duarte; Lucas dos S. Rodrigues; Luiz Felipe C. Dumont (Regional Studies in Marine Science, 2024)

The natural anthraquinone dye emodin: Eco/genotoxicological characterization for aquatic organisms - Natália Oliveira de Farias; Amanda Rocha Rodrigues; Marina Tenório Botelho; Gabriel Rampazzo Magalhães; Riikka Räisänen; Harold S. Freeman; Gisela de Aragão Umbuzeiro (Food and Chemical Toxicology, 2024)

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Evidence of plastics contamination and sewage-derived residues in a Brazilian Hope Spot for conservation of marine biodiversity - Cagarras Islands and surrounding waters - Raquel A.F. Neves; Nathália Rodrigues; Guilherme de Luca; Maria Alene A. Oliveira; Thuany F. Carvalho; Nicole S. Santos; Maria Eduarda S. Adelino; Luiza Belli Caldas; Agatha Miralha; Clarissa Naveira; Antonio J.S. Rodrigues; Igor C. Miyahira; et al. (Marine Pollution Bulletin, 2024)

Structure and morphology of chars and activated carbons obtained from thermal treatment of coal and biomass origin materials, including their wastes: Results from the ICCP Microscopy of Carbon Materials Working Group - G. Predeanu; M. Wojtaszek-Kalaitzidi; I. Suárez Ruiz; M.N Bălănescu; A. Gómez Borrego; M.D. Ghiran; P.C. Hackley; S. Kalaitzidis; J. Kus; M. Mastalerz; M. Misz-Kennan; S. Pusz; et al. (International Journal of Coal Geology, 2024)

Diminishing benefits of thermal mass in Iranian climate: Present and future scenarios - Eugénio Rodrigues; Nazanin Azimi Fereidani; Marco S. Fernandes; Adélio R. Gaspar (Building and Environment, 2024)

Ambush strategy enhances organisms’ performance in rock–paper–scissors games - R. Barbalho; S. Rodrigues; M. Tenorio; J. Menezes (BioSystems, 2024)

Seedless fruit in Annona squamosa L. is monogenic and conferred by INO locus deletion in multiple accessions - Bruno Rafael Alves Rodrigues; Charles S. Gasser; Samy Pimenta; Marlon Cristian Toledo Pereira; Silvia Nietsche (Plant Reproduction, 2024)
Key message Inheritance of the presence/absence of seeds in Annona squamosa is mediated by a single fully recessive gene and is caused by a deletion of the INNER NO OUTER ( INO ) locus. Abstract For some fruits, seedless varieties are desirable for consumption and processing. In the sugar apple tree ( Annona squamosa L.), the seedless trait in the Thai seedless (Ts) and Brazilian seedless (Bs) accessions was associated with defective ovules and an apparent deletion of the INNER NO OUTER ( INO ) ovule development gene locus. Segregation analysis of F 2 and backcross descendants of crosses of Bs to fertile wild-type varieties in this species with a multi-year generation time showed that seedlessness was recessive and controlled by a single locus. Comparison of whole genome sequence of a wild-type plant and a third accession, Hawaiian seedless (Hs), identified a 16 kilobase deletion including INO in this line. Ts and Bs lines were shown to have an identical deletion, indicating a common origin from a single deletion event. Analysis of microsatellite markers could not preclude the possibility that all three seedless accessions are vegetatively propagated clones. The sequence of the deletion site enabled a codominant assay for the wild-type and mutant genes allowing observation of complete cosegregation of the seedless/defective ovule phenotype with the INO deletion, showing maximal separation of less than 3.5 cM. The observed deletion is the only significant difference between the wild-type and Hs line over 587 kilobases, likely encompassing much more than 3.5 cM, showing that the deletion is the cause of seedless trait. The codominant markers and obtained progenies will be useful for introgression of the seedless trait into elite sugar apple lines and into other Annonas through interspecific crossings.

A densely sampled molecular phylogeny of Tachigali (Leguminosae), an evolutionarily successful lineage of neotropical ant-housing canopy trees - Isau Huamantupa-Chuquimaco; Vitor Hugo Maia; Haroldo Cavalcante de Lima; Maristerra Rodrigues Lemes; Cristiane Snak; Bernarda Gregório; Sérgio Ricardo S. Cardoso; Luciano Paganucci de Queiroz; Charles E. Zartman; Gwilym P. Lewis; Euan K. James; Kyle G. Dexter; et al. (Brazilian Journal of Botany, 2024)

The cost of genetic diagnosis of suspected hereditary pediatric cataracts with whole-exome sequencing from a middle-income country perspective: a mixed costing analysis - Luiza M. Neves; Márcia Pinto; Olivia A. Zin; Daniela P. Cunha; Bruna N. S. Agonigi; Fabiana L. Motta; Leonardo H. F. Gomes; Dafne D. G. Horovitz; Daltro C. Almeida; Jocieli Malacarne; Leticia Guida; Andressa Braga; et al. (Journal of Community Genetics, 2024)
Up to 25% of pediatric cataract cases are inherited. There is sparse information in the literature regarding the cost of whole-exome sequencing (WES) for suspected hereditary pediatric cataracts. Molecular diagnosis of suspected hereditary pediatric cataracts is important for comprehensive genetic counseling. We performed a partial economic evaluation with a mixed costing analysis, using reimbursement data and microcosting approach with a bottom-up technique to estimate the cost of using WES for genetic diagnosis of suspected hereditary pediatric cataracts from the perspective of the Brazilian governmental health care system. One hundred and ten participants from twenty-nine families in Rio de Janeiro (RJ) were included. Costs of consumables, staff and equipment were calculated. Two scenarios were created: (1) The reference scenario included patients from RJ with suspected hereditary pediatric cataracts plus two family members. (2) The alternative scenario considered other genetic diseases, resulting in 5,280 exams per month. Sensitivity analysis was also performed. In the reference scenario, the total cost per exam was 700.09 United States dollars (USD), and in the alternative scenario, the total cost was 559.23 USD. The cost of WES alone was 527.85 USD in the reference scenario and 386.98 USD in the alternative scenario. Sensitivity analysis revealed that the largest costs were associated with consumables in both scenarios. Economic evaluations can help inform policy decisions, especially in middle-income countries such as Brazil.

Enjoy the darkness: Forsake partially nocturnal sets provides a good opportunity to improve profits and sustainability in the southern Brazil longline fishery - Lucas dos S. Rodrigues; Paul Gerhard Kinas; Vinni S. Thykjaer; Luis Gustavo Cardoso (Marine Policy, 2024)

A framework for enabling conditions for wastewater reuse - Paulo M. Rodrigues; Francisco S. Pinto; Rui C. Marques (Sustainable Production and Consumption, 2024)

Using dispersion models at microscale to assess long-term air pollution in urban hot spots: A FAIRMODE joint intercomparison exercise for a case study in Antwerp - F. Martín; S. Janssen; V. Rodrigues; J. Sousa; J.L. Santiago; E. Rivas; J. Stocker; R. Jackson; F. Russo; M.G. Villani; G. Tinarelli; D. Barbero; et al. (Science of The Total Environment, 2024)

Shifts in plant functional groups along an aridity gradient in a tropical dry forest - Ana Cláudia Pereira de Oliveira; Alice Nunes; Maria Alexandra Oliveira; Rafael S. Oliveira; Renato Garcia Rodrigues; Cristina Branquinho (Science of The Total Environment, 2024)

Comparative virulence of Colletotrichum chrysophilum and Colletotrichum nymphaeae on apple leaves - Antonio J. Andrello; Aline C. Velho; Vanessa F. Soares; Ruan S. de Godoy; Mateus B. de Freitas; Rosa M. Valdebenito-Sanhueza; Franceli Rodrigues Kulcheski; Marciel J. Stadnik (Physiological and Molecular Plant Pathology, 2024)

Biodegradable PBAT/PLA blend films incorporated with turmeric and cinnamomum powder: A potential alternative for active food packaging - Layara L.R.L. de Castro; Lauriene G.L. Silva; Iago R. Abreu; Cristiano J.F. Braz; Samara C.S. Rodrigues; Regilda S. dos R. Moreira-Araújo; Rudy Folkersma; Laura H. de Carvalho; Renata Barbosa; Tatianny S. Alves (Food Chemistry, 2024)

Evaluation of different ratios of neutral detergent-soluble carbohydrate fractions on performance, ingestive behavior, and nitrogen balance in dairy goats - Marco A. D. Bomfim; MarceloT. Rodrigues; Tadeu S. Oliveira (Tropical Animal Health and Production, 2024)

Feeding behaviour of feedlot lambs offered different amounts of concentrate with or without protected fat - Cláudia L.S. Lima; Douglas dos S. Pina; Gleidson G.P. de Carvalho; Henry D.R. Alba; Maria L.G.M. L. de Araújo, Susiane de C. Matos; Stefanie A. Santos; Maria L.O. Chaves; Carlindo S. Rodrigues; Manuela S.L. Tosto (Applied Animal Behaviour Science, 2024)

Landscape Ecology Meets Disease Ecology in the Tropical America: Patterns, Trends, and Future Directions - Matheus C. S. Mancini; Julia Rodrigues Barreto; Raquel L. Carvalho; Renata L. Muylaert; Ricardo Corasa Arrais; Paula R. Prist (Current Landscape Ecology Reports, 2024)

How do microplastics alter molluscicidal activity? Effects of weathered microplastics and niclosamide in developing freshwater snails - Cândido C. Rodrigues; Cyntia A.Y. Harayashiki; Eufrásia S. Pereira; Gabriel L.S. Rodrigues; Bruno J. Neves; Thiago L. Rocha (Science of The Total Environment, 2024)

Chilled Pacu (Piaractus mesopotamicus) fillets: Modeling Pseudomonas spp. and psychrotrophic bacteria growth and monitoring spoilage indicators by 1H NMR and GC–MS during storage - Rafaela C. Baptista; Rodrigo B.A. Oliveira; Antonio A. Câmara; Émilie Lang; Juliana L.P. dos Santos; Matheus Pavani; Tatiane M. Guerreiro; Rodrigo R. Catharino; Elenilson G.A. Filho; Sueli Rodrigues; Edy S. de Brito; Verônica O. Alvarenga; et al. (International Journal of Food Microbiology, 2024)

Functional and structural attributes of Brazilian tropical and subtropical forests and savannas - Cléber Rodrigo de Souza; Fernanda Coelho de Souza; Renata Dias Françoso; Vinícius Andrade Maia; José Roberto Rodrigues Pinto; Pedro Higuchi; Ana Carolina Silva; Jamir Afonso do Prado Júnior; Camila Laís Farrapo; Eddie Lenza; Henrique Mews; Helena L. Lemos Rocha; et al. (Forest Ecology and Management, 2024)

The vicariant role of Caribbean formation in driving speciation in American loliginid squids: the case of Doryteuthis pealeii (Lesueur 1821) - João Bráullio Luna Sales; Frank E. Anderson; Bianca Lima Paiva; Yasmim T. C. Cunha; Alan Érik Souza Rodrigues; Yrlene Ferreira; Luis Fernando S. Rodrigues-Filho; Paul W. Shaw; Manuel Haimovici; Unai Markaida; Jonathan S. Ready; Iracilda Sampaio (Marine Biology, 2024)

An acute bout of resistance exercise increases BDNF in hippocampus and restores the long-term memory of insulin-resistant rats - Camila Berbert-Gomes; Júlia S. Ramos; João G. Silveira-Rodrigues; Daniel M. M. Leite; Bruno P. Melo; Danusa D. Soares (Experimental Brain Research, 2024)

Assessment of the impact of conservation measures by modeling soil loss in Minas Gerais, Brazil - A. K. M. Soares; S. Crestana; R. R. M. Ferreira; V. G. S. Rodrigues (Environmental Monitoring and Assessment, 2024)

On the estimation of scintillation severity using background F-region peak densities: description and example results using GOLD observations - J. Sousasantos; F. S. Rodrigues; A. O. Moraes; R. W. Eastes; J. F. G. Monico (GPS Solutions, 2024)

Repeated water deficit events trigger adjustments in enzymatic antioxidant system in oil palm - Wagner Romulo L. Lopes Filho; Flavio Henrique S. Rodrigues; Rosane Patrícia F. Chaves; Roberto L. Cunha; Lucas C. Costa; Hugo A. Pinheiro (Theoretical and Experimental Plant Physiology, 2024)

Occurrence of antibiotics, hormones and PFAs in surface water from a Nile tilapia aquaculture facility in a Brazilian hydroelectric reservoir - Daniel Aparecido da S. Rodrigues; Maria Clara V.M. Starling; André Luiz C. de Barros; Mônica C. Santos; Eloísa Stéphanie da Silva; Guenther Carlos C. Viana; Lara Fabian da S. Ribeiro; Matt F. Simcik; Camila C. Amorim (Chemosphere, 2024)

Performance of spray nozzles and droplet size on glufosinate deposition and weed biological efficacy - Evandro P. Prado; Júlio C. Guerreiro; Pedro J. Ferreira-Filho; Vagner do Nascimento; Samuel Ferrari; Fernando S. Galindo; Marina Funichello; Carlos G. Raetano; Paulo H. Pagliari; Rodolfo G. Chechetto; Arthur D. Rodrigues Neto (Crop Protection, 2024)

The impact of climate change on an office building in Portugal: Measures for a higher energy performance - Marco S. Fernandes; Beatriz Coutinho; Eugénio Rodrigues (Journal of Cleaner Production, 2024)

Histological evidence of hypothyroidism in mice chronically exposed to conventional farming - Nádia Coelho; Ricardo Camarinho; Patrícia Garcia; Armindo S. Rodrigues (Environmental Toxicology and Pharmacology, 2024)

Pyrogenic carbon stocks are controlled by hydro-edaphic conditions in different forest types of the Northern Brazilian Amazon - Libério Junio da Silva; Lidiany Camila da Silva Oliveira; Gabriel Nuto Nóbrega; Dener Márcio S. Oliveira; Cleber Cunha Figueredo; Gabriel Rocha; Gabriel Souza Martins; Renato de Aragão R. Rodrigues; Reinaldo Imbrózio Barbosa; Renato Campello Cordeiro (CATENA, 2024)

Negative effects of ghost nets on Mediterranean biodiversity - Júlia Fernandes Perroca; Tommaso Giarrizzo; Ernesto Azzurro; Jorge Luiz Rodrigues-Filho; Carolina V. Silva; Marlene S. Arcifa; Valter M. Azevedo-Santos (Aquatic Ecology, 2024)

Fluoxetine alters rat's milk properties causing impact on offspring's development - Gabriel R. Abreu; Julia Zaccarelli-Magalhães; Laís S. Féba; Emily Y. Penna; Julia P. Silva; Mariana V. Teixeira; Marianna Manes; Guilherme A. Vergara; Leonardo M.A. Rodrigues; André R. Fukushima; Esther L. Ricci; Helenice S. Spinosa (Toxicology and Applied Pharmacology, 2024)

Carcass traits and meat quality of lambs fed with rehydrated ground corn silage - Leandro A.S. Silva; Cláudia L.S. Lima; Douglas dos S. Pina; Henry D.R. Alba; Maria L.G.M.L. de Araújo; Luís G.A. Cirne; José A.G. Azevêdo; Carlindo S. Rodrigues; Larissa M. Borges; Maria L.O. Chaves; Gleidson G.P. de Carvalho (Small Ruminant Research, 2024)

Allometric models for non-destructive estimation of the leaflet area in acai (Euterpe oleracea Mart.) - Samara K. A. de Sousa; Rodrigo G. M. Nascimento; Flavio Henrique S. Rodrigues; Rafael G. Viana; Lucas C. da Costa; Hugo A. Pinheiro (Trees, 2024)

Effect of biomass burning emission on carbon assimilation over Brazilian Pantanal - Leone F. A. Curado; Sérgio R. de Paulo; Haline J. Araújo da Silva; Rafael S. Palácios; João B. Marques; Iramaia Jorge Cabral de Paulo; Higo José Dalmagro; Thiago Rangel Rodrigues (Theoretical and Applied Climatology, 2024)

Effects of Acacia mearnsii tannins on growth performance, footpad dermatitis, nutrient digestibility, intestinal permeability, and meat quality of broiler chickens - Guilherme L. Godoy; Beatriz N. Rodrigues; Jessica C. Agilar; Valeria Biselo; Danielle D. Brutti; Greicy S. Maysonnave; Catarina Stefanello (Animal Feed Science and Technology, 2024)

Understanding temporal variability across trophic levels and spatial scales in freshwater ecosystems - Tadeu Siqueira; Charles P. Hawkins; Julian D. Olden; Jonathan Tonkin; Lise Comte; Victor S. Saito; Thomas L. Anderson; Gedimar P. Barbosa; Núria Bonada; Claudia C. Bonecker; Miguel Cañedo‐Argüelles; Thibault Datry; et al. (Ecology, 2024)
A tenet of ecology is that temporal variability in ecological structure and processes tends to decrease with increasing spatial scales (from locales to regions) and levels of biological organization (from populations to communities). However, patterns in temporal variability across trophic levels and the mechanisms that produce them remain poorly understood. Here we analyzed the abundance time series of spatially structured communities (i.e., metacommunities) spanning basal resources to top predators from 355 freshwater sites across three continents. Specifically, we used a hierarchical partitioning method to disentangle the propagation of temporal variability in abundance across spatial scales and trophic levels. We then used structural equation modeling to determine if the strength and direction of relationships between temporal variability, synchrony, biodiversity, and environmental and spatial settings depended on trophic level and spatial scale. We found that temporal variability in abundance decreased from producers to tertiary consumers but did so mainly at the local scale. Species population synchrony within sites increased with trophic level, whereas synchrony among communities decreased. At the local scale, temporal variability in precipitation and species diversity were associated with population variability (linear partial coefficient, β = 0.23) and population synchrony (β = −0.39) similarly across trophic levels, respectively. At the regional scale, community synchrony was not related to climatic or spatial predictors, but the strength of relationships between metacommunity variability and community synchrony decreased systematically from top predators (β = 0.73) to secondary consumers (β = 0.54), to primary consumers (β = 0.30) to producers (β = 0). Our results suggest that mobile predators may often stabilize metacommunities by buffering variability that originates at the base of food webs. This finding illustrates that the trophic structure of metacommunities, which integrates variation in organismal body size and its correlates, should be considered when investigating ecological stability in natural systems. More broadly, our work advances the notion that temporal stability is an emergent property of ecosystems that may be threatened in complex ways by biodiversity loss and habitat fragmentation.

Emerging Methods for the Evaluation of Sensory Quality of Food: Technology at Service - Sandra S. Q. Rodrigues; Luís G. Dias; Alfredo Teixeira (Current Food Science and Technology Reports, 2024)
Purpose of Review Sensory evaluation holds vital significance in the food sector. Typically, humans conduct sensory analysis. Humans, being the ultimate consumers, assess food traits effectively. However, human judgment is influenced by various factors. Hence, countering subjectivity is crucial for objective evaluation while retaining hedonic insights. Recent Findings Food’s sensory assessment primarily employs humans. Various techniques differentiate, depict, or rank food. Modern sensory tools, aiming to enhance objectivity and reliability, are emerging to supplement or supplant human assessment. This advance can bolster quality, consistency, and safety by mimicking human senses such as smell, taste, and vision, mitigating risks tied to human assessors. Summary This paper provides a review about sensory analysis of food using technological methodologies. A review of different technological tools to analyze sensory characteristics of food, as well as a discussion of how those technological tools can relate to humans’ perception of food is presented.

Pest termite Cryptotermes havilandi (Sjöstedt, 1900) (Blattodea: Isoptera: Kalotermitidae) as an invasive species of natural ecosystems in northeastern Brazil - Renan Rodrigues Ferreira; Ricardo Koroiva; Flávia Maria S. Moura; Sara Rikeley Paulino Monteiro; Rozzanna Esther C. R. Figueirêdo; Matilde Vasconcelos Ernesto; Alexandre Vasconcellos (International Journal of Tropical Insect Science, 2024)

Comparative toxicity of coal and coal ash: Assessing biological impacts and potential mechanisms through in vitro and in vivo testing - Fernanda B.M. Boaretto; Juliana da Silva; Amanda Scotti; Jayne S. Torres; Ana L.H. Garcia; Gabriela Z.P. Rodrigues; Günther Gehlen; Vinícios B. Rodrigues; Mariele F. Charão; Guilherme M. Soares; Johnny F. Dias; Jaqueline N. Picada (Journal of Trace Elements in Medicine and Biology, 2024)

What are the main obstacles to turning foods healthier through probiotics incorporation? a review of functionalization of foods by probiotics and bioactive metabolites - Eliene Penha Rodrigues Pereira; Juliana Silva da Graça; Beatriz Manfrinato Ferreira; Celso Fasura Balthazar; Douglas Xavier-Santos; Fabrícia França Bezerril; Marciane Magnani; Anderson S. Sant'Ana (Food Research International, 2024)

Copper isotopes as a tool to trace contamination in mangroves from an urbanized watershed - João Barreira; Daniel F. Araújo; Breno Q.A. Rodrigues; Myller S. Tonhá; Rafael de Araújo Mendes; Carlos Eduardo Souto-Oliveira; Marly Babinski; Joël Knoery; Christian J. Sanders; Jérémie Garnier; Wilson Machado (Environmental Pollution, 2024)

Experimental and Theoretical Investigation of the Effect of Cellulose Nanowhiskers on the Pb(II) Adsorption by Superabsorbent Hydrogel Nanocomposites - André R. Fajardo; Robson S. Oliboni; Carlos E. C. de Magalhães; Maria G. M. Chaves; Francisco H. A. Rodrigues (Water, Air, & Soil Pollution, 2024)

Enantioselectivity of pinene against Leishmania amazonensis - Ingrid S. Adão; Andreza R. Garcia; Kamila M. Sette; Camila M. Adade; Jefferson R. de Andrade Silva; Ana Claudia F. Amaral; Anderson S. Pinheiro; Igor A. Rodrigues (Medicinal Chemistry Research, 2024)

Solar photocatalysis using post-consumer alkaline batteries for degrading contaminants of emerging concern in surface water - Guenther Carlos C. Viana; Elisângela Maria R. Rocha; Elisandra Scapin; Arthur Cahino; Iris Rebeca D. Leite; Daniel A. Bertuol; José D. Ardisson; Daniel Aparecido S. Rodrigues; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2023)

Protocols for the seminal cryopreservation of South American catfishes – current status - Danilo P. Streit; Rômulo B. Rodrigues; Eduardo A. Sanches; Jayme A. Povh; Diógenes H. Siqueira-Silva; Thaíza R. de Freitas; Nathalia T. Santos; Jhony B. Lisboa; Thales S. França; Eduardo Nicoleti; Larise O.C. Lima; Tiantian Zhang (Cryobiology, 2023)

Effects of different subcutaneous sites on heterotopic autotransplantation of canine ovarian tissue - Fabiana AS Brandão; Danielle CC de Brito; Leda MC Pereira; Kele A Alves; Lucy VS Ñaupas; Samara S de Souza; Duanny M de S Cunha; Reginaldo P de S Filho; Benner G Alves; Ana PR Rodrigues; Dárcio IA Teixeira (Veterinary Research Communications, 2023)

A meta-analytical review of turbidity effects on fish mobility - Jean N. Rodrigues; Jean C. G. Ortega; Danielle K. Petsch; Andre A. Padial; Dieison A. Moi; Bruno R. S. Figueiredo (Reviews in Fish Biology and Fisheries, 2023)

A limitless Brazilian scientist: Professor Travassos and his contribution to cancer biology - Elaine G. Rodrigues; Andrey S. Dobroff; Denise C. Arruda; Dayane B. Tada; Thaysa Paschoalin; Luciano Polonelli (Brazilian Journal of Microbiology, 2023)

Professor Luiz R. Travassos and the study of surface structures of fungal pathogens - Marcio L. Rodrigues; Daniela S. Alviano; Lucimar F. Kneipp; Celuta S. Alviano; Eliana Barreto-Bergter; Leonardo Nimrichter (Brazilian Journal of Microbiology, 2023)

Utilization of Rosuvastatin and Endogenous Biomarkers in Evaluating the Impact of Ritlecitinib on BCRP, OATP1B1, and OAT3 Transporter Activity - Yeamin Huh; Anna Plotka; Hua Wei; Julia Kaplan; Nancy Raha; Justin Towner; Vivek S. Purohit; Martin E. Dowty; Robert Wolk; Manoli Vourvahis; Amanda King-Ahmad; Sumathy Mathialagan; et al. (Pharmaceutical Research, 2023)
Purpose Ritlecitinib, an inhibitor of Janus kinase 3 and tyrosine kinase expressed in hepatocellular carcinoma family kinases, is in development for inflammatory diseases. This study assessed the impact of ritlecitinib on drug transporters using a probe drug and endogenous biomarkers. Methods In vitro transporter-mediated substrate uptake and inhibition by ritlecitinib and its major metabolite were evaluated. Subsequently, a clinical drug interaction study was conducted in 12 healthy adult participants to assess the effect of ritlecitinib on pharmacokinetics of rosuvastatin, a substrate of breast cancer resistance protein (BCRP), organic anion transporting polypeptide 1B1 (OATP1B1), and organic anion transporter 3 (OAT3). Plasma concentrations of coproporphyrin I (CP-I) and pyridoxic acid (PDA) were assessed as endogenous biomarkers for OATP1B1 and OAT1/3 function, respectively. Results In vitro studies suggested that ritlecitinib can potentially inhibit BCRP, OATP1B1 and OAT1/3 based on regulatory cutoffs. In the subsequent clinical study, coadministration of ritlecitinib decreased rosuvastatin plasma exposure area under the curve from time 0 to infinity (AUC inf ) by ~ 13% and maximum concentration (C max ) by ~ 27% relative to rosuvastatin administered alone. Renal clearance was comparable in the absence and presence of ritlecitinib coadministration. PK parameters of AUC inf and C max for CP-I and PDA were also similar regardless of ritlecitinib coadministration. Conclusion Ritlecitinib does not inhibit BCRP, OATP1B1, and OAT3 and is unlikely to cause a clinically relevant interaction through these transporters. Furthermore, our findings add to the body of evidence supporting the utility of CP-I and PDA as endogenous biomarkers for assessment of OATP1B1 and OAT1/3 transporter activity.

Preclinical data on morpholine (3,5-di-tertbutyl-4-hydroxyphenyl) methanone induced anxiolysis - Iara Barbosa Cabral; Caroline Vitória de Lima Moreira; Ana Carolina Cavalcante Rodrigues; Lorrane Kelle da Silva Moreira; Jhon Kennedy Alves Pereira; Christian Dias Gomides; Luciano M. Lião; Lucas S. Machado; Boniek G. Vaz; Luiz Carlos da Cunha; Jerônimo Raimundo de Oliveira Neto; Edeildo Ferreira da Silva-Júnior; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Are the ecotoxicological tools viable to evaluate the effectiveness of wastewater treatment plant effluents? - B. S. Diogo; S. Rodrigues; O. M. Lage; S. C. Antunes (International Journal of Environmental Science and Technology, 2023)
Ecotoxicological tools have proved to be sensitive and appropriate for the evaluation of the effectiveness of treatments used in wastewater treatment plants (WWTP). The objective of this study was to assess the applicability of bioassays and biomarkers to evaluate the efficiency of different treatments throughout WWTP samples[A—raw influent, B—preliminary effluent, C—final effluent, and D—receiving stream], seasonally over 1 year, through a multispecies approach: i) bacterial cell viability [ Escherichia coli , Rhodopirellulla rubra , Arthrobacter sp., and Pseudomonas putida ]; ii) microalgae Raphidocelis subcapitata and the macrophyte Lemna minor growth inhibition; and iii) microcrustacean Daphnia magna acute and feeding rate assays. Total chlorophyll, malondialdehyde, and proline levels were evaluated in L. minor , and catalase, glutathione-S-transferase activities, and thiobarbituric acid reactive substances levels were quantified in D. magna , after exposure to wastewater samples. Overall, the tested species showed different sensitivities, P. putida = Arthrobacter sp. = R. rubra < R. subcapitata < E. coli = D. magna = L. minor , to the collected samples. The results obtained in D. magna and L. minor assays demonstrated that these organisms can be used in programs for monitoring and environmental assessment of wastewater effluents. The present study demonstrates the usefulness of ecotoxicological tools, with multispecies and different endpoints, to assess the effectiveness of WWTPs. Moreover, it is important to ensure that WWTP implements a monitoring program to minimize the discharge of effluents that compromise the environment in order to guarantee the good ecological quality of the environmental ecosystems.

Prolonged drought influences the taxonomic and functional structure of fish assemblages in estuaries along the Brazilian semiarid coast - Ronaldo C. Gurgel-Lourenço; Carlos A. S. Rodrigues-Filho; Leonardo M. Pinto; Jorge I. Sánchez-Botero (Hydrobiologia, 2023)

Metallothionein expression in the central nervous system in response to chronic heavy metal exposure: possible neuroprotective mechanism - A. Navarro-Sempere; P. Martínez-Peinado; A. S. Rodrigues; P. V. Garcia; R. Camarinho; G. Grindlay; L. Gras; M. García; Y. Segovia (Environmental Geochemistry and Health, 2023)
It has been reported that volcanoes release several tonnes of mercury per year among other heavy metals through eruptions, fumaroles, or diffuse soil degassing. Since a high percentage of the world's population lives in the vicinity of an active volcano, the aim of this study is to evaluate the accumulation of these metals in the central nervous system and the presence of cellular mechanisms of heavy metal detoxification such as metallothioneins. To carry out this study, wild mice (Mus musculus) chronically exposed to an active volcanic environment were captured in Furnas village (Azores, Portugal) and compared with those trapped in a reference area (Rabo de Peixe, Azores, Portugal). On the one hand, the heavy metal load has been evaluated by analyzing brain and cerebellum using ICP-MS and a mercury analyzer and on the other hand, the presence of metallothionein 2A has been studied by immunofluorescence assays. Our results show a higher load of metals such as mercury, cadmium and lead in the central nervous system of exposed mice compared to non-exposed individuals and, in addition, a higher immunoreactivity for metallothionein 2A in different areas of the cerebrum and cerebellum indicating a possible neuroprotection process.

Sustainable treatment of municipal secondary effluent from UASB systems by solar photo-Fenton: CECs removal and toxicity control - Fernando Rodrigues-Silva; Maria Clara V.M. Starling; Daniel Aparecido S. Rodrigues; Camila C. Amorim (Journal of Environmental Chemical Engineering, 2023)

Marine Isotope Stage 4 (71–57 ka) on the Western European margin: Insights to the drainage and dynamics of the Western European Ice Sheet - Samuel Toucanne; Teresa Rodrigues; Guillemette Menot; Guillaume Soulet; Sandrine Cheron; Isabelle Billy; Frederique Eynaud; Pierre Antoine; Jaap S. Sinninghe Damste; Edouard Bard; Maria-Fernanda Sanchez Goñi (Global and Planetary Change, 2023)

Flexible thermoelectric energy harvesting system based on polymer composites - T. Rodrigues-Marinho; V. Correia; C.-R. Tubio; A. Ares-Pernas; M.-J. Abad; S. Lanceros-Méndez; P. Costa (Chemical Engineering Journal, 2023)

Anti-Candida Potential of Peptides from Immature and Ripe Fruits of Capsicum chinense Jacq - Marilucia C. Ribeiro; Rodrigo S. Gebara; Gabriel B. Taveira; André de O. Carvalho; Rosana Rodrigues; Erica O. Mello; Celso S. Nagano; Renata P. Chaves; Valdirene M. Gomes (Probiotics and Antimicrobial Proteins, 2023)

P06-04: Development of the TOXIN Knowledge Graph for assisting animal-free risk assessment of cosmetic ingredients - S. Sepehri; J. Maushagen; G. Vrijens; C. Debruyne; R. Marcelino Rodrigues; A. Sanctorum; O. De Troyer; T. Vanhaecke (Toxicology Letters, 2023)

P01-02: An updated adverse outcome pathway network on chemical-induced liver steatosis - A. Verhoeven; J. van Ertvelde; J. Boeckmans; A. Gatzios; R. Jover; B. Lindeman; G. Lopez Soop; R. Marcelino Rodrigues; A. Rapisarda; M. Stinckens; S. Sepehri; M. Vinken; et al. (Toxicology Letters, 2023)

Integrated membrane process (UF/RO/EDI) for treating a petrochemical wastewater to obtain ultrapure water for industrial reuse - Andréia B. Santos; Alexandre Giacobbo; Marco Antônio S. Rodrigues; Andréa Moura Bernardes (Process Safety and Environmental Protection, 2023)

Detection of Equus caballus Papillomavirus in Equine Aural Plaque Samples - Cristiana R. Bromberger; Julia Rodrigues Costa; Mariana Herman; Juliana Mira Hernandez; Lukas Garrido Albertino; Carlos Eduardo Fonseca Alves; Alexandre S. Borges; Jose P. Oliveira-Filho (Journal of Equine Veterinary Science, 2023)

Influence of loading rates and feeding conditions on hybrid constructed wetlands integrated with microbial fuel cells - Gustavo S. Colares; Naira Dell'Osbel; Igor Conrad; Gabriele Paranhos; Sabrina B. Vaz; Gislayne Oliveira; Letícia Mesacasa; Deison Fochi; Odorico Konrad; Lucia R. Rodrigues; Carlos A. Lutterbeck; Adriane Lawisch Rodriguez; et al. (Ecological Engineering, 2023)

Sustainable bioethanol production from first- and second-generation sugar-based feedstocks: Advanced bibliometric analysis - Cláudia Elisa César Guimarães; Francisco Simão Neto; Viviane de Castro Bizerra; Jean Gleison Andrade do Nascimento; Roberta Bussons Rodrigues Valério; Paulo Gonçalves de Sousa Junior; Ana Kátia de Sousa Braz; Rafael Leandro Fernandes Melo; Juliana de França Serpa; Rita Karolinny Chaves de Lima; Artemis Pessoa Guimarães; Maria Cristiane Martins de Souza; et al. (Bioresource Technology Reports, 2023)

Silicon, magnesium, and their interaction on wheat resistance against blast - Marcela U. P. Araujo; Lillian M. Oliveira; Leandro C. Silva; Luiz F. C. C. Pinto; Isaias S. Cacique; Fabrício A. Rodrigues (Plant and Soil, 2023)

Fitness costs associated with spinetoram resistance in Spodoptera frugiperda is driven by host plants - Rubens H. Kanno; Aline S. Guidolin; Fernando E. O. Padovez; Juliana G. Rodrigues; Celso Omoto (Journal of Pest Science, 2023)

Behavior of deteriogenic fungi in aviation fuels (fossil and biofuel) during simulated storage - Mariane Rodrigues Lobato; Juciana Clarice Cazarolli; Regiane Débora Fernandes Rios; Emmanuel Bezerra D’ Alessandro; Marcia T. S Lutterbach; Nelson Roberto Antoniosi Filho; Vânya Márcia Duarte Pasa; Donato Aranda; Pedro Rodrigo Scorza; Fátima Menezes Bento (Brazilian Journal of Microbiology, 2023)

Topical formulations containing Trichilia catigua extract as therapeutic options for a genital and an acyclovir-resistant strain of herpes recurrent infection - Elisa Vicente Ribelato; Jéssica Wouk; Gabriela Gomes Celestino; Bianca Cerqueira Dias Rodrigues; Maria Laura Goussain Darido; Mario Gabriel Lopes Barboza; Tatiana Jabor Botura; Maylla Cardoso de Oliveira; Fábio Goulart de Andrade; Audrey A. S. G. Lonni; João Carlos Palazzo de Mello; Sérgio Paulo Dejato da Rocha; et al. (Brazilian Journal of Microbiology, 2023)

Different patterns of maize hybrids responses under variable phosphorus availability - R. E. Rodrigues; A. R. Neto; L. S. Jesus; L. T. M. Guedes; L. S. Santos; M. N. Xavier; L. A. Souza (Acta Physiologiae Plantarum, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Paleoecological indicators of the highstand sea level on the Amazonian supralittoral until the last two millennia - Samuel Rodrigues Ribeiro; Roberto Célio Valadão; Makênia Oliveira Soares Gomes; Jonathas S. Bittencourt; Raquel Araújo Alves (Journal of South American Earth Sciences, 2023)

Comparative neurotoxicity of dietary methylmercury and waterborne inorganic mercury in fish: Evidence of optic tectum vulnerability through morphometric and histopathological assessments - Patrícia S. Carvalho; Diana Fonseca-Rodrigues; Mário Pacheco; Armando Almeida; Filipa Pinto-Ribeiro; Patrícia Pereira (Aquatic Toxicology, 2023)

[8] and [10]-Gingerol reduces urothelial damage in ifosfamide-induced hemorrhagic cystitis via JAK/STAT/FOXO signaling pathway via IL-10 - Francisco C. S. Ferreira; Marco Clementino; Francisco A. P. Rodrigues; Herlice N. Veras; Dainesy S. Martins; Marcus L. Queiroga; Mikael A. Lima; Dayara O. Silva; Thiago M. de Freitas; Samilly A. Ribeiro; Mario R. L. Mota; James A. da Silva; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Extending records of albinism and skin disorders in American cownose rays to southeastern Brazil - Alexandre Rodrigues; Wesley Shkola; Bianca S. Rangel (Journal of Fish Biology, 2023)
Albinism is a genetic condition expressed as a lack of integumentary and retinal melanin. Although documented across many vertebrate species, albinism and other skin disorders are rarely observed in elasmobranchs (sharks and rays). The present study describes the first confirmed case of albinism in American cownose ray ( Rhinoptera bonasus ), and three other juveniles of the species with undetermined skin disorders observed in São Paulo, southeastern Brazil. Pigmentation disorders have already been observed in American cownose rays from the North Atlantic, including two cases of leucism and a possible albinism. Based on the results, it was discussed the possible consequences of albinism for the ray survival as well as the possible causes for the undetermined skin disorders.

Heated environment offsets the cardiovascular responses to prolonged rowing exercise in competitive athletes - Igor V.P. dos S. Barreto; Gabriel D. Rodrigues; Josie de S. Oliveira; Eduardo B. Neves; Pedro Paulo da S. Soares (Journal of Thermal Biology, 2023)

Characterizing isoprene production in cyanobacteria – Insights into the effects of light, temperature, and isoprene on Synechocystis sp. PCC 6803 - João S. Rodrigues; László Kovács; Martin Lukeš; Rune Höper; Ralf Steuer; Jan Červený; Pia Lindberg; Tomáš Zavřel (Bioresource Technology, 2023)

Sex and the Estrous-Cycle Phase Influence the Expression of G Protein-Coupled Estrogen Receptor 1 (GPER) in Schizophrenia: Translational Evidence for a New Target - Francisco Eliclécio Rodrigues da Silva; Rafaela Carneiro Cordeiro; Camila N. de Carvalho Lima; Pablo Leal Cardozo; Germana Silva Vasconcelos; Aline Santos Monte; Lia Lira Olivier Sanders; Silvânia Maria Mendes Vasconcelos; David Freitas de Lucena; Breno Fiuza Cruz; Rodrigo Nicolato; Mary V. Seeman; et al. (Molecular Neurobiology, 2023)

A new species of mailed catfish of genus Rhadinoloricaria (Siluriformes: Loricariidae: Loricariinae) from Rio Negro basin, Brazil - Jefferson L. Crispim‐Rodrigues; Maxwell J. Bernt; Brandon T. Waltz; Gabriel S. C. Silva; Ricardo C. Benine; Claudio Oliveira; Raphaël Covain; Fábio F. Roxo (Journal of Fish Biology, 2023)
During a recent collection expedition to the Rio Negro, in the state of Amazonas, Brazil, eight individuals of an unknown species were collected, with a combination of characteristics that placed the species in the genus Rhadinoloricaria . Furthermore, the presence of two autapomorphic characteristics, including numerous elongated papillae on the lower lip and unbranched barbelets on the margin of lower lip, suggests that it is a new species. From morphological and phylogenetic analyses, including the sequencing of specific genes to calculate the maximum likelihood analyses, coupled with osteological computed tomography (CT) scan analyses, the authors corroborated that the specimens represent a new species of Rhadinoloricaria , described in the present study.

Assessing water conservation behaviour of India's urban households - Sudheer Bhakta S; Lewlyn LR Rodrigues; K.V. Sriram (Utilities Policy, 2023)

The antidepressant-like effect of guanosine involves the modulation of adenosine A1 and A2A receptors - Anderson Camargo; Luis E. B. Bettio; Priscila B. Rosa; Julia M. Rosa; Glorister A. Altê; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2023)

Combined Application of Antisense Oligomers to Control Transcription Factors of Candida albicans Biofilm Formation - D. Araújo; B. Gonçalves; D. Vilas Boas; M. E. Rodrigues; M. Henriques; S. Silva (Mycopathologia, 2023)

Application of essential oils as sanitizer alternatives on the postharvest washing of fresh produce - Jessica S. Pizzo; Jesui V. Visentainer; Andre L.B.R. da Silva; Camila Rodrigues (Food Chemistry, 2023)

Controlled lipid self-assembly for scalable manufacturing of next-generation immune stimulating complexes - Ivan S. Pires; Kaiyuan Ni; Mariane Bandeira Melo; Na Li; Elana Ben-Akiva; Laura Maiorino; Jonathan Dye; Kristen A. Rodrigues; DongSoo Yun; Byungji Kim; Ryan R. Hosn; Paula T. Hammond; et al. (Chemical Engineering Journal, 2023)

Colchicine reduces the activation of NLRP3 inflammasome in COVID-19 patients - N. B. Amaral; T. S. Rodrigues; M. C. Giannini; M. I. Lopes; L. P. Bonjorno; P. I. S. O. Menezes; S. M. Dib; S. L. G. Gigante; M. N. Benatti; U. C. Rezek; L. L. Emrich-Filho; B. A. Sousa; et al. (Inflammation Research, 2023)

Means, motive and opportunity for biological invasions: Genetic introgression in a fungal pathogen - Flávia Rogério; Cock Van Oosterhout; Maisa Ciampi‐Guillardi; Fernando Henrique Correr; Guilherme Kenichi Hosaka; Sandrine Cros‐Arteil; Gabriel Rodrigues Alves Margarido; Nelson S. Massola Júnior; Pierre Gladieux (Molecular Ecology, 2023)
Invasions by fungal plant pathogens pose a significant threat to the health of agricultural ecosystems. Despite limited standing genetic variation, many invasive fungal species can adapt and spread rapidly, resulting in significant losses to crop yields. Here, we report on the population genomics of Colletotrichum truncatum , a polyphagous pathogen that can infect more than 460 plant species, and an invasive pathogen of soybean in Brazil. We study the whole‐genome sequences of 18 isolates representing 10 fields from two major regions of soybean production. We show that Brazilian C . truncatum is subdivided into three phylogenetically distinct lineages that exchange genetic variation through hybridization. Introgression affects 2%–30% of the nucleotides of genomes and varies widely between the lineages. We find that introgressed regions comprise secreted protein‐encoding genes, suggesting possible co‐evolutionary targets for selection in those regions. We highlight the inherent vulnerability of genetically uniform crops in the agro‐ecological environment, particularly when faced with pathogens that can take full advantage of the opportunities offered by an increasingly globalized world. Finally, we discuss “the means, motive and opportunity” of fungal pathogens and how they can become invasive species of crops. We call for more population genomic studies because such analyses can help identify geographical areas and pathogens that pose a risk, thereby helping to inform control strategies to better protect crops in the future.

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Assessment of eutrophication from phosphorus remobilization after resuspension of coastal sediments from an urban tropical estuary - Christiane do N. Monte; Ana Paula de Castro Rodrigues; Matheus Cavalcante Silva; Luana J. S. Ferreira; Gustavo Monte; Carla Semiramis Silveira; Renato Campello Cordeiro; Wilson Machado (Environmental Science and Pollution Research, 2023)

Integrated ecosystem assessment around islands of the tropical South Mid-Atlantic Ridge - Amanda R. Rodrigues; Sergio R. Floeter; Vicente Gomes; Débora S. Ferrari; Vinicius J. Giglio; Fernanda C. Silva; Ana M. R. Liedke; Carlos E. L. Ferreira; Kerry Howell; Maria A. Gasalla (Frontiers in Marine Science, 2023)
The South Mid Atlantic Ridge comprises three main oceanic islands in the equatorial and tropical portions of the Atlantic Ocean. These islands are isolated from each other and equidistant from both the continental margins of South America and Africa, sharing common patterns but with different types of human use and pressures. Moreover, the areas beyond national jurisdiction between those islands are visited and exploited by distant fishing fleets and include large areas of shipping activity for commodities. Here, a pioneering integrated ecosystem assessment (IEA) process is constructed for the region among Saint Peter and Saint Paul’s Archipelago (Brazil), Saint Helena Island and Ascension Island (UK overseas territories). For that, we used a qualitative assessment of risks arising from anthropogenic activities, representing a novel contribution to the field. The Options for Delivering Ecosystem-Based Marine Management (ODEMM) approach was applied to trace sector–pressure–component pathways. A ‘linkage framework’ was outlined including pressures affecting each ecosystem component, and supported a process of knowledge attributions that scored the impact risks. All results were validated with regional stakeholders through workshops, including local and international management bodies, non-governmental organizations (NGOs) and scientists. The approach focused on a significant area among encompassing the open ocean, shallow and deep-sea biomes, analyzing the main sectors and pressures affecting the ecological components. Our results identified 14 sectors and 16 key pressures associated with 23 ecosystem components, totaling 780 impact chains. Fishing, shipping, wastewater, and tourism/recreation appeared as the top impacting sectors. Fishing and shipping were the most connected with ecosystem components links. Litter, species extraction, contaminants, and bycatch were the pressures that had the highest risk of impact values. Lastly, demersal and pelagic fish and pelagic and demersal elasmobranchs were the groups with the highest risk related to overall impacts, which were supported by local and regional evidence from long term monitoring programs and local studies. Our study demonstrated that these seemingly pristine islands and oceanic waters are already experiencing human impacts that should be addressed by local both conservation measures and international agreements. We also highlight the pressures that should be prioritized for better monitoring and policy, as well as those linkage components that have been less investigated.

Are biopesticides safe for the environment? Effects of pyrethrum extract on the non-target species Daphnia magna - B.S. Diogo; S.C. Antunes; S. Rodrigues (Environmental Toxicology and Pharmacology, 2023)

NMDA receptor-mediated modulation on glutamine synthetase and glial glutamate transporter GLT-1 is involved in the antidepressant-like and neuroprotective effects of guanosine - Anderson Camargo; Ana P. Dalmagro; Glorister A. Altê; Ana Lúcia B. Zeni; Carla I. Tasca; Ana Lúcia S. Rodrigues (Chemico-Biological Interactions, 2023)

Future weather generator for building performance research: An open-source morphing tool and an application - Eugénio Rodrigues; Marco S. Fernandes; David Carvalho (Building and Environment, 2023)

Disinformation permeates Castro's reply to Rajão et al. (2022) - Raoni Rajão; Antonio Donato Nobre; Evandro L.T.P. Cunha; Tiago Ribeiro Duarte; Camilla Marcolino; Britaldo S. Soares-Filho; Gerd Sparovek; Ricardo R. Rodrigues; Carlos Valera; Mercedes Bustamante; Carlos Nobre; Letícia Santos de Lima (Biological Conservation, 2023)

Unveiling the membrane bound dihydroorotate: Quinone oxidoreductase from Staphylococcus aureus - Filipe M. Sousa; Patrícia Pires; Andreia Barreto; Patrícia N. Refojo; Micael S. Silva; Pedro B. Fernandes; Ana P. Carapeto; Tiago T. Robalo; Mário S. Rodrigues; Mariana G. Pinho; Eurico J. Cabrita; Manuela M. Pereira (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Acute bouts of aerobic and resistance exercise similarly alter inhibitory control and response time while inversely modifying plasma BDNF concentrations in middle-aged and older adults with type 2 diabetes - João G. Silveira-Rodrigues; Bruno T. Campos; André T. de Lima; Pedro H. M. Ogando; Camila B. Gomes; Patrícia F. Gomes; Ivana M. S. Aleixo; Danusa D. Soares (Experimental Brain Research, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Four diterpenes identified in silico were isolated from Hyptidinae and demonstrated in vitro activity against Mycobacterium tuberculosis - Andreza Barbosa Silva Cavalcanti; Mayara dos Santos Maia; Pedro Thiago Ramalho de Figueiredo; Renata Priscila Barros de Menezes; Alex France Messias Monteiro; Roseana Araújo Ramos Meireles; Gabriela Cristina Soares Rodrigues; Ana Rita Rodrigues de Almeida Silva; Jociano da Silva Lins; Laísa Vilar Cordeiro; Valnês S. Rodrigues Junior; Ana Paula O. T. Castelo Branco; et al. (Natural Product Research, 2023)

Advancing textural heterogeneity: Effect of manipulating multi-component model foods on the perception of textural complexity - Niamh M. Patterson; Yvonne S. Kuiper; Sophia A. Rodrigues; Bryony J. James; Nicholas Gant; Michael J. Hautus (Food Research International, 2023)

When forest loss leads to biodiversity gain: Insights from the Brazilian Atlantic Forest - Julia Rodrigues Barreto; Renata Pardini; Jean Paul Metzger; Fernando Augusto Barbosa Silva; Elizabeth S. Nichols (Biological Conservation, 2023)

Neuroinflammation in Alzheimer’s disease: potential beneficial effects of vitamin D - Bruna R. Kouba; Anderson Camargo; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2023)

Bacterial identification in cerebrospinal fluid of domestic species with neurologic signs: a retrospective case-series study in 136 animals (2005–2021) - Márcio Garcia Ribeiro; Thiago Tourinho Pereira; Patrik Júnior de Lima Paz; Beatriz Oliveira de Almeida; Carmen S. Araújo Cerviño; Carolina Aparecida Rodrigues; Gabrielly Terra Sartori Santos; Larissa Maria de Souza Freire; Fábio Vinicius Ramos Portilho; Marcelo Fagali Árabe Filho; Natália Rodrigues Paschoal; Thaís Spessotto Bello; et al. (Brazilian Journal of Microbiology, 2023)

Pre-assessments of plant conservation status in islands: the case of French Overseas Territories - S. Véron; A. Bernard; E. Lebreton; C. Rodrigues-Vaz; M. Durand; L. Procopio; M. Hélion; M. Gayot; G. Viscardi; G. A. Krupnick; C. M. S. Carrington; V. Boullet; et al. (Biodiversity and Conservation, 2023)

Assessment of total evaporation rates and its surface distribution by tridimensional modelling and remote sensing - Sofia M.G. Rocha; Ernesto Molinas; Italo S. Rodrigues; Iran E. Lima Neto (Journal of Environmental Management, 2023)

Methyl benzoate and nerolidol attract the cyclocephaline beetle Cyclocephala paraguayensis to trumpet flowers - Arodí P. Favaris; Amanda C. Túler; Weliton D. Silva; Marvin Pec; Sérgio R. Rodrigues; Artur C. D. Maia; José Maurício S. Bento (The Science of Nature, 2023)

The antidepressant-like effect elicited by vitamin D3 is associated with BDNF/TrkB-related synaptic protein synthesis - Bruna R. Kouba; Ana Clara N. C. Torrá; Anderson Camargo; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2023)

Mitochondrial DNA variation of the caracal (Caracal caracal) in Iran and range-wide phylogeographic comparisons - Yasaman Hassan-Beigi; Mónica Rodrigues; Mohammad Ali Adibi; Seyed Massoud Madjdzadeh; Paul Vercammen; Mohammad S. Farhadinia; Carlos Rodríguez Fernandes (Mammalian Biology, 2023)

Pharmacological evaluation of antinociceptive and anti-inflammatory activities of LQFM202: a new piperazine derivative - Aline N. Martins; Dionys de Souza Almeida; Iziara F. Florentino; Lorrane K. da Silva Moreira; Larissa C. Turones; Daniel C. Batista; Lucas S. Machado; Boniek G. Vaz; Luciano M. Lião; Gerlon de Almeida Ribeiro Oliveira; José Luís Rodrigues Martins; James Oluwagbamigbe Fajemiroye; et al. (Inflammopharmacology, 2023)

Connectivity between countries established by landbirds and raptors migrating along the African–Eurasian flyway - João L. Guilherme; Victoria R. Jones; Inês Catry; Martin Beal; Maria P. Dias; Steffen Oppel; Juliet A. Vickery; Chris M. Hewson; Stuart H. M. Butchart; Ana S. L. Rodrigues (Conservation Biology, 2023)
The conservation of long‐distance migratory birds requires coordination between the multiple countries connected by the movements of these species. The recent expansion of tracking studies is shedding new light on these movements, but much of this information is fragmented and inaccessible to conservation practitioners and policy makers. We synthesized current knowledge on the connectivity established between countries by landbirds and raptors migrating along the African–Eurasian flyway. We reviewed tracking studies to compile migration records for 1229 individual birds, from which we derived 544 migratory links, each link corresponding to a species’ connection between a breeding country in Europe and a nonbreeding country in sub‐Saharan Africa. We used these migratory links to analyze trends in knowledge over time and spatial patterns of connectivity per country (across species), per species (across countries), and at the flyway scale (across all countries and all species). The number of tracking studies available increased steadily since 2010 (particularly for landbirds), but the coverage of existing tracking data was highly incomplete. An average of 7.5% of migratory landbird species and 14.6% of raptor species were tracked per country. More data existed from central and western European countries, and it was biased toward larger bodied species. We provide species‐ and country‐level syntheses of the migratory links we identified from the reviewed studies, involving 123 populations of 43 species, migrating between 28 European and 43 African countries. Several countries (e.g., Spain, Poland, Ethiopia, Democratic Republic of Congo) are strategic priorities for future tracking studies to complement existing data, particularly on landbirds. Despite the limitations in existing tracking data, our data and results can inform discussions under 2 key policy instruments at the flyway scale: the African–Eurasian Migratory Landbirds Action Plan and the Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia.

Dietary glutamine improves growth and intestinal morphology of juvenile GIFT tilapia (Oreochromis niloticus) but has limited effects on innate immunity and antioxidant capacity - Pedro L.P.F. Carvalho; William dos S. Xavier; Matheus G. Guimarães; Edgar J.D. Rodrigues; Wilson M. Furuya; Fernando Y. Yamamoto; Luiz E. Pezzato; Delbert M. Gatlin; Margarida M. Barros (Aquaculture, 2023)

Reservoir lithofacies study of the Toolebuc Formation, Eromanga Basin, Australia as a potential unconventional target - Xiaoxiao Mao; Sandra Rodrigues; Joan S. Esterle; Suzanne D. Golding (International Journal of Coal Geology, 2023)

Mouse organoids as an in vitro tool to study the in vivo intestinal response to cytotoxicants - F. Jardi; C. Kelly; C. Teague; H. Fowler-Williams; D. C. Sevin; D. Rodrigues; H. Jo; S. Ferreira; B. Herpers; M. Van Heerden; T. de Kok; C. Pin; et al. (Archives of Toxicology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Small mammals from the C aatinga: A dataset for the B razilian semiarid biome - Anna Ludmilla da Costa‐Pinto; Ricardo S. Bovendorp; Adriana Bocchiglieri; Aldo Caccavo; Ana Cláudia Delciellos; Ana Cláudia Malhado; Ana Karolina Rodrigues de Almeida; Caryne Braga; Diogo Loretto; Edeltrudes Maria Valadares Calaça Câmara; Fernando Heberson Menezes; Gabby Guilhon; et al. (Ecology, 2023)
The Caatinga is an exclusively Brazilian biome, and is the largest and most biodiverse Seasonal Tropical Dry Forest in the world. Despite that, the mammalian fauna, especially small mammals, is the least studied of all Brazilian biomes. In order to fill gaps and provide detailed information on small mammals (Didelphimorphia, Rodentia) in the Caatinga biome, we compiled reliable records focusing on richness, composition and some biometric data. These records came from mammal collections, papers, theses, books, and unpublished data, prioritizing records with vouchers housed in scientific collections. We compiled a total of 3133 records from 816 locations, resulting in a richness of 47 native species (12 marsupials and 35 rodents, plus three exotic rodents, Rattus rattus , Rattus norvegicus , and Mus musculus ). This dataset includes records of three new species for the biome and its transition zone: the rodents Calomys mattevii , Holochilus oxe , and Nectomys squamipes . Of the total number of records, 1808 (57.71%) are from consulting activities, 95 (3.03%) are from zoonoses studies and 104 (3.32%) are from the National Plague Service (SNP). All nine Brazilian states with territory in the Caatinga have sampling data for small mammals, but the number of records and localities are unevenly distributed, with the state of Rio Grande do Norte having the lowest number of records and locations sampled. Our dataset is the first of its kind for the Caatinga biome and has considerable potential value for studies of habitat use, landscape ecology, macroecology, biogeography, and conservation. There are no copyright restrictions on the data. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Triiodothyronine Treatment reverses Depression-Like Behavior in a triple-transgenic animal model of Alzheimer’s Disease - Andréa V. Maglione; Bruna P. P. do Nascimento; Miriam O. Ribeiro; Talytha J. L. de Souza; Renata E. C. da Silva; Monica A. Sato; Carlos A. A. Penatti; Luiz R. G. Britto; Janaina S. de Souza; Rui M.B. Maciel; Rodrigo Rodrigues da Conceição; Roberto Laureano-Melo; et al. (Metabolic Brain Disease, 2022)

Environmental disaster in mining areas: routes of exposure to metals in the Doce River basin - A. R. de Matos; H. T. da Silva; M. C. S. da Faria; B. M. Freire; R. M. Pereira; B. L. Batista; J. L. Rodrigues (International Journal of Environmental Science and Technology, 2022)

Response of benthic dinoflagellates Amphidinium carterae and Bysmatrum gregarium to salinity changes and prolonged darkness: elucidation through laboratory experiments - R. V. Rodrigues; J. S. Patil (Aquatic Ecology, 2022)

The need for European harmonization of Nutrivigilance in a public health perspective: a comprehensive review - G. Vo Van Regnault; M. C. Costa; A. Adanić Pajić; A. P. Bico; S. Bischofova; U. Blaznik; F. Menniti-Ippolito; K. Pilegaard; C. Rodrigues; I. Margaritis (Critical Reviews in Food Science and Nutrition, 2022)

Metformin improves depressive-like behavior in experimental Parkinson’s disease by inducing autophagy in the substantia nigra and hippocampus - Ingrid Prata Mendonça; Igor Henrique Rodrigues de Paiva; Eduardo Pereira Duarte-Silva; Michel Gomes de Melo; Rodrigo S. da Silva; Maria Isabelly Xavier do Nascimento; Christina Alves Peixoto (Inflammopharmacology, 2022)

Potential role of passively increased muscle temperature on contractile function - Patrick Rodrigues; Gabriel S. Trajano; Ian B. Stewart; Geoffrey M. Minett (European Journal of Applied Physiology, 2022)
Declines in muscle force, power, and contractile function can be observed in older adults, clinical populations, inactive individuals, and injured athletes. Passive heating exposure (e.g., hot baths, sauna, or heated garments) has been used for health purposes, including skeletal muscle treatment. An acute increase in muscle temperature by passive heating can increase the voluntary rate of force development and electrically evoked contraction properties (i.e., time to peak twitch torque, half-relation time, and electromechanical delay). The improvements in the rate of force development and evoked contraction assessments with increased muscle temperature after passive heating reveal peripheral mechanisms’ potential role in enhancing muscle contraction. This review aimed to summarise, discuss, and highlight the potential role of an acute passive heating stimulus on skeletal muscle cells to improve contractile function. These mechanisms include increased calcium kinetics (release/reuptake), calcium sensitivity, and increased intramuscular fluid.

Water Quality in a Tropical Estuarine Channel: Current Conditions, Trends, and Trophic Status (1990–2016) - Carlos Noriega; Carmen Medeiros; Humberto L. Varona; Leonardo Rodrigues; Moacyr Araujo; Sury Monteiro; Andrea Xavier da Silva; Newton Antas Pereira; Eduardo Elvino Sales de Lima; Deive S. Teixeira da Silva; Sonali de Campos Pereira; Julia Araujo; et al. (Water, Air, & Soil Pollution, 2022)

An update on the phylogeny of Spintharinae with analysis based on morphological characters and taxonomy of Janula (Araneae, Theridiidae) - Everton Nei Lopes Rodrigues; Patrícia E. S. Rodrigues; Antonio D. Brescovit; Joseph K. H. Koh (Organisms Diversity & Evolution, 2022)

Are the current commercially available oximes capable of reactivating acetylcholinesterase inhibited by the nerve agents of the A-series? - Marcelo C. Santos; Fernanda D. Botelho; Arlan S. Gonçalves; Daniel A. S. Kitagawa; Caio V. N. Borges; Taynara Carvalho-Silva; Leandro B. Bernardo; Cíntia N. Ferreira; Rafael B. Rodrigues; Denise C. Ferreira Neto; Eugenie Nepovimova; Kamil Kuča; et al. (Archives of Toxicology, 2022)

Sugarcane: A Promising Source of Green Carbon in the Circular Bioeconomy - Susan G. Karp; Walter J. M. Burgos; Luciana P. S. Vandenberghe; Kim V. Diestra; Luis A. Z. Torres; Adenise L. Woiciechowski; Luiz A. J. Letti; Gilberto V. M. Pereira; Vanete Thomaz-Soccol; Cristine Rodrigues; Júlio C. de Carvalho; Carlos R. Soccol (Sugar Tech, 2022)

Epithelial morphometric alterations and mucosecretory responses in the nasal cavity of mice chronically exposed to hydrothermal emissions - R. Camarinho; A. Madrero Pardo; P. V. Garcia; A. S. Rodrigues (Environmental Geochemistry and Health, 2022)

Metabolomic Profiling of Phloem Sap from Different Pine Species and Implications on Black Capuchin - Lorena Mara A. Silva; Elenilson G. Alves Filho; Tigressa Helena S. Rodrigues; Francisca Jamila C. Louredo; Guilherme J. Zocolo; Kirley M. Canuto; Sandra B. Mikich; Dieter Liebsch; Adriana De Almeida; Edy S. De Brito (Journal of Chemical Ecology, 2022)

Registered clinical trials investigating treatment of long COVID: a scoping review and recommendations for research - Felicia Ceban; Alexia Leber; Muhammad Youshay Jawad; Mathew Yu; Leanna M. W. Lui; Mehala Subramaniapillai; Joshua D. Di Vincenzo; Hartej Gill; Nelson B. Rodrigues; Bing Cao; Yena Lee; Kangguang Lin; et al. (Infectious Diseases, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

Wide tolerance to environmental conditions and substrate colonization mediates the invasion of false mussels (Bivalvia: Dreissenidae) in brackish systems - Antonio J. S. Rodrigues; Igor C. Miyahira; Nathália Rodrigues; Danielle Ribeiro; Luciano N. Santos; Raquel A. F. Neves (Biological Invasions, 2022)

Asynchrony, density dependence, and persistence in an amphibian - Freya E. Rowland; Elizabeth S. Schyling; L. Kealoha Freidenburg; Mark C. Urban; Jonathan L. Richardson; A. Z. Andis Arietta; Susan B. Rodrigues; Adriana D. Rubinstein; Michael F. Benard; David K. Skelly (Ecology, 2022)
Understanding drivers of metapopulation dynamics remains a critical challenge for ecology and conservation. In particular, the degree of synchrony in metapopulation dynamics determines how resilient a metapopulation is to a widespread disturbance. In this study, we used 21 years of egg mass count data across 64 nonpermanent freshwater ponds in Connecticut, USA to evaluate patterns of abundance and growth and to assess regional as well as local factors in shaping the population dynamics of wood frogs ( Rana sylvatica = Lithobates sylvaticus ). In particular, we asked whether a species known to undergo metapopulation dynamics exhibited spatial synchrony in abundances. With the exception of a single year when breeding took place during severe drought conditions, our analyses revealed no evidence of synchrony despite close proximity (mean minimum distance

Incidence of SARS-CoV-2 infection in a cohort of workers from the University of Porto, Portugal - Joana Pinto da Costa; Paula Meireles; Pedro N. S. Rodrigues; Henrique Barros (Infectious Diseases, 2022)

Lung-Brain Crosstalk in Sepsis: Protective Effect of Prophylactic Physical Exercise Against Inflammation and Oxidative Stress in Rats - Amanda Della Giustina; Judite Filgueiras Rodrigues; Erick Bagio; Sandra Bonfante; Larissa Joaquim; Graciela Zarbato; Solange Stork; Richard Simon Machado; Mariana Pereira de Souza Goldim; Lucinéia Gainski Danielski; Khiany Mathias; Carlos Dacoregio; et al. (Molecular Neurobiology, 2022)

Involvement of serotonergic neurotransmission in the antidepressant-like effect elicited by cholecalciferol in the chronic unpredictable stress model in mice - Vivian B. Neis; Isabel Werle; Morgana Moretti; Priscila B. Rosa; Anderson Camargo; Yasmim de O. Dalsenter; Nicolle Platt; Axel F. Rosado; William D. Engel; Gudrian Ricardo L. de Almeida; Ingrid Selhorst; Alcir Luiz Dafre; et al. (Metabolic Brain Disease, 2022)

Comparison of sugarcane pressmud with traditional low-cost materials for adsorption of lead and zinc in mining areas - I. M. Raimondi; E. M. Vieira; L. A. A. Vaz; V. G. S. Rodrigues (International Journal of Environmental Science and Technology, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Occurrence of Volcanogenic Inorganic Mercury in Wild Mice Spinal Cord: Potential Health Implications - A. Navarro-Sempere; M. García; A. S. Rodrigues; P. V. Garcia; R. Camarinho; Y. Segovia (Biological Trace Element Research, 2022)
Mercury accumulation has been proposed as a toxic factor that causes neurodegenerative diseases. However, the hazardous health effects of gaseous elemental mercury exposure on the spinal cord in volcanic areas have not been reported previously in the literature. To evaluate the presence of volcanogenic inorganic mercury in the spinal cord, a study was carried out in São Miguel island (Azores, Portugal) by comparing the spinal cord of mice exposed chronically to an active volcanic environment (Furnas village) with individuals not exposed (Rabo de Peixe village), through the autometallographic silver enhancement histochemical method. Moreover, a morphometric and quantification analysis of the axons was carried out. Results exhibited mercury deposits at the lumbar level of the spinal cord in the specimens captured at the site with volcanic activity (Furnas village). A decrease in axon calibre and axonal atrophy was also observed in these specimens. Given that these are relevant hallmarks in the neurodegenerative pathologies, our results highlight the importance of the surveillance of the health of populations chronically exposed to active volcanic environments.

Level of genetic divergence among accessions of the native forage grass, Mesosetum chaseae Luces, for tracing strategies to conservation of germplasm collections from the brazilian pantanal - Ana Clara de Sousa Meirelles; Eliane Rodrigues Monteiro; Claudete Aparecida Mangolin; Sandra Aparecida Santos; Maria de Fátima P. S. Machado (Conservation Genetics Resources, 2022)

Combined effects of bird extinctions and introductions in oceanic islands: Decreased functional diversity despite increased species richness - Filipa C. Soares; Ricardo F. de Lima; Jorge M. Palmeirim; Pedro Cardoso; Ana S. L. Rodrigues (Global Ecology and Biogeography, 2022)
Aim We analyse the consequences of species extinctions and introductions on the functional diversity and composition of island bird assemblages. Specifically, we ask if introduced species have compensated the functional loss resulting from species extinctions. Location Seventy‐four oceanic islands (> 100 km 2 ) in the Atlantic, Pacific and Indian Oceans. Time period Late Holocene. Major taxa studied Terrestrial and freshwater bird species. Methods We compiled a species list per island (extinct and extant, native and introduced), and then compiled traits per species. We used single‐trait analyses to assess the effects of past species extinctions and introductions on functional composition. Then, we used probabilistic hypervolumes in trait space to calculate functional richness and evenness of original versus present avifaunas of each island (and net change), and to estimate how functionally unique are extinct and introduced species on each island. Results The net effects of extinctions and introductions were: an increase in average species richness per island (alpha diversity), yet a decline in diversity across all islands (gamma diversity); an average increase in the prevalence of most functional traits, yet an average decline in functional richness and evenness, associated with the fact that extinct species were functionally more unique (when compared to extant natives) than introduced species. Main conclusions Introduced species are on average offsetting (and even surpassing) the losses of extinct species per island in terms of species richness, and they are increasing the prevalence of most functional traits. However, they are not compensating for the loss of functional richness due to extinctions. Current island bird assemblages are becoming functionally poorer, having lost unique species and being composed of functionally more redundant species. This is likely to have cascading repercussions on the functioning of island ecosystems. We highlight that taxonomic and functional biodiversity should be assessed simultaneously to understand the global impacts of human activities.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Which birds are Brazilians seeing on urban and non-urban feeders? An analysis based on a collective online birding - Eduardo Roberto Alexandrino; Thaís Abreu Camboim; Flávia Guimarães Chaves; Alex Augusto Abreu Bovo; Marco Aurélio Galvão da Silva; Daniela Alves Maia da Silva; Margi Moss; Tatiana Pongiluppi Souza; Clarissa de Oliveira Santos; Caio Bezerra de Mattos Brito; Maristela Camolesi Alcantara; Karlla V. C. Barbosa; et al. (Ornithology Research, 2022)

Correction to: Basic oxygen furnace sludge to treat industrial arsenic- and sulfate‑rich acid mine drainage - Sandrine F. Araujo; Cláudia L. Caldeira; Virginia S. T. Ciminelli; Ricardo P. Borba; Joanna P. Rodrigues; Gustavo F. Simões (Environmental Science and Pollution Research, 2022)

Basic oxygen furnace sludge to treat industrial arsenic- and sulfate-rich acid mine drainage - Sandrine F. Araujo; Cláudia L. Caldeira; Virginia S. T. Ciminelli; Ricardo P. Borba; Joanna P. Rodrigues; Gustavo F. Simões (Environmental Science and Pollution Research, 2022)

Attraction of whitefly Aleurodicus cocois mediated by cashew volatiles - Wenner V. A. Saraiva; Nívia S. Dias-Pini; Elenilson G. Alves Filho; José W. S. Melo; Marilene Fancelli; Cristiane R. Coutinho; Guilherme J. Zocolo; Tigressa H. S. Rodrigues; Poliana M. Duarte; Vitor H. M. Macedo; Elaine S. S. Goiana (Phytoparasitica, 2022)

Folic acid supplementation during pregnancy alters behavior in male rat offspring: nitrative stress and neuroinflammatory implications - Josiane Silva Silveira; Osmar Vieira Ramires Júnior; Felipe Schmitz; Fernanda Silva Ferreira; Fabiana Cristina Rodrigues; Robson Coutinho Silva; Luiz Eduardo Baggio Savio; Angela T. S. Wyse (Molecular Neurobiology, 2022)

RI75, a curcumin analogue, inhibits tumor necrosis factor-α and interleukin-6 production and exhibits antiallodynic and antiedematogenic activities in mice - Sarah O. A. M. Costa; Ianny B. Rodrigues; Alysson V. Braga; Bárbara C. M. Barbosa; Roger R. L. Silva; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela Í. Morais; Brenda F. M. Castro; Armando S. Cunha Júnior; Vinícius G. Maltarollo; Renata B. Oliveira; et al. (Inflammopharmacology, 2022)

Novel Lethal Clostridial Infection in Florida Manatees (Trichechus manatus latirostris): Cause of the 2013 Unusual Mortality Event in the Indian River Lagoon - Jan H. Landsberg; Maki Tabuchi; David S. Rotstein; Kuttichantran Subramaniam; Thais C. S. Rodrigues; Thomas B. Waltzek; Nicole I. Stacy; Patrick W. Wilson; Yasunari Kiryu; Francisco A. Uzal; Martine de Wit (Frontiers in Marine Science, 2022)
The Indian River Lagoon (IRL) on Florida’s east coast is a biologically diverse estuary and an important habitat to the threatened Florida manatee ( Trichechus manatus latirostris ). An unusual mortality event (UME) was declared by the Working Group on Marine Mammal Unusual Mortality Events in 2013 after a marked increase in manatee deaths in the IRL of an unknown cause. This UME followed a dramatic reduction of seagrass coverage in the IRL due to chronic non-toxic phytoplankton blooms, with a resultant ecosystem shift to mixed macroalgal dominance. At least 199 manatee deaths fitting the UME case definition were documented in and adjacent to the IRL during 2012–2019; mortality was highest in 2013, when 111 of these deaths were documented. The case definition included carcasses in good nutritional condition, with multiorgan congestion or wet lungs consistent with drowning without trauma. The gastrointestinal compartments of manatee carcasses were filled with diverse macroalga species, and the contents were notably more fluid than usual. Gross intestinal findings included blebbing to segmental thickening of the wall. Microscopic lesions were primarily intestinal, including necrosis, edema, hemorrhage, mucosa-associated lymphoid changes, and inflammation, sometimes associated with Gram-positive bacterial rods. A multidisciplinary approach of environmental and carcass sampling found no causative evidence through tests for micro- and macroalgal biotoxins, trace metals, general toxin screening, or vitreum biochemistry. Microbiological, cytological, immunohistochemical, and molecular analyses of Clostridiales from intestinal samples identified Clostridioides difficile toxin A, toxins A/B and toxin A gene; Paeniclostridium sordellii lethal gene (and other potential virulence factors from a sequenced strain); and Clostridium perfringens alpha and epsilon toxin genes. The results from this 8 year-long investigation are indicative that the cause of death in this manatee UME was associated with clostridial infection, initiated by a shift to a predominantly macroalgal diet.

Influence of spatial and environmental factors on the structure of a zooplankton metacommunity in an intermittent river - Eliêta A. Ramos; Cláudio Simões de Morais-Junior; Carlos A. S. Rodrigues-Filho; Jorge I. Sánchez-Botero; Mauro Melo Júnior; José L. C. Novaes (Aquatic Ecology, 2022)

Pharmacological blockage of the AHR-CYP1A1 axis: a call for in vivo evidence - N. R. Coelho; A. B. Pimpão; M. J. Correia; T. C. Rodrigues; E. C. Monteiro; J. Morello; S. A. Pereira (Journal of Molecular Medicine, 2022)

Manganese(I) tricarbonyl complexes as potential anticancer agents - Oscar A. Lenis-Rojas; Beatriz Carvalho; Rui Cabral; Margarida Silva; Sofia Friães; Catarina Roma-Rodrigues; Marta S. H. Meireles; Clara S. B. Gomes; Jhonathan A. A. Fernández; Sabela F. Vila; Juan A. Rubiolo; Laura Sanchez; et al. (JBIC Journal of Biological Inorganic Chemistry, 2022)

Metformin effect in models of inflammation is associated with activation of ATP-dependent potassium channels and inhibition of tumor necrosis factor-α production - Paulo S. A. Augusto; Tamires C. Matsui; Alysson V. Braga; Felipe F. Rodrigues; Marcela I. Morais; Marcela M. G. B. Dutra; Carla R. A. Batista; Ivo S. F. Melo; Sarah O. A. M. Costa; Caryne M. Bertollo; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Spatial controls on riverbed sediment chemistry in three anthropogenically modified tropical mountainous watersheds - J. Papotto; L. J. Rodrigues; E. M. Siebert; E. J. Wagner; S. T. Goldsmith (International Journal of Environmental Science and Technology, 2022)

Assessment of Water Quality Parameters and their Seasonal Behaviour in a Portuguese Water Supply System: a 6-year Monitoring Study - Raquel S. Chaves; Daniel Salvador; Paulo Nogueira; Miguel M. Santos; Paula Aprisco; Célia Neto; Vítor Cardoso; Maria J. Benoliel; João E. Rodrigues; Rui N. Carneiro (Environmental Management, 2022)

Household dependence on fish-based farming systems in the Bons Sinais Estuary in Mozambique - Rodrigues P. Francisco; Antonio M. Hoguane; Rosa L. Simbine; Humberto S. Mabota (Western Indian Ocean Journal of Marine Science, 2021)
Households in estuarine deltas of the Western Indian Ocean depend on small-scale fishing, farming in flood-recession and adjacent areas, and mangrove forest products for food security, energy and an income in so-called deltaic fish-based farming (FBF) systems. It was hypothesized that the relative importance of household activities would depend on location along the Bons Sinais Estuary in Mozambique, diversifying in peri-urban settings. Semi-structured interviews were undertaken at five sites, including rural sites near the estuary mouth and upstream, and peri-urban settings near Quelimane city. Fishing contributed the most to FBF livelihoods (54 %) followed by farming (15 %), small business operators (14 %), collection and use of mangrove products (6 %) and other activities such as wage-earning or formal employment (10 %). The highest diversity of activities was at a peri-urban site, Chuabo Dembe, which differed from all other sites in Cluster and Principal Components Analyses. Fishing dominated activities at four of five sites, with the highest preponderance near the estuary mouth. Women played an important role in generating household income, mainly through farming and operating small businesses in peri-urban areas. The education level declined in rural settings. Overexploitation and degradation of natural ecosystems to provide for an increasing urban population around Quelimane threaten estuarine functioning, making deltaic FBF systems vulnerable. Rural development programmes should focus on improving education levels and the efficiency of food production, processing and distribution systems.

The antileishmanial activity of the antarctic brown alga Ascoseira mirabilis Skottsberg - Leandro da Costa Clementino; Fernando Bombarda Oda; Thaiz Rodrigues Teixeira; Renata Spagolla Napoleão Tavares; Pio Colepicolo; André Gonzaga dos Santos; Hosana Maria Debonsi; Márcia A. S. Graminha (Natural Product Research, 2021)

Pyramiding dsRNAs increases phytonematode tolerance in cotton plants - Maria E. Lisei-de-Sá; Paolo L. Rodrigues-Silva; Carolina V. Morgante; Bruno Paes de Melo; Isabela T. Lourenço-Tessutti; Fabricio B. M. Arraes; João P. A. Sousa; Rafael Galbieri; Regina M. S. Amorim; Camila B. J. de Lins; Leonardo L. P. Macedo; Valdeir J. Moreira; et al. (Planta, 2021)

Ketamine, but not fluoxetine, rapidly rescues corticosterone-induced impairments on glucocorticoid receptor and dendritic branching in the hippocampus of mice - Daiane B. Fraga; Anderson Camargo; Gislaine Olescowicz; Dayane Azevedo Padilha; Francielle Mina; Josiane Budni; Patricia S. Brocardo; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2021)

Aerobic degradation of 2,4,6-trinitrophenol by Proteus sp. strain OSES2 obtained from an explosive contaminated tropical soil - Osekokhune E. Okozide; Sunday A. Adebusoye; Oluwafemi S. Obayori; Deborah F. Rodrigues (Biodegradation, 2021)

Whiptail lizard lineage delimitation and population expansion as windows into the history of Amazonian open ecosystems - Lidia F. Martins; Erik L. Choueri; Alan F. S. Oliveira; Fabrícius M. C. B. Domingos; Gabriel H. O. Caetano; Vitor H. G. L. Cavalcante; Rafael N. Leite; Antoine Fouquet; Miguel T. Rodrigues; Ana C. Carnaval; Guarino R. Colli; Fernanda P. Werneck (Systematics and Biodiversity, 2021)

Proteome of Erythroxylum pungens (Erythroxylaceae): an endemic species of the semiarid Caatinga - Daisy Sotero Chacon; Ivanice Bezerra da Silva; Taffarel Melo Torres; Gabrielle Macedo Pereira; Letícia Gondim Lambert Moreira; Luiz Fernando Rodrigues de Souza; Fernanda Priscila Santos Reginaldo; Alan de Araújo Roque; José Angelo S. Zuanazzi; Renata Libonati; Julia A. Rodrigues; Filippe L.M Santos; et al. (Plant Biosystems, 2021)

Dopaminergic Receptors as Neuroimmune Mediators in Experimental Autoimmune Encephalomyelitis - E. C. D. Gonçalves; V. Lieberknecht; V. V. Horewicz; B. D. Rabelo; F. A. Felipetti; A. L. S. Rodrigues; D. F. Martins; R. C. Dutra (Molecular Neurobiology, 2021)

Chronic exposure to volcanic gaseous elemental mercury: using wild Mus musculus to unveil its uptake and fate - R. Camarinho; A. Navarro-Sempere; P. V. Garcia; M. García; Y. Segovia; A. S. Rodrigues (Environmental Geochemistry and Health, 2021)

Human astrovirus types 1, 4 and 5 circulating among children with acute gastroenteritis in a rural Brazilian state, 2010-2016 - Adriana Luchs; Kaelan Tardy; Roozbeh Tahmasebi; Simone Guadagnucci Morillo; Flavio Augusto de Pádua Milagres; Vanessa dos Santos Morais; Rafael Brustulin; Maria da Aparecida Rodrigues Teles; Lais Sampaio de Azevedo; Ellen Viana de Souza; Roberta Salzone Medeiros; Yasmin França Viana Pires de Souza; et al. (Archives of Virology, 2021)

Quorum sensing disruption regulates hydrolytic enzyme and biofilm production in estuarine bacteria - Marion Urvoy; Raphaël Lami; Catherine Dreanno; David Daudé; Alice M. S. Rodrigues; Michèle Gourmelon; Stéphane L'Helguen; Claire Labry (Environmental Microbiology, 2021)
Summary Biofilms of heterotrophic bacteria cover organic matter aggregates and constitute hotspots of mineralization, primarily acting through extracellular hydrolytic enzyme production. Nevertheless, regulation of both biofilm and hydrolytic enzyme synthesis remains poorly investigated, especially in estuarine ecosystems. In this study, various bioassays, mass spectrometry and genomics approaches were combined to test the possible involvement of quorum sensing (QS) in these mechanisms. QS is a bacterial cell–cell communication system that relies notably on the emission of N ‐acylhomoserine lactones (AHLs). In our estuarine bacterial collection, we found that 28 strains (9%), mainly Vibrio , Pseudomonas and Acinetobacter isolates, produced at least 14 different types of AHLs encoded by various luxI genes. We then inhibited the AHL QS circuits of those 28 strains using a broad‐spectrum lactonase preparation and tested whether biofilm production as well as β‐glucosidase and leucine‐aminopeptidase activities were impacted. Interestingly, we recorded contrasted responses, as biofilm production, dissolved and cell‐bound β‐glucosidase and leucine‐aminopeptidase activities significantly increased in 4%–68% of strains but decreased in 0%–21% of strains. These findings highlight the key role of AHL‐based QS in estuarine bacterial physiology and ultimately on biogeochemical cycles. They also point out the complexity of QS regulations within natural microbial assemblages.

Mismatch between bird species sensitivity and the protection of intact habitats across the Americas - Victor Cazalis; Megan D. Barnes; Alison Johnston; James E. M. Watson; Cagan H. Şekercioğlu; Ana S. L. Rodrigues (Ecology Letters, 2021)
Protected areas are highly heterogeneous in their effectiveness at buffering human pressure, which may hamper their ability to conserve species highly sensitive to human activities. Here, we use 60 million bird observations from eBird to estimate the sensitivity to human pressure of each bird species breeding in the Americas. Concerningly, we find that ecoregions hosting large proportions of high‐sensitivity species, concentrated in tropical biomes, do not have more intact protected habitat. Moreover, 266 high‐sensitivity species have little or no intact protected habitat within their distributions. Finally, we show that protected area intactness is decreasing faster where high‐sensitivity species concentrate. Our results highlight a major mismatch between species conservation needs and the coverage of intact protected habitats, which likely hampers the long‐term effectiveness of protected areas at retaining species. We highlight ecoregions where protection and management of intact habitats, complemented by restoration, is urgently needed.

Microencapsulated Lemongrass ( Cymbopogon flexuosus ) Essential Oil Supplementation on Quality and Stability of Silver Catfish Fillets during Frozen Storage - Cristine Rampelotto; Caroline S. Speroni; Lisiane Conte; Dirleise Pianesso; Isadora S. Machado; Renata F. Rodrigues; Natália M. Minuzzi; Taida J. Adorian; Bruna Klein; Roger Wagner; Bernardo Baldisserotto; Leila P. da Silva; et al. (Journal of Aquatic Food Product Technology, 2021)

Tropical grass and legume pastures may alter lamb meat physical and chemical characteristics - V. S. Hampel; C. H. E. C. Poli; M. Joy; J. F. Tontini; T. Devincenzi; J. R. B. Pardos; R. E. F. Macedo; E. N. Nalério; A. G. F. Saccol; E. Rodrigues; V. Manfroi; N. M. Fajardo (Tropical Animal Health and Production, 2021)

Low doses of ketamine and guanosine abrogate corticosterone-induced anxiety-related behavior, but not disturbances in the hippocampal NLRP3 inflammasome pathway - Anderson Camargo; Ana Paula Dalmagro; Daiane B. Fraga; Julia M. Rosa; Ana Lúcia B. Zeni; Manuella P. Kaster; Ana Lúcia S. Rodrigues (Psychopharmacology, 2021)

Light- and nutrient-related relationships in mixed plantations of Eucalyptus and a high diversity of native tree species - Nino Tavares Amazonas; David I. Forrester; Carina Camargo Silva; Danilo Roberti Alves de Almeida; Rafael Silva Oliveira; Ricardo Ribeiro Rodrigues; Pedro H. S. Brancalion (New Forests, 2021)

Total and Organic Mercury in Fish from Different Geographical Areas in the North Atlantic Ocean and Health Risk Assessment - H. C. Vieira; M. M. B. Ramirez; M. D. Bordalo; A. C. M. Rodrigues; A. M. V. M. Soares; S. N. Abreu; F. Morgado; J. Rendón-von Osten (Exposure and Health, 2021)

Impact of growing seasons and pesticides used on the occurrence and severity of the gummy stem blight in melon cultivation in Brazil - Gil Rodrigues dos Santos; P. H. Tschoeke; R. A. Sarmento; E. E. Oliveira; N. Rodrigues-Silva; M. S. Dalcin; K. Haddi; R. S. Silva (European Journal of Plant Pathology, 2021)

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

Propolis and Lentinula edodes extracts can control the angular leaf spot of strawberry by different mechanisms - Bruna Rodrigues; Danila S. O. Coqueiro; Robson M. Di Piero (Journal of Plant Pathology, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

A Novel Orthoreovirus Isolated From Dead Stranded Harbor Seals From Puget Sound, Washington State, United States - Ole Nielsen; Thaís C. S. Rodrigues; Vsevolod L. Popov; Kuttichantran Subramaniam; Thomas B. Waltzek; Dyanna M. Lambourn; Stephen Raverty (Frontiers in Marine Science, 2021)
As part of an ongoing investigation of harbor seal ( Phoca vitulina ) mortalities within Puget Sound, Washington State, United States, between October 2007 and July 2008, 25 seal cases were submitted for histopathology and ancillary diagnostic testing, including additional attempted virus isolation. In vitro granular and refractile cytopathic effects (CPE) were consistently observed in Vero.DogSLAMtag cells inoculated with tissue homogenates from three seals. Transmission electron microscopy of infected Vero.DogSLAMtag cells revealed cytoplasmic clusters of icosahedral viral particles morphologically consistent with members of the family Reoviridae . The complete genome of a novel species within the genus Orthoreovirus , tentatively named phocid orthoreovirus 1 (PhRV1), was determined by next-generation sequencing and confirmed by rt-PCR in isolates from the three harbor seals. This is the first report of an orthoreovirus infection associated with dead stranded harbor seals. Aside from the CPE and ultrastructural findings, no consistent signalment, gross pathology, histopathology, or ancillary diagnostic findings were identified with PhRV1 infection. Further research is needed to determine the prevalence, tissue tropism, transmission, pathogenicity, zoonotic potential, and host range of orthoreoviruses in pinnipeds. This study demonstrates the value of thorough necropsy investigations and a multidisciplinary team approach to advance our understanding of marine mammal health.

The neurotherapeutic role of a selenium-functionalized quinoline in hypothalamic obese rats - Karline C. Rodrigues; Cristiani F. Bortolatto; Ketlyn P. da Motta; Renata L. de Oliveira; Jaini J. Paltian; Roberta Krüger; Silvane S. Roman; Silvana P. Boeira; Diego Alves; Ethel Antunes Wilhelm; Cristiane Luchese (Psychopharmacology, 2021)

Overexploitation and anthropogenic disturbances threaten the genetic diversity of an economically important neotropical palm - Jéssica Ritchele Moura dos Santos; Fábio de Almeida Vieira; Cristiane Gouvêa Fajardo; Murilo Malveira Brandão; Richeliel Albert Rodrigues Silva; Alistair S. Jump (Biodiversity and Conservation, 2021)

Plastic pollution: A focus on freshwater biodiversity - Valter M. Azevedo-Santos; Marcelo F. G. Brito; Pedro S. Manoel; Júlia F. Perroca; Jorge Luiz Rodrigues-Filho; Lucas R. P. Paschoal; Geslaine R. L. Gonçalves; Milena R. Wolf; Martín C. M. Blettler; Marcelo C. Andrade; André B. Nobile; Felipe P. Lima; et al. (Ambio, 2021)

A Concise Review on Induced Pluripotent Stem Cell-Derived Cardiomyocytes for Personalized Regenerative Medicine - Pallavi Pushp; Diogo E. S. Nogueira; Carlos A. V. Rodrigues; Frederico C. Ferreira; Joaquim M. S. Cabral; Mukesh Kumar Gupta (Stem Cell Reviews and Reports, 2021)

Antidepressant-like effect of guanosine involves activation of AMPA receptor and BDNF/TrkB signaling - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Fernanda N. Kaufmann; Mauren K. Tavares; Isabel Werle; Yasmim Dalsenter; Nicolle Platt; Axel F. Rosado; Daiane B. Fraga; Isabella A. Heinrich; et al. (Purinergic Signalling, 2021)

Potent Anti-Candida Fraction Isolated from Capsicum chinense Fruits Contains an Antimicrobial Peptide That is Similar to Plant Defensin and is Able to Inhibit the Activity of Different α-Amylase Enzymes - Mariana C. L. Aguieiras; Larissa M. Resende; Thaynã A. M. Souza; Celso S. Nagano; Renata P. Chaves; Gabriel B. Taveira; André O. Carvalho; Rosana Rodrigues; Valdirene M. Gomes; Érica O. Mello (Probiotics and Antimicrobial Proteins, 2021)

Cytocompatible cellulose nanofibers from invasive plant species Agave americana L. and Ricinus communis L.: a renewable green source of highly crystalline nanocellulose - Olga L. Evdokimova; Carla S. Alves; Radenka M. Krsmanović Whiffen; Zaida Ortega; Helena Tomás; João Rodrigues (Journal of Zhejiang University-SCIENCE B, 2021)

Correction to: A copper(II)-binding triazole derivative with ionophore properties is active against Candida spp. - A. Gaspar-Cordeiro; S. da Silva; M. Aguiar; C. Rodrigues-Pousada; H. Haas; L. M. P. Lima; C. Pimentel (JBIC Journal of Biological Inorganic Chemistry, 2021)

Diallel analysis of the morphoagronomic, phytochemical, and antioxidant traits in Capsicum baccatum var. pendulum - Gisely Paula Gomes; Douglas Mariani Zeffa; Leonel Vinicius Constantino; Viviane Yumi Baba; Cristina Silvar; Federico Pomar; Rosana Rodrigues; Leandro S. A. Gonçalves (Horticulture, Environment, and Biotechnology, 2021)

Exposure to four chemical UV filters through contaminated sediment: impact on survival, hatching success, cardiac frequency, and aerobic metabolic scope in embryo-larval stage of zebrafish - Julie Lucas; Valentin Logeux; Alice M. S. Rodrigues; Didier Stien; Philippe Lebaron (Environmental Science and Pollution Research, 2021)

KIR2DL4 genetic diversity in a Brazilian population sample: implications for transcription regulation and protein diversity in samples with different ancestry backgrounds - Emiliana Weiss; Heloisa S. Andrade; Juliana Rodrigues Lara; Andreia S. Souza; Michelle A. Paz; Thálitta H. A. Lima; Iane O. P. Porto; Nayane S. B. Silva; Camila F. Bannwart Castro; Rejane M. T. Grotto; Eduardo A. Donadi; Celso T. Mendes-Junior; et al. (Immunogenetics, 2021)

Not just a methane source: Amazonian floodplain sediments harbour a high diversity of methanotrophs with different metabolic capabilities - Júlia B. Gontijo; Fabiana S. Paula; Andressa M. Venturini; Caio A. Yoshiura; Clovis D. Borges; José Mauro S. Moura; Brendan J.M. Bohannan; Klaus Nüsslein; Jorge L. Mazza Rodrigues; Siu M. Tsai (Molecular Ecology, 2021)
The Amazonian floodplain forests are dynamic ecosystems of great importance for the regional hydrological and biogeochemical cycles and function as a significant CH 4 source contributing to the global carbon balance. Unique geochemical factors may drive the microbial community composition and, consequently, affect CH 4 emissions across floodplain areas. Here, we report the in situ composition of CH 4 cycling microbial communities in Amazonian floodplain sediments. We considered how abiotic factors may affect the microbial community composition and, more specifically, CH 4 cycling groups. We collected sediment samples during wet and dry seasons from three different types of floodplain forests, along with upland forest soil samples, from the Eastern Amazon, Brazil. We used high‐resolution sequencing of archaeal and bacterial 16S rRNA genes combined with real‐time PCR to quantify Archaea and Bacteria, as well as key functional genes indicative of the presence of methanogenic ( mcr A) and methanotrophic ( pmo A) microorganisms. Methanogens were found to be present in high abundance in floodplain sediments, and they seem to resist the dramatic environmental changes between flooded and nonflooded conditions. Methanotrophs known to use different pathways to oxidise CH 4 were detected, including anaerobic archaeal and bacterial taxa, indicating that a wide metabolic diversity may be harboured in this highly variable environment. The floodplain environmental variability, which is affected by the river origin, drives not only the sediment chemistry but also the composition of the microbial communities. These environmental changes seem also to affect the pools of methanotrophs occupying distinct niches. Understanding these shifts in the methanotrophic communities could improve our comprehension of the CH 4 emissions in the region.

Environmental correlates of taxonomic and phylogenetic diversity in the Atlantic Forest - Andrea Paz; Jason L. Brown; Carlos L. O. Cordeiro; Julian Aguirre‐Santoro; Claydson Assis; Renata Cecilia Amaro; Fabio Raposo do Amaral; Thuane Bochorny; Lucas F. Bacci; Mayara K. Caddah; Fernando d’Horta; Miriam Kaehler; et al. (Journal of Biogeography, 2021)
Aim There is little consensus on which environmental variables are best at predicting multiple dimensions of diversity. We ask whether there are common environmental correlates of diversity, despite ecological differences, across nine clades of plants and animals distributed along a single rainforest domain. For that, we compare the environmental correlates of species richness, phylogenetic diversity, and phylogenetic endemism. Location Brazilian Atlantic Forest. Taxon: Five clades of plants (Bromelioideae, Miconieae, Bertolonia , Cambessedesieae, and the Fridericia and allies) and four clades of animals (butterlies in the tribe Ithomiini, frogs in the genera Boana and Proceratophrys , and birds in the subfamily Thraupinae). Methods Using curated occurrence localities and phylogenetic data, we generated maps of (a) species richness, (b) phylogenetic diversity, (c) residuals of phylogenetic diversity regressed on species richness, and (d) phylogenetic endemism for all groups. We also compiled a set of 30 environmental descriptors, including records of current temperature and precipitation, climatic stability over time, and topography. Through a machine learning framework, we explored the environmental correlates of each of these diversity measures for each group. Results The environmental variables used here were strong predictors of diversity for all studied groups. However, models for phylogenetic endemism had lower predictive power. Although patterns of diversity are different among groups, correlates of diversity are consistent across taxa. For both species richness and phylogenetic diversity, current precipitation and precipitation stability over time were consistently ranked among the variables that strongly correlate with diversity patterns. The correlates of phylogenetic endemism were less homogeneous across groups. The results suggest that including climate stability over time is important when predicting diversity measures that reflect historical components. Main conclusions Investigating environmental correlates of diversity for multiple clades and diversity measures in a single geographic area allows for a better understanding of common patterns across taxa. This study shows that environmental conditions, particularly precipitation, are good predictors of the patterns of species richness and phylogenetic diversity‐but not phylogenetic endemism‐across different Atlantic Forest groups.

Soil resource availability, plant defense, and herbivory along a successional gradient in a tropical dry forest - Jhonathan O. Silva; Herbert Souza-Silva; Priscyla M. S. Rodrigues; Pablo Cuevas-Reyes; Mário M. Espírito-Santo (Plant Ecology, 2021)

Using richness of native and non-native aquatic species along a climatic gradient to test the intermediate disturbance hypothesis - Luciano N. Santos; Ana Clara S. Franco; Joice S. de Souza; Igor C. Miyahira; Antonio Jailson S. Rodrigues; Isabela Cristina B. Gonçalves; Natascha Krepsky; Helga A. B. Monte; Clarissa Naveira; Tatiana M. B. Cabrini; Rayane R. S. Abude; Matheus Augusto; et al. (Hydrobiologia, 2021)

Imidacloprid-mediated alterations on the salivary glands of the Neotropical brown stink bug, Euschistus heros - Nathaly L. Castellanos; Noelio A. Ferreira-Filho; Higor S. Rodrigues; Luis Carlos Martínez; José E. Serrão; Eugenio E. Oliveira (Ecotoxicology, 2021)

Functional and structural brain connectivity in congenital deafness - Karolyne Dell Ducas; Antonio Carlos da S. Senra Filho; Pedro Henrique Rodrigues Silva; Kaio Felippe Secchinato; Renata Ferranti Leoni; Antonio Carlos Santos (Brain Structure and Function, 2021)

Ketamine-induced urological toxicity: potential mechanisms and translation for adults with mood disorders receiving ketamine treatment - Jason Ng; Leanna M. W. Lui; Joshua D. Rosenblat; Kayla M. Teopiz; Orly Lipsitz; Danielle S. Cha; Jiaqi Xiong; Flora Nasri; Yena Lee; Kevin Kratiuk; Nelson B. Rodrigues; Hartej Gill; et al. (Psychopharmacology, 2021)

Glycoside hydrolases from the tunics of two Antarctic ascidians (Ascidia challengeri and Pyura bouvetensis) and the tropical species Phallusia nigra - Elisa K. S. Ramos; Stéfanie C. L. dos Santos; Kerolyn K. Kuroki; Letícia Benavalli; Gannabathula S. Vani; Valter J. Cobo; Takahisa Hayashi; Edson Rodrigues; Cecilia N. K. Suda (Polar Biology, 2021)

(3,3’-Methylene)bis-2-hydroxy-1,4-naphthoquinones induce cytotoxicity against DU145 and PC3 cancer cells by inhibiting cell viability and promoting cell cycle arrest - Paula Priscilla de Freitas; Ruan Carlos Busquet Ribeiro; Isabella dos Santos Guimarães; Caroline S. Moreira; David R. Rocha; Fernando de Carvalho da Silva; Vitor Francisco Ferreira; Etel Rodrigues Pereira Gimba (Molecular Biology Reports, 2021)

Neuronal activity regulated pentraxin (narp) and GluA4 subunit of AMPA receptor may be targets for fluoxetine modulation - Isabella A. Heinrich; Andiara E. Freitas; Ingrid A. V. Wolin; Ana Paula M. Nascimento; Roger Walz; Ana Lúcia S. Rodrigues; Rodrigo B. Leal (Metabolic Brain Disease, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Scale‐dependent patterns of metacommunity structuring in aquatic organisms across floodplain systems - Fernando M. Lansac‐Tôha; Luis M. Bini; Jani Heino; Bianca R. Meira; Bianca T. Segovia; Carla S. Pavanelli; Claudia C. Bonecker; Claudia P. de Deus; Evanilde Benedito; Geziele M. Alves; Gislaine I. Manetta; Juliana D. Dias; et al. (Journal of Biogeography, 2021)
Aim Evaluating how groups of organisms vary in dispersal capability and how environmental, spatial and temporal signals vary across multiple scales is critical to elucidating metacommunity theory. We examined whether the relative contributions of environmental, spatial and hydrological factors have different effects on organismal groups with different dispersal abilities at three spatial scales, and how this knowledge contributes to our understanding of metacommunity dynamics. Location Four major Brazilian floodplains, with the largest distance among them of 2,300 Km. Taxon 10 aquatic organismal groups, ranging from bacterioplankton to fish. Methods We sampled lakes connected to the main river in the low‐ and high‐water periods of each floodplain between 2011 and 2012. Different biological groups were analysed across three hierarchical spatial scales (fine, intermediate and subcontinental) within and between floodplain systems. We applied a series of partial redundancy analyses to estimate the relative contributions of environmental factors, spatial factors and hydrological period for each biological group. Results At the fine spatial scale, predominantly environmental factors and hydrological period structure metacommunities, although less so for microorganisms than for micro‐invertebrates and macro‐organisms. The relative importance of environmental factors increased at the intermediate spatial scale. At the subcontinental scale, the relative importance of spatial factors increased for all biological groups, but environmental factors remained the primary regulators of microorganisms even at the largest scale. Main conclusions This study design allowed us to make more robust inferences about the mechanisms responsible for regulating community structure of distinct biological groups at different spatial scales. Our results suggest that biological groups displaying distinct body size likely determine the spatial extent at which environmental, spatial and hydrological processes prevail as the primary regulators of community structure. These findings are important in guiding the conservation and management of floodplain biodiversity because these systems are naturally highly heterogeneous in space and time.

Feeding behavior of feedlot-finished crossbred bulls fed palm kernel cake - Mateus de M. Lisboa; Robério R. Silva; Fabiano F. da Silva; Maria M. S. Pereira; Gabriel D. Costa; Fabrício B. L. Mendes; Sinvaldo O. de Souza; Marceliana da C. Santos; Laoan B. O. Rodrigues; Henry D. R. Alba; Gleidson G. P. de Carvalho (Tropical Animal Health and Production, 2021)

The usefulness of Olanzapine plasma concentrations in monitoring treatment efficacy and metabolic disturbances in first-episode psychosis - J. A. Arnaiz; C. Rodrigues-Silva; G. Mezquida; S. Amoretti; M. J. Cuesta; D. Fraguas; A. Lobo; A. González-Pinto; M. C. Díaz-Caneja; I. Corripio; E. Vieta; I. Baeza; et al. (Psychopharmacology, 2021)

COVID-19-Associated Histoplasmosis in an AIDS Patient - Rossana Patricia Basso; Vanice Rodrigues Poester; Jéssica Louise Benelli; David A. Stevens; Heruza Einsfeld Zogbi; Izadora Clezar da S. Vasconcellos; Alessandro Comarú Pasqualotto; Melissa Orzechowski Xavier (Mycopathologia, 2021)

Ursolic acid abrogates depressive-like behavior and hippocampal pro-apoptotic imbalance induced by chronic unpredictable stress - André R. S. Colla; Francis L. Pazini; Vicente Lieberknecht; Anderson Camargo; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2021)

The CORDEX Flagship Pilot Study in southeastern South America: a comparative study of statistical and dynamical downscaling models in simulating daily extreme precipitation events - M. L. Bettolli; S. A. Solman; R. P. da Rocha; M. Llopart; J. M. Gutierrez; J. Fernández; M. E. Olmo; A. Lavin-Gullon; S. C. Chou; D. Carneiro Rodrigues; E. Coppola; R. Balmaceda Huarte; et al. (Climate Dynamics, 2021)

Physical exercise prevents amyloid β1−40-induced disturbances in NLRP3 inflammasome pathway in the hippocampus of mice - Julia M. Rosa; Anderson Camargo; Ingrid A. V. Wolin; Manuella P. Kaster; Ana Lúcia S. Rodrigues (Metabolic Brain Disease, 2021)

Administration of branched-chain amino acids alters epigenetic regulatory enzymes in an animal model of Maple Syrup Urine Disease - Emilio L. Streck; Felipe P. Bussular; Leticia B. Wessler; Mariane B. Duarte; Victoria L. Rezende; Matheus S. Rodrigues; Carolina A. Torres; Isabela S. Lemos; Gabriela Candiotto; Fernanda F. Gava; Jade de Oliveira; Samira S. Valvassori (Metabolic Brain Disease, 2021)

Association between exposure to air pollution during intrauterine life and cephalic circumference of the newborn - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R. D. M. Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Environmental Science and Pollution Research, 2021)

Industrial wastewater treatment using a bubble photo-Fenton reactor with continuous gas supply - Emanuel F. S. Sampaio; Carmen S. D. Rodrigues; Vanessa N. Lima; Luis M. Madeira (Environmental Science and Pollution Research, 2021)

Purification of arsenic-contaminated water using iron molybdate filters and monitoring of their genotoxic, mutagenic, and cytotoxic effects through bioassays - Rodrigo C. Hott; Thainá S. Magalhães; Luiz F. O. Maia; Kallel S. F. Santos; Guilherme L. Rodrigues; Luiz C. A. Oliveira; Márcio C. Pereira; Márcia C. S. Faria; Alessandra P. Carli; Caio C. Souza Alves; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2021)

Seasonal variation in photosynthetic rates and satellite-based GPP estimation over mangrove forest - N. Lele; M. K. Kripa; M. Panda; S. K. Das; A. Hari Nivas; N. Divakaran; S. Naik-Gaonkar; A. Sawant; A. K. Pattnaik; R. N. Samal; T. Thangaradjou; A. Saravanakumar; et al. (Environmental Monitoring and Assessment, 2021)

First record on mercury accumulation in mice brain living in active volcanic environments: a cytochemical approach - A. Navarro-Sempere; Y. Segovia; A. S. Rodrigues; P. V. Garcia; R. Camarinho; M. García (Environmental Geochemistry and Health, 2021)

Marine Heatwaves, Sewage and Eutrophication Combine to Trigger Deoxygenation and Biodiversity Loss: A SW Atlantic Case Study - Kalina M. Brauko; Alex Cabral; Natasha V. Costa; Juliana Hayden; Carlos E. P. Dias; Edilene S. Leite; Renan D. Westphal; Carolina M. Mueller; Jason M. Hall-Spencer; Regina R. Rodrigues; Leonardo R. Rörig; Paulo R. Pagliosa; et al. (Frontiers in Marine Science, 2020)
Marine heatwaves (MHWs) are a major concern worldwide due to their increasing impacts in recent years, and these extreme events may trigger deoxygenation of coastal waters affected by sewage and eutrophication. Here we investigate the combined effects of MHWs and nutrient enrichment on the water quality and biodiversity of the Bay of Santa Catarina Island (Brazil). We used historical (1994–2020) sea surface temperature data from satellites and in situ physical, chemical and biological parameters to assess temporal trends. Oxygen levels have been decreasing whilst phosphorus levels have been increasing in the bay. During the austral summer of 2020 a regional sea surface heatwave was detected by satellite, lasting for 9 days and coinciding with our research cruise. During this period, seawater temperatures reached 29.8°C and anoxia was detected for the first time in the bay. A decrease in macrobenthic and phytoplankton community richness correlated with decreases in oxygen both through time and towards more urbanized areas. Overall, poor wastewater treatment is a key stressor that combined with MHWs to degrade coastal waters. Mitigation strategies are needed to minimize the impact of MHWs, including improved sewage treatment, restoration and conservation of wetlands and the use of nature-based technologies to promote coastal ecosystem recovery.

In vitro bioassay guided anti-dermatophyte and cytotoxic activities from Piper umbellatum L. Miq. led to 4-nerolidylcatechol - Jolindo A. Freitas; Rodrigo Sorrechia; Flávio A. S. Politi; André G. Santos; Edvânio R. Rodrigues; Lourdes C. Santos; Ana M. Fusco-Almeida; Andrew A. Oliveira; Rafael V. C. Guido; Rosemeire C. L. R. Pietro (Natural Product Research, 2020)

Violacein antimicrobial activity on Staphylococcus epidermidis biofilm - H. V. Dodou; A. H. M. Batista; S. C. Medeiros; G. W. P. Sales; M. L. Rodrigues; P. I. O. Pereira; P. C. N. Nogueira; E. R. Silveira; T. B. Grangeiro; N. A. P. Nogueira (Natural Product Research, 2020)

Does leaf flushing in the dry season affect leaf traits and herbivory in a tropical dry forest? - Jhonathan O. Silva; Mário M. Espírito-Santo; Joselândio C. Santos; Priscyla M. S. Rodrigues (The Science of Nature, 2020)

A copper(II)-binding triazole derivative with ionophore properties is active against Candida spp. - A. Gaspar-Cordeiro; S. da Silva; M. Aguiar; C. Rodrigues-Pousada; H. Haas; L. M. P. Lima; C. Pimentel (JBIC Journal of Biological Inorganic Chemistry, 2020)

Recent advances on anaerobic digestion of swine wastewater - G. Lourinho; L. F. T. G. Rodrigues; P. S. D. Brito (International Journal of Environmental Science and Technology, 2020)

Muscle temperature kinetics and thermoregulatory responses to 42 °C hot-water immersion in healthy males and females - Patrick Rodrigues; Gabriel S. Trajano; Lee Wharton; Geoffrey M. Minett (European Journal of Applied Physiology, 2020)

Mitoxantrone impairs proteasome activity and prompts early energetic and proteomic changes in HL-1 cardiomyocytes at clinically relevant concentrations - Vera Marisa Costa; João Paulo Capela; Joana R. Sousa; Rute P. Eleutério; Patrícia R. S. Rodrigues; José Luís Dores-Sousa; Rui A. Carvalho; Maria Lourdes Bastos; José Alberto Duarte; Fernando Remião; M. Gabriela Almeida; Kurt J. Varner; et al. (Archives of Toxicology, 2020)

Characterization, antibacterial activity and antibiotic modifying action of the Caryocar coriaceum Wittm. pulp and almond fixed oil - Fladson F.G. Pereira; Maria K. S. B. Feitosa; Maria do S. Costa; Saulo R. Tintino; Fábio F.G. Rodrigues; Irwin R. A. Menezes; Henrique D. M. Coutinho; José G.M. da Costa; Erlânio O. de Sousa (Natural Product Research, 2020)

Molecular Inferences on Scomberomorus brasiliensis, From the Western South Atlantic, Based on Two Mitochondrial Genes - Divino B. da Cunha; Luis Fernando S. Rodrigues-Filho; João Braúllio de Luna Sales; Pericles Rêgo; Cleonilde Queiroz; Iracilda Sampaio; Marcelo Vallinoto (Frontiers in Marine Science, 2020)

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

Adsorption of amoxicillin onto high surface area–activated carbons based on olive biomass: kinetic and equilibrium studies - Daniel Lucas Costa Rodrigues; Fernando Machado Machado; Alice Gonçalves Osório; Cristiane Ferraz de Azevedo; Eder Claudio Lima; Raphaelle S. da Silva; Diana Ramos Lima; Fernanda Medeiros Gonçalves (Environmental Science and Pollution Research, 2020)

Formaldehyde effects on kanamycin resistance gene of inactivated recombinant Escherichia coli vaccines - Rafael A. Donassolo; Marcos Roberto A. Ferreira; Clóvis Moreira Jr; Lucas M. dos Santos; Emili Griep; Gustavo M. S. G. Moreira; Rafael R. Rodrigues; Ângela N. Moreira; Fabricio R. Conceição (Biotechnology Letters, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

The involvement of GABAergic system in the antidepressant-like effect of agmatine - Vivian Binder Neis; Axel Fogaça Rosado; Gislaine Olescowicz; Morgana Moretti; Priscila Batista Rosa; Nicole Platt; Ana Lúcia S. Rodrigues (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Gonadal remodeling and hormonal regulation during sex change of juvenile dusky grouper Epinephelus marginatus (Teleostei, Serranidae), an endangered protogynous hermaphrodite fish - J. A. Rodrigues-Filho; C. E. O. Garcia; C. G. Chehade; E. G. Sanches; M. I. Borella; F. L. Lo Nostro; B. C. Araújo; G. S. Branco; R. G. Moreira (Fish Physiology and Biochemistry, 2020)

Association between maternal exposure to air pollution before conception and sex determination in the city of São Paulo - Mariana Azevedo Carvalho; Karen Hettfleisch; Agatha S Rodrigues; Alexandra Benachi; Sandra Elisabete Vieira; Silvia R D M Saldiva; Paulo Hilário N. Saldiva; Rossana Pulcineli Vieira Francisco; Lisandra Stein Bernardes (Air Quality, Atmosphere & Health, 2020)

Sugarcane Juice with Co-encapsulated Bifidobacterium animalis subsp. lactis BLC1 and Proanthocyanidin-Rich Cinnamon Extract - Augusto Tasch Holkem; Edmur José Santos Neto; Megumi Nakayama; Clitor J. F. Souza; Marcelo Thomazini; Fabio Augusto Gallo; Marluci Palazzolli da Silva; Laura de Queiroz Bomdespacho; Carla Giovana Luciano; Izabel Cristina Freitas Moraes; Rodrigo Rodrigues Petrus; Carmen S. Favaro-Trindade (Probiotics and Antimicrobial Proteins, 2020)

SERK genes identification and expression analysis during somatic embryogenesis and sporogenesis of sexual and apomictic Brachiaria brizantha (Syn. Urochloa brizantha) - Andréa D. Koehler; André S. T. Irsigler; Vera T. C. Carneiro; Glaucia B. Cabral; Júlio C. M. Rodrigues; Ana Cristina M. M. Gomes; Roberto C. Togawa; Marcos M. C. Costa; Adriana Pinheiro Martinelli; Diva Maria de Alencar Dusi (Planta, 2020)

Effect of Biochar on Emission of Greenhouse Gases and Productivity of Cardoon Crop (Cynara cardunculus L.) - Paulo Barracosa; Isabel Cardoso; Francisco Marques; António Pinto; Jorge Oliveira; Henrique Trindade; Pedro Rodrigues; José L. S. Pereira (Journal of Soil Science and Plant Nutrition, 2020)

Confocal microscopy provides visual evidence and confirms the feasibility of dsRNA delivery to emerald ash borer through plant tissues - Flavia Pampolini; Thais B. Rodrigues; Ramya S. Leelesh; Tomokazu Kawashima; Lynne K. Rieske (Journal of Pest Science, 2020)
Double-stranded RNA (dsRNA)-mediated gene silencing, or RNA interference (RNAi), is an emerging biotechnology that has been a breakthrough tool for crop protection. Exogenous dsRNA triggers the RNAi pathway, silences genes, disrupts protein function, and can cause insect mortality. However, effective delivery of the dsRNA is problematic, particularly in systems with long-lived, endophagous insects such as the emerald ash borer (EAB), Agrilus planipennis , a tree-killing nonnative invader that attacks ash, Fraxinus spp. Larvae feed on cambial tissue causing rapid tree death. EAB is susceptible to RNAi, but we lack a practical means of delivery. Here we evaluated delivery of dsRNA to green, F. pennsylvanica , and tropical ash, F. uhdei , through root and/or petiole absorption, and also demonstrated dsRNA absorption through the EAB egg chorion. We labeled exogenous dsRNA using a fluorescing label and then used confocal microscopy and RT-qPCR to evaluate its distribution in plant and insect tissues. Labeled dsRNAs are detectable in root, stem, and leaf tissues 48-h postapplication. In excised ash branches, labeled dsRNA is detectable in the inner bark and in recovered EAB neonates 8-day postapplication. Eggs and larvae emerging from treated eggs also presented fluorescing dsRNA under confocal imaging. Adult EAB-fed tropical ash leaves treated with in vitro synthesized EAB-specific dsSHI through petiole absorption experience a significant knockdown of the shi gene and a significant mortality. Our findings provide a proof of concept that delivery of dsRNAs through topical or systemic application methods is a feasible means of suppressing EAB, providing hope for future tree protection.

The Evolution of the Maxillary Canal in Probainognathia (Cynodontia, Synapsida): Reassessment of the Homology of the Infraorbital Foramen in Mammalian Ancestors - Julien Benoit; Irina Ruf; Juri A. Miyamae; Vincent Fernandez; Pablo Gusmão Rodrigues; Bruce S. Rubidge (Journal of Mammalian Evolution, 2020)

Protective Effects of Agmatine Against Corticosterone-Induced Impairment on Hippocampal mTOR Signaling and Cell Death - Gislaine Olescowicz; Tuane B. Sampaio; Cristine de Paula Nascimento-Castro; Patricia S. Brocardo; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Neurotoxicity Research, 2020)

Micropropagation, encapsulation, and conservation of Decalepis salicifolia, a vanillin isomer containing medicinal and aromatic plant - Vereena Rodrigues; Amit Kumar; Sivaraman Gokul; Ram S. Verma; Laiq ur Rahman; Velusamy Sundaresan (In Vitro Cellular & Developmental Biology - Plant, 2020)

Evaluation of gully development over several years using GIS and fractal analysis: a case study of the Palmital watershed, Minas Gerais (Brazil) - L. S. C. Real; S. Crestana; R. R. M. Ferreira; V. G. S. Rodrigues (Environmental Monitoring and Assessment, 2020)

PAH Profiles in Suspended Particulate Matter from an Urbanized River Within the Brazilian Amazon - L. C. Sousa; C. C. S. Rodrigues; R. A. Mendes; J. A. M. Corrêa (Bulletin of Environmental Contamination and Toxicology, 2020)

P2X7 siRNA targeted to the kidneys increases klotho and delays the progression of experimental diabetic nephropathy - A. M. Rodrigues; R. S. Serralha; D. Y. Lima; G. R. Punaro; I. Visona; M. J. S. Fernandes; E. M. S. Higa (Purinergic Signalling, 2020)

Entomopathogenic Viruses in the Neotropics: Current Status and Recently Discovered Species - D R Sosa-Gómez; F S Morgado; R F T Corrêa; L A Silva; D M P Ardisson-Araújo; B M P Rodrigues; E E Oliveira; R W S Aguiar; B M Ribeiro (Neotropical Entomology, 2020)

Natural Enemies of the Harrisia Cactus Mealybug and Other Hypogeococcus Species (Hemiptera: Pseudococcidae) in Puerto Rico: Identification and Taxonomic Notes on Primary and Secondary Parasitoids - S. V. Triapitsyn; S. D. Hight; G. A. Logarzo; M. B. Aguirre; J. C. Verle Rodrigues; V. A. Trjapitzin; Z. Rivera Ocasio; M. L. Rivera-Vázquez; M. J. West Ortiz; Y. Rodríguez Reyes (Neotropical Entomology, 2020)

Cytotoxic Effect of Prodigiosin, Natural Red Pigment, Isolated from Serratia marcescens UFPEDA 398 - J. C. L. Lapenda; V. P. Alves; M. L. Adam; M. D. Rodrigues; S. C. Nascimento (Indian Journal of Microbiology, 2020)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

Population Genetics Coupled Chemical Profiling for Conservation Implications of Decalepis salicifolia (Bedd. ex Hook.f.) Venter, an Endemic and Critically Endangered Species of Western Ghats, India - Sivaraman Gokul; Vereena Rodrigues; Amit Kumar; Ram S. Verma; Ashutosh K. Shukla; Velusamy Sundaresan (Biochemical Genetics, 2020)

Assessing ecological function in the context of species recovery - H. Resit Akçakaya; Ana S. L. Rodrigues; David A. Keith; E. J. Milner‐Gulland; Eric W. Sanderson; Simon Hedges; David P. Mallon; Molly K. Grace; Barney Long; Erik Meijaard; P. J. Stephenson (Conservation Biology, 2020)
Species interactions matter to conservation. Setting an ambitious recovery target for a species requires considering the size, density, and demographic structure of its populations such that they fulfill the interactions, roles, and functions of the species in the ecosystems in which they are embedded. A recently proposed framework for an International Union for Conservation of Nature Green List of Species formalizes this requirement by defining a fully recovered species in terms of representation, viability, and functionality. Defining and quantifying ecological function from the viewpoint of species recovery is challenging in concept and application, but also an opportunity to insert ecological theory into conservation practice. We propose 2 complementary approaches to assessing a species’ ecological functions: confirmation (listing interactions of the species, identifying ecological processes and other species involved in these interactions, and quantifying the extent to which the species contributes to the identified ecological process) and elimination (inferring functionality by ruling out symptoms of reduced functionality, analogous to the red‐list approach that focuses on symptoms of reduced viability). Despite the challenges, incorporation of functionality into species recovery planning is possible in most cases and it is essential to a conservation vision that goes beyond preventing extinctions and aims to restore a species to levels beyond what is required for its viability. This vision focuses on conservation and recovery at the species level and sees species as embedded in ecosystems, influencing and being influenced by the processes in those ecosystems. Thus, it connects and integrates conservation at the species and ecosystem levels.

Clindamycin inhibits nociceptive response by reducing tumor necrosis factor-α and CXCL-1 production and activating opioidergic mechanisms - Felipe F. Rodrigues; Marcela I. Morais; Ivo S. F. Melo; Paulo S. A. Augusto; Marcela M. G. B. Dutra; Sarah O. A. M. Costa; Fábio C. Costa; Franciele A. Goulart; Alysson V. Braga; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2020)

Tree diversity and above-ground biomass in the South America Cerrado biome and their conservation implications - Paulo S. Morandi; Beatriz Schwantes Marimon; Ben Hur Marimon-Junior; James A. Ratter; Ted R. Feldpausch; Guarino Rinaldi Colli; Cássia Beatriz Rodrigues Munhoz; Manoel Cláudio da Silva Júnior; Edson de Souza Lima; Ricardo Flores Haidar; Luzmila Arroyo; Alejandro Araujo Murakami; et al. (Biodiversity and Conservation, 2020)

The Galactose-Binding Lectin Isolated from Vatairea macrocarpa Seeds Enhances the Effect of Antibiotics Against Staphylococcus aureus–Resistant Strain - Valdenice F. Santos; Maria S. Costa; Fábia F. Campina; Renato R. Rodrigues; Ana L. E. Santos; Felipe M. Pereira; Karla L. R. Batista; Rafael C. Silva; Raquel O. Pereira; Bruno A. M. Rocha; Henrique D. M. Coutinho; Claudener S. Teixeira (Probiotics and Antimicrobial Proteins, 2020)

Brazil's vegetation ravage may be encouraged by law - Gustavo H. Zaia Alves; Raffael M. Tófoli; Jorge L. Rodrigues-Filho; Patricia A. Sacramento; Vivian M. Cionek; Bruno R. S. Figueiredo; Edivando Vitor do Couto (Biodiversity and Conservation, 2020)

Metacommunity organization in an intermittent river in Brazil: the importance of riverine networks for regional biodiversity - Carlos A. S. Rodrigues-Filho; Ronaldo C. Gurgel-Lourenço; Eliêta A. Ramos; José L. C. Novaes; Danielle S. Garcez; Rodrigo S. Costa; Jorge I. Sánchez-Botero (Aquatic Ecology, 2020)

Lethal and Sub-lethal Effects of Nitrofurantoin on Zebrafish Early-Life Stages - Reginaldo Carlyle Silva de Oliveira; Rhaul Oliveira; Maria Augusta Carvalho Rodrigues; Natália Oliveira de Farias; Diego Sousa-Moura; Nilma Almeida Nunes; Thayres S. Andrade; Cesar Koppe Grisolia (Water, Air, & Soil Pollution, 2020)

Natural Vs Managed Habitat: Effect Over the Seed-Predator Pachymerus nucleorum and Its Natural Enemies - J O S Silva; M L E Costa; B S Paixão; J D B Macêdo; P M S Rodrigues; E M F Lins-Neto (Neotropical Entomology, 2020)

Lawsone, a 2-hydroxy-1,4-naphthoquinone from Lawsonia inermis (henna), produces mitochondrial dysfunctions and triggers mitophagy in Saccharomyces cerevisiae - Mariana Rodrigues Xavier; Manuella Maria Silva Santos; Maise Gomes Queiroz; Mariza S. de Lima Silva; Alexandre José S. Goes; Marcos Antonio De Morais Jr (Molecular Biology Reports, 2020)

Increased Mmp/Reck Expression Ratio Is Associated with Increased Recognition Memory Performance in a Parkinson’s Disease Animal Model - Adauto Spindola; Adriano D. S. Targa; Lais Soares Rodrigues; Sheila Maria Brochado Winnischofer; Marcelo M. S. Lima; Mari Cleide Sogayar; Marina Trombetta-Lima (Molecular Neurobiology, 2020)

Thiamine, riboflavin, and nicotinamide inhibit paclitaxel-induced allodynia by reducing TNF-α and CXCL-1 in dorsal root ganglia and thalamus and activating ATP-sensitive potassium channels - Alysson V. Braga; Sarah O. A. M. Costa; Felipe F. Rodrigues; Ivo S. F. Melo; Marcela I. Morais; Márcio M. Coelho; Renes R. Machado (Inflammopharmacology, 2020)

Molecular characterization of a germplasm bank of Platonia insignis Mart.: a fruit tree - D. N. Pena; E. F. Moura; S. M. Rodrigues; M. S. P. Oliveira; J. P. Sanches; M. F. Moura (Genetic Resources and Crop Evolution, 2020)

Detection of Zika virus in paired urine and amniotic fluid samples from symptomatic and asymptomatic women and their babies during a disease outbreak: association with neurological symptoms in newborns - Danila Vedovello; Steven S. Witkin; Andrea Cristina Botelho Silva; Thamirys Cosmo Gillo Fajardo; Alexandra Siqueira Mello; Ana Paula Antunes Pascalicchio Bertozzi; Alify Bertoldo da Silva; Nemésio Florence Vieira Filho; Maria Manoela Duarte Rodrigues; Rosa Estela Gazeta; Antônio Fernandes Moron; Stéphanno Gomes Pereira Sarmento; et al. (Journal of NeuroVirology, 2020)
Paired maternal and newborn urine and amniotic fluid from 138 subjects collected during a Zika virus (ZIKV) outbreak was analyzed for ZIKV by gene amplification (RT-qPCR), and the findings were correlated with clinical symptoms and neurological anomalies in the babies. ZIKV was detected in 1 of 9 symptomatic women (11.1%) and in 19 of 129 asymptomatic women (14.7%). Neurological manifestations were present in 19 babies (13.7%), 10 of 20 (50%) positive and 9 of 119 (7.6%) negative ( p < 0.001) for ZIKV. Twelve (8.6%) urines collected during gestation were ZIKV-positive; only 2 remained positive for ZIKV postpartum. Six (4.1%) newborn urines collected within 1 day of delivery were ZIKV-positive cases. In 3 of these cases, ZIKV was detected in mother’s urine pre- and postpartum and in both mother’s urine and babies’ urine. Four of the amniotic fluid samples (2.9%) were ZIKV-positive. Among ZIKV-negative babies with neurological sequel, 87.5% were female; in contrast, 72.7% ZIKV-positive babies with neurological abnormalities were male ( p = 0.019). We conclude that during a ZIKV outbreak, clinical symptoms and ZIKV detection in biological fluids are poor predictors of infection and adverse neurologic sequel in newborns.

Effects of cholecalciferol on behavior and production of reactive oxygen species in female mice subjected to corticosterone-induced model of depression - Suene Vanessa da Silva Souza; Priscila Batista da Rosa; Vivian Binder Neis; Júlia Dubois Moreira; Ana Lúcia S. Rodrigues; Morgana Moretti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The antidepressant-like effect of guanosine is dependent on GSK-3β inhibition and activation of MAPK/ERK and Nrf2/heme oxygenase-1 signaling pathways - Priscila B. Rosa; Luis E. B. Bettio; Vivian B. Neis; Morgana Moretti; Isabel Werle; Rodrigo B. Leal; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2019)

The Fitness and Economic Benefits of Rearing the Parasitoid Telenomus podisi Under Fluctuating Temperature Regime - N L Castellanos; A F Bueno; K Haddi; E C Silveira; H S Rodrigues; E Hirose; G Smagghe; E E Oliveira (Neotropical Entomology, 2019)

A novel homozygous RTEL1 variant in a consanguineous Lebanese family: phenotypic heterogeneity and disease anticipation - Fernanda Gutierrez-Rodrigues; Nohad Masri; Eliane Chouery; Carrie Diamond; Nadine Jalkh; Alana Vicente; Sachiko Kajigaya; Fayez Abillama; Noha Bejjani; Wassim Serhal; Rodrigo T. Calado; Neal S. Young; et al. (Human Genetics, 2019)

Calibration and combination of monthly near-surface temperature and precipitation predictions over Europe - Luis R. L. Rodrigues; Francisco J. Doblas-Reyes; Caio A. S. Coelho (Climate Dynamics, 2019)

Antibacterial activity of silver/reduced graphene oxide nanocomposite synthesized by sustainable process - Raynara M. S. Jacovone; Jaqueline J. S. Soares; Thainá S. Sousa; Flávia R. O. Silva; Rafael H. L. Garcia; Hang N. Nguyen; Debora F. Rodrigues; Solange K. Sakata (Energy, Ecology and Environment, 2019)

Synthesis, structural characterization, and cytotoxic evaluation of chalcone derivatives - Paulo N. Bandeira; Telma L. G. Lemos; Hélcio S. Santos; Mylena C. S. de Carvalho; Daniel P. Pinheiro; Manoel O. de Moraes Filho; Cláudia Pessoa; Francisco W. A. Barros-Nepomuceno; Tigressa H. S. Rodrigues; Paulo R. V. Ribeiro; Herbert S. Magalhães; Alexandre M. R. Teixeira (Medicinal Chemistry Research, 2019)

Testing main Amazonian rivers as barriers across time and space within widespread taxa - Renata M. Pirani; Fernanda P. Werneck; Andréa T. Thomaz; Mariah L. Kenney; Marcelo J. Sturaro; Teresa C. S. Ávila‐Pires; Pedro L. V. Peloso; Miguel T. Rodrigues; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Present Amazonian diversity patterns can result from many different mechanisms and, consequently, the factors contributing to divergence across regions and/or taxa may differ. Nevertheless, the river‐barrier hypothesis is still widely invoked as a causal process in divergence of Amazonian species. Here we use model‐based phylogeographic analyses to test the extent to which major Amazonian rivers act similarly as barriers across time and space in two broadly distributed Amazonian taxa. Local Amazon rain forest. Taxon The lizard Gonatodes humeralis (Sphaerodactylidae) and the tree frog Dendropsophus leucophyllatus (Hylidae). Methods We obtained RADseq data for samples distributed across main river barriers, representing main Areas of Endemism previously proposed for the region. We conduct model‐based phylogeographic and genetic differentiation analyses across each population pair. Results Measures of genetic differentiation (based on F ST calculated from genomic data) show that all rivers are associated with significant genetic differentiation. Parameters estimated under investigated divergence models showed that divergence times for populations separated by each of the 11 bordering rivers were all fairly recent. The degree of differentiation consistently varied between taxa and among rivers, which is not an artifact of any corresponding difference in the genetic diversities of the respective taxa, or to amounts of migration based on analyses of the site‐frequency spectrum. Main conclusions Taken together, our results support a dispersal (rather than vicariance) history, without strong evidence of congruence between these species and rivers. However, once a species crossed a river, populations separated by each and every river have remained isolated—in this sense, rivers act similarly as barriers to any further gene flow. This result suggests differing degrees of persistence and gives rise to the seeming contradiction that the divergence process indeed varies across time, space and species, even though major Amazonian rivers have acted as secondary barriers to gene flow in the focal taxa.

Diversity, genetic structure, and population genomics of the tropical tree Centrolobium tomentosum in remnant and restored Atlantic forests - Erick M. G. Cordeiro; Camila Menezes Macrini; Patricia Sanae Sujii; Kaiser Dias Schwarcz; José Baldin Pinheiro; Ricardo Ribeiro Rodrigues; Pedro H. S. Brancalion; Maria I. Zucchi (Conservation Genetics, 2019)

Defining the indigenous ranges of species to account for geographic and taxonomic variation in the history of human impacts: reply to Sanderson 2019 - P. J. Stephenson; Molly K. Grace; H. Resit Akçakaya; Ana S. L. Rodrigues; Barney Long; David P. Mallon; Erik Meijaard; Jon Paul Rodriguez; Richard P. Young; Thomas M. Brooks; Craig Hilton‐Taylor (Conservation Biology, 2019)

Relative importance of host and plant semiochemicals in the foraging behavior of Trichogramma achaeae, an egg parasitoid of Tuta absoluta - Lessando Gontijo; Pasquale Cascone; Massimo Giorgini; Marco Michelozzi; Hígor S. Rodrigues; Giuseppe Spiezia; Luigi Iodice; Emilio Guerrieri (Journal of Pest Science, 2019)

Distribution of Distances Between Symmetric Words in the Human Genome: Analysis of Regular Peaks - Carlos A. C. Bastos; Vera Afreixo; João M. O. S. Rodrigues; Armando J. Pinho; Raquel M. Silva (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Isachneburchellii (Poaceae, Micrairoideae) from Rio de Janeiro, Brazil – an endemic new species segregated from Isachne goiasensis - Rodrigo S. Rodrigues; Tarciso S. Filgueiras (Brittonia, 2019)

Ecophysiology of mesophotic reef‐building corals in Hawai‘i is influenced by symbiont–host associations, photoacclimatization, trophic plasticity, and adaptation - Jacqueline L. Padilla‐Gamiño; Melissa S. Roth; Lisa J. Rodrigues; Christina J. Bradley; Robert R. Bidigare; Ruth D. Gates; Celia M. Smith; Heather L. Spalding (Limnology and Oceanography, 2019)
Mesophotic reef corals remain largely unexplored in terms of the genetic adaptations and physiological mechanisms to acquire, allocate, and use energy for survival and reproduction. In the Hawaiian Archipelago, the Leptoseris species complex form the most spatially extensive mesophotic coral ecosystem known and provide habitat for a unique community. To study how the ecophysiology of Leptoseris species relates to symbiont–host specialization and understand the mechanisms responsible for coral energy acquisition in extreme low light environments, we examined Symbiodinium (endosymbiotic dinoflagellate) photobiological characteristics and the lipids and isotopic signatures from Symbiodinium and coral hosts over a depth‐dependent light gradient (55–7 μ mol photons m −2 s −1 , 60–132 m). Clear performance differences demonstrate different photoadaptation and photoacclimatization across this genus. Our results also show that flexibility in photoacclimatization depends primarily on Symbiodinium type. Colonies harboring Symbiodinium sp. COI‐2 showed significant increases in photosynthetic pigment content with increasing depth, whereas colonies harboring Symbiodinium spp. COI‐1 and COI‐3 showed variability in pigment composition, yield measurements for photosystem II, as well as size and density of Symbiodinium cells. Despite remarkable differences in photosynthetic adaptive strategies, there were no significant differences among lipids of Leptoseris species with depth. Finally, isotopic signatures of both host and Symbiodinium changed with depth, indicating that coral colonies acquired energy from different sources depending on depth. This study highlights the complexity in physiological adaptations within this symbiosis and the different strategies used by closely related mesophotic species to diversify energy acquisition and to successfully establish and compete in extreme light‐limited environments.

Generation and validation of genetic markers for the selection of carioca dry bean genotypes with the slow-darkening seed coat trait - Renata C. Alvares; Robert Stonehouse; Thiago L. P. O. Souza; Patrícia G. S. Melo; Phillip N. Miklas; Kirstin E. Bett; Leonardo C. Melo; Luana A. Rodrigues; Lorena L. Souza; Helton S. Pereira (Euphytica, 2019)

Occurrence and Environmental Distribution of 5 UV Filters During the Summer Season in Different Water Bodies - S. K. Fagervold; A. S. Rodrigues; C. Rohée; R. Roe; M. Bourrain; D. Stien; P. Lebaron (Water, Air, & Soil Pollution, 2019)

A commonly occurring genetic variant within the NPLOC4–TSPAN10–PDE6G gene cluster is associated with the risk of strabismus - Denis Plotnikov; Rupal L. Shah; Jamille N. Rodrigues; Phillippa M. Cumberland; Jugnoo S. Rahi; Pirro G. Hysi; Denize Atan; Cathy Williams; Jeremy A. Guggenheim (Human Genetics, 2019)

Whistle variability of Guiana dolphins in South America: Latitudinal variation or acoustic adaptation? - Juliana Rodrigues Moron; Nara Pavan Lopes; Sarah Stutz Reis; Natália Mamede; Suzana Stutz Reis; Gustavo Toledo; Gilberto Corso; Renata S. Sousa‐lima; Artur Andriolo (Marine Mammal Science, 2019)
A previous comparison of whistles using data sampled at 48 kHz suggested that certain frequency parameters vary along a latitudinal gradient. This geographical pattern may be biased because whistles sampled at higher frequencies could potentially have very different frequency contents. The current study compared the acoustic parameters of Guiana dolphin ( Sotalia guianensis ) whistles recorded at a higher sampling rate (96 kHz) and from groups occupying two never before sampled sites, Benevente Bay, Espírito Santo, Brazil, and Formosa Bay, Rio Grande do Norte, Brazil, with recordings of other populations in South America. By only considering data sampled at a rate of at least 96 kHz, we aimed to detect differences in whistles across locations. Contrary to previous findings, our analyses do not indicate any clear separation between northern and southern populations based on whistles, and do not corroborate the hypothesis of latitudinal acoustic variation in this species. The variation in Guiana dolphin whistle parameters found here appears to be influenced by latitude to some extent, but several other factors, including sampling method, environmental fluctuations, and social influence on vocal learning, may be confounding the detection of a geographic pattern in these whistle samples.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Photochemistry and hydric responses of congeneric Croton species at restoration sites under dry season: implications for species selection - Angélica L. Rodrigues; Angelo A. S. Bertholdi; Luís Paulo B. Mantoan; Gabriela M. Vasconcellos; Luiz Fernando R. Almeida (Theoretical and Experimental Plant Physiology, 2019)

Chemical Characterization and Biotechnological Applicability of Pigments Isolated from Antarctic Bacteria - Tiago R. Silva; Renata S. N. Tavares; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Iramaia A. Neri-Numa; Glaucia M. Pastore; Luiz H. Rosa; José A. A. Schultz; Hosana M. Debonsi; Lorena R. G. Cordeiro; Valeria M. Oliveira (Marine Biotechnology, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Progress on the phylogeny of the Omphalotaceae: Gymnopus s. str., Marasmiellus s. str., Paragymnopus gen. nov. and Pusillomyces gen. nov. - Jadson J. S. Oliveira; Ruby Vargas-Isla; Tiara S. Cabral; Doriane P. Rodrigues; Noemia K. Ishikawa (Mycological Progress, 2019)

Secretomic analysis of Beauveria bassiana related to cattle tick, Rhipicephalus microplus, infection - Lucélia Santi; Caio J. B. Coutinho-Rodrigues; Markus Berger; Lisete A. S. Klein; Eduardo M. De Souza; Rafael L. Rosa; Jorge A. Guimarães; John R. Yates; Wendell M. S. Perinotto; Vânia R. E. P. Bittencourt; Walter O. Beys-da-Silva (Folia Microbiologica, 2019)

Geostatistical stationary space-time covariance functions modeling of Yellow Sigatoka progress in banana crop - J. D. P. Rodrigues; M. C. Alves; A. S. Freitas; E. A. Pozza; M. S. Oliveira; H. J. P. Alves (Australasian Plant Pathology, 2019)

Control of Non-migrating Bar Morphodynamics on Survival of Populus nigra Seedlings during Floods - C. L. Wintenberger; S. Rodrigues; S. Greulich; J. G. Bréhéret; P. Jugé; M. Tal; A. Dubois; M. Villar (Wetlands, 2019)

Levels of 25-hydroxyvitamin D3, biochemical parameters and symptoms of depression and anxiety in healthy individuals - Gleicilaine A. S. Casseb; Gabriela Ambrósio; Ana Lúcia S. Rodrigues; Manuella P. Kaster (Metabolic Brain Disease, 2019)

Pyrene degradation by marine-derived ascomycete: process optimization, toxicity, and metabolic analyses - Maria R. S. Vasconcelos; Gabriela A. L. Vieira; Igor V. R. Otero; Rafaella C. Bonugli-Santos; Marili V. N. Rodrigues; Vera L. G. Rehder; Milene Ferro; Sinésio Boaventura; Maurício Bacci; Lara D. Sette (Environmental Science and Pollution Research, 2019)

Chemical characterisation of the constituents of Eugenia protenta McVaugh and leishmanicidal activity of dimethylxanthoxylin - Flávio N. Sarges; Márcia M. Cascaes; Lienne S. Moraes; Giselle M. S. P. Guilhon; Edilene O. Silva; Maria das Graças B. Zoghbi; Eloisa H. A. Andrade; Ana Paula D. Rodrigues; Brenda F. Costa; Rayssa N. M. Figueiredo (Natural Product Research, 2019)

Correction to: Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. G. Coelho; G. V. Tolesano-Pascoli; V. S. Rodrigues; M. P. J. Szabó; V. N. Ramos (Tropical Animal Health and Production, 2019)

Effect of temperature on the thermal conductivity of a granite with high heat production from Central Portugal - M. M. Miranda; C. R. Matos; N. V. Rodrigues; A. J. S. C. Pereira; J. J. Costa (Journal of Iberian Geology, 2019)

Can Luminol Be a Fluorophore? - M. Fátima Barroso; Rui J. A. Silva; Sérgio F. Moreira; Sofia S. Rodrigues; Helena M. R. Gonçalves; Abel J. Duarte (Journal of Fluorescence, 2019)

Eucalyptus rust climatic risk as affected by topography and ENSO phenomenon - R. S. Nóia Júnior; F. Schwerz; J. L. Safanelli; J. C. Rodrigues; P. C. Sentelhas (Australasian Plant Pathology, 2019)

Pigments in an iridescent bacterium, Cellulophaga fucicola, isolated from Antarctica - Tiago R. Silva; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Fábio N. dos Santos; Marcos N. Eberlin; Iramaia A. Neri-Numa; Glaucia M. Pastore; Renata S. N. Tavares; Hosana M. Debonsi; Lorena R. G. Cordeiro; Luiz H. Rosa; et al. (Antonie van Leeuwenhoek, 2019)

Regulation of cell wall development in Brachypodium distachyon in vitro as affected by cytokinin and gas exchange - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; E. A. Fortini; A. C. F. Cruz; M. G. C. Costa; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Dopaminergic Lesion in the Olfactory Bulb Restores Olfaction and Induces Depressive-Like Behaviors in a 6-OHDA Model of Parkinson’s Disease - Jessica L. Ilkiw; Luana C. Kmita; Adriano D. S. Targa; Ana Carolina D. Noseda; Lais S. Rodrigues; Flávia W. C. Dorieux; Juliane Fagotti; Patrícia dos Santos; Marcelo M. S. Lima (Molecular Neurobiology, 2019)

Differences in food webs and trophic states of Brazilian tropical humid and semi-arid shallow lakes: implications of climate change - Rosemberg Fernandes Menezes; José Luiz Attayde; Sarian Kosten; Gissell Lacerot; Leonardo Coimbra e Souza; Luciana S. Costa; Leonel da S. L. Sternberg; Anna Claudia dos Santos; Michele de Medeiros Rodrigues; Erik Jeppesen (Hydrobiologia, 2019)

Biofilm Formation by Avian Pathogenic Escherichia coli is Not Related to In Vivo Pathogenicity - Suelle V. Rodrigues; Vanessa Laviniki; Karen A. Borges; Thales Q. Furian; Hamilton L. S. Moraes; Vladimir P. Nascimento; Carlos T. P. Salle (Current Microbiology, 2019)

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Crispoic acid, a new compound from Laelia marginata (Orchidaceae), and biological evaluations against parasites, human cancer cell lines and Zika virus - Andrezza C. Belloto; Gredson K. Souza; Paula C. Perin; Ivania T. A. Schuquel; Silvana M. O. Santin; Lucas U. R. Chiavelli; Francielle P. Garcia; Vanessa Kaplum; Jean H. S. Rodrigues; Débora B. Scariot; Rodrigo Delvecchio; Erik Machado-Ferreira; et al. (Natural Product Research, 2018)

Risk Assessment of the Drinking Water Samples in the Rural Area from MG, Brazil - Mayra S. Santos; Maria C. R. M. Metzker; Guilherme L. Rodrigues; Luis R. S. Corrêa; Mayne L. V. Silva; Ana L. G. Barbosa; Márcia C. S. Faria; Jairo L. Rodrigues (International Journal of Environmental Research, 2018)

Application of the Fenton’s process in a bubble column reactor for hydroquinone degradation - Vanessa N. Lima; Carmen S. D. Rodrigues; Luis M. Madeira (Environmental Science and Pollution Research, 2018)

Synthetic olive mill wastewater treatment by Fenton’s process in batch and continuous reactors operation - Bruno M. Esteves; Carmen S. D. Rodrigues; Luís M. Madeira (Environmental Science and Pollution Research, 2018)

Current advances in gibberellic acid (GA3) production, patented technologies and potential applications - Marcela C. Camara; Luciana P. S. Vandenberghe; Cristine Rodrigues; Juliana de Oliveira; Craig Faulds; Emmanuel Bertrand; Carlos R. Soccol (Planta, 2018)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Quantifying individual specialization using tracking data: a case study on two species of albatrosses - A.-S. Bonnet-Lebrun; R. A. Phillips; A. Manica; A. S. L. Rodrigues (Marine Biology, 2018)

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

Gaseous and liquid effluents treatment in bubble column reactors by advanced oxidation processes: A review - Vanessa N. Lima; Carmen S. D. Rodrigues; Ricardo A. C. Borges; Luis M. Madeira (Critical Reviews in Environmental Science and Technology, 2018)

Brain-Derived Neurotrophic Factor Prevents Depressive-Like Behaviors in Early-Symptomatic YAC128 Huntington’s Disease Mice - Victor Silva da Fonsêca; André R. da Silva Colla; Cristine de Paula Nascimento-Castro; Evelini Plácido; Julia Macedo Rosa; Marcelo Farina; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues; Patricia S. Brocardo (Molecular Neurobiology, 2018)

The Híbrido de Timor germplasm: identification of molecular diversity and resistance sources to coffee berry disease and leaf rust - R. A. Silva; L. Zambolim; I. S. L. Castro; H. S. Rodrigues; C. D. Cruz; E. T. Caixeta (Euphytica, 2018)

Targeting the mitochondrial VDAC in hepatocellular carcinoma using a polyclonal antibody-conjugated to a nitrosyl ruthenium complex - Loyanne C. B. Ramos; Fernando P. Rodrigues; Juliana C. Biazzotto; Sergio de Paula Machado; Leonardo D. Slep; Michael R. Hamblin; Roberto S. da Silva (JBIC Journal of Biological Inorganic Chemistry, 2018)

Validation of a robust LLE-GC-MS method for determination of trihalomethanes in environmental samples - Elton S. Franco; Válter L. Pádua; Alessandra Giani; Mariandry Rodríguez; Diego F. Silva; Ana F. A. Ferreira; Israel C. S. Júnior; Márcio C. Pereira; Jairo L. Rodrigues (Environmental Monitoring and Assessment, 2018)

Transcriptome analysis provides insights into the delayed sticky disease symptoms in Carica papaya - Johana Madroñero; Silas P. Rodrigues; Tathiana F. S. Antunes; Paolla M. V. Abreu; José A. Ventura; A. Alberto R. Fernandes; Patricia Machado Bueno Fernandes (Plant Cell Reports, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

P2X7 receptor and klotho expressions in diabetic nephropathy progression - A. M. Rodrigues; R. S. Serralha; C. Farias; G. R. Punaro; M. J. S. Fernandes; Elisa Mieko Suemitsu Higa (Purinergic Signalling, 2018)

Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - T. S. George; C. D. Giles; D. Menezes-Blackburn; L. M. Condron; A. C. Gama-Rodrigues; D. Jaisi; F. Lang; A. L. Neal; M. I. Stutter; D. S. Almeida; R. Bol; K. G. Cabugao; et al. (Plant and Soil, 2018)

Vulnerability associated with “symptoms similar to those of mercury poisoning” in communities from Xingu River, Amazon basin - Flávio Mnaoel Rodrigues Da Silva-Junior; Ritta M. Oleinski; Antonia E. S. Azevedo; Kátia C. M. C. Monroe; Marina Dos Santos; Tatiane Britto Da Silveira; Adrianne Maria Netto De Oliveira; Maria Cristina Flores Soares; Tatiana Da Silva Pereira (Environmental Geochemistry and Health, 2018)

Lepeophtheirus azoricus n. sp. (Copepoda: Caligidae) parasitic on dusky grouper, Epinephelus marginatus, from Atlantic waters off the Azores, Portugal - Argun Akif Özak; Alfredo M. V. Rodrigues; Nina S. S. Vieira; Rui M. G. Rosa; Alper Yanar; Erkin Koyuncu; Geoffrey A. Boxshall (Marine Biodiversity, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

Treatment with pentylenetetrazole (PTZ) and 4-aminopyridine (4-AP) differently affects survival, locomotor activity, and biochemical markers in Drosophila melanogaster - Deividi C. S. Soares; José L. R. Portela; Daniel H. Roos; Nathane R. Rodrigues; Karen K. Gomes; Giulianna E. Macedo; Thais Posser; Jeferson L. Franco; Waseem Hassan; Robson L. Puntel (Molecular and Cellular Biochemistry, 2018)

Purification of arsenic-contaminated water with K-jarosite filters - Rodrigo C. Hott; Luiz F. O. Maia; Mayra S. Santos; Márcia C. Faria; Luiz C. A. Oliveira; Márcio C. Pereira; Cleide A. Bomfeti; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2018)

Transgenerational Effects of Toxicants: An Extension of the Daphnia 21-day Chronic Assay? - B. B. Castro; A. R. Freches; M. Rodrigues; B. Nunes; S. C. Antunes (Archives of Environmental Contamination and Toxicology, 2018)

Reconquering the water: Evolution and systematics of South and Central American aquatic lizards (Gymnophthalmidae) - Sergio Marques‐Souza; Ivan Prates; Antoine Fouquet; Agustín Camacho; Philippe J. R. Kok; Pedro M. S. Nunes; Francisco Dal Vechio; Renato Sousa Recoder; Nathalia Mejia; Mauro Teixeira Junior; Cesar Barrio‐Amorós; José Cassimiro; et al. (Zoologica Scripta, 2018)
The Cercosaurini tribe stands out from other Gymnophthalmidae lizards for including several species with morphological adaptations to aquatic lifestyle (“Crocodile‐Like Morphology” – CLM ). Recent molecular phylogenies of Cercosaurini demonstrated the paraphyly of CLM species, implicitly suggesting that adaptations to the aquatic life evolved more than once. However, CLM species have remained poorly sampled, and a number of uncertainties persist, such as the monophyly of Neusticurus and the placement of Potamites apodemus within the tribe. Based on a more extensive molecular and morphological data set, we propose a phylogenetic hypothesis for Neusticurus and investigate, for the first time, the phylogenetic position of P . apodemus . We recovered a monophyletic Neusticurus clade; however, Neusticurus rudis as currently understood was recovered as paraphyletic, with two lineages that also show consistent morphological diagnosis; as a result, we resurrect and provide a taxonomic redescription of Neusticurus surinamensis Müller, . Moreover, because P. apodemus was recovered as sister to all other Echinosaura , we propose a new combination for this species ( Echinosaura apodema ). We also review the distribution of Neusticurus species, offering a comprehensive view of their biogeography. Lastly, our ancestral character reconstruction and dating analyses indicate that the CLM phenotype evolved four times independently during Cercosaurini′s evolutionary history. We hypothesize that the CLM phenotype and subsequent adaptation to aquatic life may be linked to the development of the Pebas Lake in western Amazonia during the Miocene.

Lignin and cellulose synthesis and antioxidative defense mechanisms are affected by light quality in Brachypodium distachyon - T. C. Mamedes-Rodrigues; D. S. Batista; T. A. Napoleão; A. C. F. Cruz; E. A. Fortini; F. T. S. Nogueira; E. Romanel; W. C. Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Periphyton nutrient content, biomass and algal community on artificial substrate: response to experimental nutrient enrichment and the effect of its interruption in a tropical reservoir - Suele Aparecida Mendes Santos; Thiago Rodrigues dos Santos; Mariana S. R. Furtado; Raoul Henry; Carla Ferragut (Limnology, 2018)

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

Area-wide spatial survey of the likelihood of insecticide control failure in the neotropical brown stink bug Euschistus heros - Edmar S. Tuelher; Éder H. da Silva; Hígor S. Rodrigues; Edson Hirose; Raul Narciso C. Guedes; Eugênio E. Oliveira (Journal of Pest Science, 2018)

Methionine Administration in Pregnant Rats Causes Memory Deficit in the Offspring and Alters Ultrastructure in Brain Tissue - Bruna Martins Schweinberger; André Felipe Rodrigues; Tiago Marcon dos Santos; Francieli Rohden; Silvia Barbosa; Paula Rigon da Luz Soster; Wania Aparecida Partata; Maria Cristina Faccioni-Heuser; Angela T. S. Wyse (Neurotoxicity Research, 2018)

Evidence for the involvement of opioid system in the antidepressant-like effect of ascorbic acid - Morgana Moretti; Camille M. Ribeiro; Vivian B. Neis; Luis Eduardo B. Bettio; Priscila B. Rosa; Ana Lúcia S. Rodrigues (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Maternal Hypermethioninemia Affects Neurons Number, Neurotrophins Levels, Energy Metabolism, and Na+,K+-ATPase Expression/Content in Brain of Rat Offspring - Bruna M. Schweinberger; André F. Rodrigues; Elias Turcatel; Paula Pierozan; Leticia F. Pettenuzzo; Mateus Grings; Giselli Scaini; Mariana M. Parisi; Guilhian Leipnitz; Emilio L. Streck; Florencia M. Barbé-Tuana; Angela T. S. Wyse (Molecular Neurobiology, 2018)

Feline immudeficiency virus subtypes B and A in cats from São Luis, Maranhão, Brazil - Nathálya dos S. Martins; Ana Paula de S. Rodrigues; Luciana A. da Luz; Luana da L. dos Reis; Renata M. de Oliveira; Rudson A. de Oliveira; Ana Lucia Abreu-Silva; Jenner Karlisson P. dos Reis; Ferdinan A. Melo (Archives of Virology, 2018)

Monitoring of Francisella noatunensis subsp. orientalis in farmed Nile tilapia (Oreochromis niloticus) in Brazil - Marianna Vaz Rodrigues; Claire Juliana Francisco; Gianmarco S. David; Reinaldo José da Silva; Maria Fernanda Falcone-Dias; João Pessoa Araújo Júnior (Aquaculture International, 2018)

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Mining noise affects loud call structures and emission patterns of wild black-fronted titi monkeys - M. H. L. Duarte; M. C. Kaizer; R. J. Young; M. Rodrigues; R. S. Sousa-Lima (Primates, 2018)

Methylphenidate Decreases ATP Levels and Impairs Glutamate Uptake and Na+,K+-ATPase Activity in Juvenile Rat Hippocampus - Felipe Schmitz; Paula Pierozan; André F. Rodrigues; Helena Biasibetti; Mateus Grings; Bruna Zanotto; Daniella M. Coelho; Carmen R. Vargas; Guilhian Leipnitz; Angela T. S. Wyse (Molecular Neurobiology, 2017)

Organosulfur compound protects against memory decline induced by scopolamine through modulation of oxidative stress and Na+/K+ ATPase activity in mice - Fernanda D. da Silva; Mikaela P. Pinz; Renata L. de Oliveira; Karline C. Rodrigues; Francine R. Ianiski; Mariana M. Bassaco; Claudio C. Silveira; Cristiano R. Jesse; Silvane S. Roman; Ethel A. Wilhelm; Cristiane Luchese (Metabolic Brain Disease, 2017)

Role of Dynein Axonemal Heavy Chain 6 Gene Expression as a Possible Biomarker for Huntington’s Disease: a Translational Study - Lorena B. Areal; Lorraine P. Pereira; Fabiola M. Ribeiro; Isabella G. Olmo; Marcelo R. Muniz; Maria do Carmo Rodrigues; Patrik F. Costa; Cristina Martins-Silva; Stephen S. G. Ferguson; Daniela A. M. Guimarães; Rita G. W. Pires (Journal of Molecular Neuroscience, 2017)

Larval aggregation in a Neotropical butterfly: risky behaviors, per capita risk, and larval responses in Ascia monuste orseis - Alessandra F. K. Santana; Daniela Rodrigues; Fernando S. Zucoloto (Behavioral Ecology and Sociobiology, 2017)

Biogeography of mutualistic fungi cultivated by leafcutter ants - Ulrich G. Mueller; Heather D. Ishak; Sofia M. Bruschi; Chad C. Smith; Jacob J. Herman; Scott E. Solomon; Alexander S. Mikheyev; Christian Rabeling; Jarrod J. Scott; Michael Cooper; Andre Rodrigues; Adriana Ortiz; et al. (Molecular Ecology, 2017)
Leafcutter ants propagate co‐evolving fungi for food. The nearly 50 species of leafcutter ants ( Atta , Acromyrmex ) range from Argentina to the United States, with the greatest species diversity in southern South America. We elucidate the biogeography of fungi cultivated by leafcutter ants using DNA sequence and microsatellite‐marker analyses of 474 cultivars collected across the leafcutter range. Fungal cultivars belong to two clades (Clade‐A and Clade‐B). The dominant and widespread Clade‐A cultivars form three genotype clusters, with their relative prevalence corresponding to southern South America, northern South America, Central and North America. Admixture between Clade‐A populations supports genetic exchange within a single species, Leucocoprinus gongylophorus . Some leafcutter species that cut grass as fungicultural substrate are specialized to cultivate Clade‐B fungi, whereas leafcutters preferring dicot plants appear specialized on Clade‐A fungi. Cultivar sharing between sympatric leafcutter species occurs frequently such that cultivars of Atta are not distinct from those of Acromyrmex . Leafcutters specialized on Clade‐B fungi occur only in South America. Diversity of Clade‐A fungi is greatest in South America, but minimal in Central and North America. Maximum cultivar diversity in South America is predicted by the Kusnezov–Fowler hypothesis that leafcutter ants originated in subtropical South America and only dicot‐specialized leafcutter ants migrated out of South America, but the cultivar diversity becomes also compatible with a recently proposed hypothesis of a Central American origin by postulating that leafcutter ants acquired novel cultivars many times from other nonleafcutter fungus‐growing ants during their migrations from Central America across South America. We evaluate these biogeographic hypotheses in the light of estimated dates for the origins of leafcutter ants and their cultivars.

New cytotoxic furan from the marine sediment-derived fungi Aspergillus niger - Paula Karina S. Uchoa; Antonia T. A. Pimenta; Raimundo Braz-Filho; Maria da Conceição F. de Oliveira; Natália N. Saraiva; Barbara S. F. Rodrigues; Ludwig H. Pfenning; Lucas M. Abreu; Diego V. Wilke; Katharine G. D. Florêncio; Mary Anne S. Lima (Natural Product Research, 2017)

Molecular phylogenetic diversity in the widespread lizard Cercosaura ocellata (Reptilia: Gymnophthalmidae) in South America - Marcelo José Sturaro; Teresa C. S. Avila-Pires; Miguel T. Rodrigues (Systematics and Biodiversity, 2017)

Structural equation modeling for the estimation of interconnections between the P cycle and soil properties - Marcus V. S. Sales; Seldon Aleixo; Antonio Carlos Gama-Rodrigues; Emanuela Forestieri Gama-Rodrigues (Nutrient Cycling in Agroecosystems, 2017)

Complete genome sequence of a new bipartite begomovirus infecting Macroptilium lathyroides in Brazil - Laise S. Passos; Janaína S. Rodrigues; Érica Cristina S. Soares; João Paulo Silva; F. Murilo Zerbini; Ademir Sérgio F. Araújo; José Evando A. Beserra (Archives of Virology, 2017)

Spittlebugs (Hemiptera: Cercopidae) and their host plants: a strategy for pasture diversification - R. Alvarenga; Alexander M. Auad; Jair C. Moraes; Sandra E. B. Silva; Brunno S. Rodrigues; Giani B. Silva (Applied Entomology and Zoology, 2017)

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

MPP+-Lesioned Mice: an Experimental Model of Motor, Emotional, Memory/Learning, and Striatal Neurochemical Dysfunctions - Mauricio P. Cunha; Francis L. Pazini; Vicente Lieberknecht; Josiane Budni; Ágatha Oliveira; Júlia M. Rosa; Gianni Mancini; Leidiane Mazzardo; André R. Colla; Marina C. Leite; Adair R. S. Santos; Daniel F. Martins; et al. (Molecular Neurobiology, 2017)

Creatine Prevents Corticosterone-Induced Reduction in Hippocampal Proliferation and Differentiation: Possible Implication for Its Antidepressant Effect - Francis L. Pazini; Mauricio P. Cunha; Dayane Azevedo; Julia M. Rosa; André Colla; Jade de Oliveira; Ana B. Ramos-Hryb; Patricia S. Brocardo; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2017)

Atorvastatin Protects from Aβ1–40-Induced Cell Damage and Depressive-Like Behavior via ProBDNF Cleavage - Fabiana K. Ludka; Maurício P. Cunha; Tharine Dal-Cim; Luisa Bandeira Binder; Leandra C. Constantino; Caio M. Massari; Wagner C. Martins; Ana Lúcia S. Rodrigues; Carla I. Tasca (Molecular Neurobiology, 2017)

Evaluation of Mycotube, a modified version of Lowenstein–Jensen (LJ) medium, for efficient recovery of Mycobacterium tuberculosis (MTB) - R. Nambiar; S. Chatellier; N. Bereksi; A. van Belkum; N. Singh; B. Barua; A. Shetty; C. Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Cholinergic Oculomotor Nucleus Activity Is Induced by REM Sleep Deprivation Negatively Impacting on Cognition - Patrícia Dos Santos; Adriano D. S. Targa; Ana Carolina D. Noseda; Lais S. Rodrigues; Juliane Fagotti; Marcelo M. S. Lima (Molecular Neurobiology, 2017)

Study of macro and microelements in fish from the Cienfuegos Bay. Relationship with its content in sediments - M. Peña-Icart; E. Rodrigues Pereira-Filho; L. Lopes Fialho; J. A. Nóbrega; C. Alonso-Hernández; Y. Bolaños-Alvarez; A. Muñoz-Caravaca; M. S. Pomares-Alfonso (Environmental Monitoring and Assessment, 2017)

Evidence for a correlation between total lead concentrations in soils and the presence of geological faults - Marcos R. Moreira-Silva; Carlos A. Tello Sáenz; João O. Rodrigues Nunes; Manoel Godoy; Marcos F. S. Teixeira (Environmental Chemistry Letters, 2017)

Richness of periphytic algae and its relationship with hydrological attributes - Vanessa M. Algarte; Natália S. Siqueira; Daiane T. Ruwer; Nicolli C. Osório; Liliana Rodrigues (Brazilian Journal of Botany, 2017)

Evaluation of Oxidative Stress Parameters and Energy Metabolism in Cerebral Cortex of Rats Subjected to Sarcosine Administration - Rodrigo Binkowski de Andrade; Tanise Gemelli; Denise Bertin Rojas; Tomas Duk Hwa Kim; Ângela Zanatta; Felipe Schmitz; André Felipe Rodrigues; Angela T. S. Wyse; Moacir Wajner; Carlos Severo Dutra-Filho; Clovis Milton Duval Wannmacher (Molecular Neurobiology, 2017)

Methylphenidate Causes Behavioral Impairments and Neuron and Astrocyte Loss in the Hippocampus of Juvenile Rats - Felipe Schmitz; Paula Pierozan; André F. Rodrigues; Helena Biasibetti; Matheus Grunevald; Letícia F. Pettenuzzo; Giselli Scaini; Emilio L. Streck; Carlos A. Netto; Angela T. S. Wyse (Molecular Neurobiology, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

Inosine, an Endogenous Purine Nucleoside, Suppresses Immune Responses and Protects Mice from Experimental Autoimmune Encephalomyelitis: a Role for A2A Adenosine Receptor - Stella Célio Junqueira; Igor dos Santos Coelho; Vicente Lieberknecht; Mauricio Peña Cunha; João B. Calixto; Ana Lúcia S. Rodrigues; Adair Roberto Soares Santos; Rafael Cypriano Dutra (Molecular Neurobiology, 2017)

Signaling pathways underlying the antidepressant-like effect of inosine in mice - Filipe Marques Gonçalves; Vivian Binder Neis; Débora Kurrle Rieger; Mark William Lopes; Isabella A. Heinrich; Ana Paula Costa; Ana Lúcia S. Rodrigues; Manuella P. Kaster; Rodrigo Bainy Leal (Purinergic Signalling, 2017)

P transformations in cacao agroforests soils in the Atlantic forest region of Bahia, Brazil - S. Aleixo; A. C. Gama-Rodrigues; M. G. Costa; M. V. S. Sales; E. F. Gama-Rodrigues; J. R. B. Marques (Agroforestry Systems, 2017)

Entropy theory for analysing water resources in northeastern region of Brazil - Vicente de P. Rodrigues da Silva; Adelgicio F. Belo Filho; Vijay P. Singh; Rafaela S. Rodrigues Almeida; Bernardo B. da Silva; Inajá F. de Sousa; Romildo Morant de Holanda (Hydrological Sciences Journal, 2017)

Erratum to: Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

The pivotal role of small non-coding RNAs in the regulation of seed development - Andreia S. Rodrigues; Célia M. Miguel (Plant Cell Reports, 2017)

Hypoxanthine Intrastriatal Administration Alters Neuroinflammatory Profile and Redox Status in Striatum of Infant and Young Adult Rats - Helena Biasibetti; Paula Pierozan; André Felipe Rodrigues; Vanusa Manfredini; Angela T. S. Wyse (Molecular Neurobiology, 2017)

Detecting deforestation impacts in Southern Amazonia rainfall using rain gauges - Nathan S. Debortoli; Vincent Dubreuil; Marina Hirota; Saulo Rodrigues Filho; Diego P. Lindoso; Jean Nabucet (International Journal of Climatology, 2017)
During the last decades, several climate‐modelling studies have forecasted a decrease in precipitation in Southern Amazonia, projecting scenarios of a drier Amazon for the future in relation with deforestation (or forest cover). In this area, only a limited number of analyses using forest cover data and rainfall time series have considered the transitional zones between the Amazon Forest and the Cerrado biome. In this work, we evaluated whether forest cover and rainfall patterns are correlated. The analysis encompassed rainfall times series from 207 rain gauges during the 1971–2010 period, and forest cover data acquired from LANDSAT5 satellite images. The results indicate that, at local level (1–15 km), both seasonal and annual precipitation values are not correlated to forest cover, whereas at the regional scale (30–50 km) contrasting to annual values, significant correlation occurs between forest cover and seasonal precipitation. Additionally, the study suggests that the larger the forest areas, the greater the probabilities of those influencing precipitation at regional scale, in opposite direction to the observed local level effects.

Benthic dinoflagellate blooms in tropical intertidal rock pools: elucidation of photoprotection mechanisms - J. S. Patil; R. V. Rodrigues; P. Paul; K. Sathish; M. Rafi; A. C. Anil (Marine Biology, 2017)

Influence of forest structure upon the diversity and composition of edaphic diplopods - Patrícia E. S. Rodrigues; Luiz Ernesto Costa-Schmidt; Ricardo Ott; Everton Nei Lopes Rodrigues (Journal of Insect Conservation, 2017)

Enhanced dietary formulation to mitigate winter thermal stress in gilthead sea bream (Sparus aurata): a 2D-DIGE plasma proteome study - Denise Schrama; Nadège Richard; Tomé S. Silva; Filipe A. Figueiredo; Luís E.C. Conceição; Richard Burchmore; David Eckersall; Pedro M.L. Rodrigues (Fish Physiology and Biochemistry, 2017)

Occurrence of anti-Leptospira spp. antibodies in Rhipidomys spp. from a forest fragment of the Brazilian Cerrado - D. O. Gomes; G. B. Ramos; V. B. A. Alves; A. Z. Ciuffa; L. P. Cuccato; T. F. M. dos Reis; A. M. C. Lima; M. C. Gonçalves; G. V. Tolesano; V. S. Rodrigues; M. P. J. Szabó (Tropical Animal Health and Production, 2017)

Life cycle thinking in Brazil: challenges and advances towards a more comprehensive practice - Danielle Maia de Souza; Tiago Braga; Maria Cléa Brito de Figueirêdo; Marília I. S. Folegatti Matsuura; Fernando Rodrigues Teixeira Dias; Cássia Maria Lie Ugaya (The International Journal of Life Cycle Assessment, 2017)

An index of Brazil’s vulnerability to expected increases in natural flash flooding and landslide disasters in the context of climate change - Nathan S. Debortoli; Pedro Ivo M. Camarinha; José A. Marengo; Regina R. Rodrigues (Natural Hazards, 2017)

Pramipexole, a Dopamine D2/D3 Receptor-Preferring Agonist, Prevents Experimental Autoimmune Encephalomyelitis Development in Mice - Vicente Lieberknecht; Stella C. Junqueira; Mauricio P. Cunha; Thaís A. Barbosa; Luiz F. de Souza; Igor S. Coelho; Adair R. S. Santos; Ana Lúcia S. Rodrigues; Alcir L. Dafré; Rafael C. Dutra (Molecular Neurobiology, 2017)

The importance of Portuguese Continental Shelf Waters to Balearic Shearwaters revealed by aerial census - Hélder Araújo; Jorge Bastos-Santos; Pedro Correia Rodrigues; Marisa Ferreira; Andreia Pereira; Ana Catarina Henriques; Sílvia S. Monteiro; Catarina Eira; José Vingada (Marine Biology, 2017)

3-D distribution of the radioelements in the granitic rocks of northern and central Portugal and geothermal implications - R. Lamas; M. M. Miranda; A. J. S. C. Pereira; L. J. P. F. Neves; N. Ferreira; N. V. Rodrigues (Journal of Iberian Geology, 2017)

Exceptional Symmetry by Genomic Word - Vera Afreixo; João M. O. S. Rodrigues; Carlos A. C. Bastos; Ana H. M. P. Tavares; Raquel M. Silva (Interdisciplinary Sciences: Computational Life Sciences, 2017)

Adaptative processes, control measures, genetic background, and resilience of malaria vectors and environmental changes in the Amazon region - W. P. Tadei; I. B. Rodrigues; M. S. Rafael; R. T. M. Sampaio; H. G. Mesquita; V. C. S. Pinheiro; J. A. C. Zequi; R. A. Roque; J. M. M. dos Santos (Hydrobiologia, 2017)

Bacteria and fungi inactivation by photocatalysis under UVA irradiation: liquid and gas phase - Caio Rodrigues-Silva; Sandra M. Miranda; Filipe V. S. Lopes; Mário Silva; Márcia Dezotti; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar; Eugénia Pinto (Environmental Science and Pollution Research, 2017)

“Why throw away something useful?”: Attitudes and opinions of people treated for bipolar disorder and their relatives on organ and tissue donation - Carolina S. Padoan; Lucas F. Garcia; Aline A. Rodrigues; Lucas M. Patusco; Mariana V. Atz; Flavio Kapczinski; José R. Goldim; Pedro V. S. Magalhães (Cell and Tissue Banking, 2017)

Conversion of Amazon rainforest to agriculture alters community traits of methane‐cycling organisms - Kyle M. Meyer; Ann M. Klein; Jorge L. M. Rodrigues; Klaus Nüsslein; Susannah G. Tringe; Babur S. Mirza; James M. Tiedje; Brendan J. M. Bohannan (Molecular Ecology, 2017)
Land use change is one of the greatest environmental impacts worldwide, especially to tropical forests. The Amazon rainforest has been subject to particularly high rates of land use change, primarily to cattle pasture. A commonly observed response to cattle pasture establishment in the Amazon is the conversion of soil from a methane sink in rainforest, to a methane source in pasture. However, it is not known how the microorganisms that mediate methane flux are altered by land use change. Here, we use the deepest metagenomic sequencing of Amazonian soil to date to investigate differences in methane‐cycling microorganisms and their traits across rainforest and cattle pasture soils. We found that methane‐cycling microorganisms responded to land use change, with the strongest responses exhibited by methane‐consuming, rather than methane‐producing, microorganisms. These responses included a reduction in the relative abundance of methanotrophs and a significant decrease in the abundance of genes encoding particulate methane monooxygenase. We also observed compositional changes to methanotroph and methanogen communities as well as changes to methanotroph life history strategies. Our observations suggest that methane‐cycling microorganisms are vulnerable to land use change, and this vulnerability may underlie the response of methane flux to land use change in Amazon soils.

Selection and Characterization of Bacillus thuringiensis (Berliner) (Eubacteriales: Bacillaceae) Strains for Ecdytolopha aurantiana (Lima) (Lepidoptera: Tortricidae) Control - J Zorzetti; A P S Ricietto; F A P Fazion; A M Meneguim; P M O J Neves; L A Vilas-Boas; R B Rodrigues; G T Vilas-Bôas (Neotropical Entomology, 2017)

Prevalence of hepatitis E virus antibodies in workers occupationally exposed to swine in Portugal - J. Teixeira; J. R. Mesquita; S. S. Pereira; R. M. S. Oliveira; J. Abreu-Silva; A. Rodrigues; M. Myrmel; K. Stene-Johansen; J. Øverbø; G. Gonçalves; M. S. J. Nascimento (Medical Microbiology and Immunology, 2017)

Ecology of termites from the genus Nasutitermes (Termitidae: Nasutitermitinae) and potential for science-based development of sustainable pest management programs - Isabelle Boulogne; Reginaldo Constantino; Nadine Amusant; Michaël Falkowski; Alice M. S. Rodrigues; Emeline Houël (Journal of Pest Science, 2017)

Extraction and electrophoretic analysis of large dsRNAs from desiccated plant tissues infected with plant viruses and biotrophic fungi - S. Khankhum; C. Escalante; E. Rodrigues de Souto and; R. A. Valverde (European Journal of Plant Pathology, 2017)

Drought tolerance in two oil palm hybrids as related to adjustments in carbon metabolism and vegetative growth - Priscilla A. Silva; Vanessa S. Cosme; Kátia C. B. Rodrigues; Kelly S. C. Detmann; Fábio M. Leão; Roberto L. Cunha; Reginaldo A. Festucci Buselli; Fábio M. DaMatta; Hugo A. Pinheiro (Acta Physiologiae Plantarum, 2017)

Multibiomarker responses in aquatic insect Belostoma elegans (Hemiptera) to organic pollution in freshwater system - S. Lavarías; C. Ocon; V. López van Oosterom; A. Laino; D. A. Medesani; A. Fassiano; H. Garda; J. Donadelli; M. Ríos de Molina; A. Rodrigues Capítulo (Environmental Science and Pollution Research, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Performance of Eriopis connexa (Coleoptera: Coccinellidae) resistant to lambda-cyhalothrin after extended recovery from knockdown - D S Santos; A R S Rodrigues; J B Torres; R Lira (Neotropical Entomology, 2016)

Creatine, Similar to Ketamine, Counteracts Depressive-Like Behavior Induced by Corticosterone via PI3K/Akt/mTOR Pathway - Francis L. Pazini; Mauricio P. Cunha; Julia M. Rosa; André R. S. Colla; Vicente Lieberknecht; Ágatha Oliveira; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2016)

Adsorption of arsenic from water and its recovery as a highly active photocatalyst - Rodrigo C. Hott; Thaina G. Andrade; Mayra S. Santos; Anne C. F. Lima; Márcia C. S. Faria; Cleide A. Bomfeti; Fernando Barbosa; Luiz F. O. Maia; Luiz C. A. Oliveira; Márcio C. Pereira; Jairo L. Rodrigues (Environmental Science and Pollution Research, 2016)

Fitness Advantage in Heterozygous Ladybird Beetle Eriopis connexa (Germar) Resistant to Lambda-Cyhalothrin - R Lira; A R S Rodrigues; J B Torres (Neotropical Entomology, 2016)

Photosynthesis impairments precede noticeable changes in leaf water status of mango plants infected by Ceratocystis fimbriata - Wilka M. S. Bispo; Leonardo Araujo; Isaías S. Cacique; Fábio M. DaMatta; Fabrício A Rodrigues (European Journal of Plant Pathology, 2016)

Essential oils to control ichthyophthiriasis in pacu, Piaractus mesopotamicus (Holmberg): special emphasis on treatment with Melaleuca alternifolia - G M R Valladão; S U Gallani; C V Ikefuti; C da Cruz; N Levy‐Pereira; M V N Rodrigues; F Pilarski (Journal of Fish Diseases, 2016)
In vitro effect of the Melaleuca alternifolia , Lavandula angustifolia and Mentha piperita essential oils ( EO s) against Ichthyophthirius multifiliis and in vivo effect of M. alternifolia for treating ichthyophthiriasis in one of the most important South American fish, Piaractus mesopotamicus (Holmberg), were evaluated. The in vitro test consisted of three EO s, each at concentrations of 57 μL L −1 , 114 μL L −1 , 227 μL L −1 and 455 μL L −1 , which were assessed once an hour for 4 h in microtitre plates (96 wells). The in vitro results demonstrated that all tested EO s showed a cytotoxic effect against I. multifiliis compared to control groups ( P 0.05). The in vivo treatment for white spot disease was performed in a bath for 2 h day −1 for 5 days using the M. alternifolia EO (50 μL L −1 ). In this study, 53.33% of the fish severely infected by I. multifiliis survived after the treatment with M. alternifolia (50 μL L −1 ) and the parasitological analysis has shown an efficacy of nearly 100% in the skin and gills, while all the fish in the control group died. Furthermore, the potential positive effect of M. alternifolia EO against two emergent opportunistic bacteria in South America Edwardsiella tarda and Citrobacter freundii was discussed.

Guanosine and its role in neuropathologies - Luis E. B. Bettio; Joana Gil-Mohapel; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2016)

Phylogenetic clustering among aggressive competitors: evidence from odonate assemblages along a riverine gradient - Victor S. Saito; Francisco Valente-Neto; Marciel Elio Rodrigues; Fabio de Oliveira Roque; Tadeu Siqueira (Oecologia, 2016)

Indomethacin treatment reduces microglia activation and increases numbers of neuroblasts in the subventricular zone and ischaemic striatum after focal ischaemia - Rosana S Lopes; Marcelo M Cardoso; Arthur O Sampaio; Mario Santos Barbosa; Celice C Souza; Michelle C da Silva; Elane Magno N Ferreira; Marco Aurelio M Freire; Rafael Rodrigues Lima; Walace Gomes-Leal (Journal of Biosciences, 2016)

Eucalyptus Cell Wall Architecture: Clues for Lignocellulosic Biomass Deconstruction - Marcela Mendes Salazar; Adriana Grandis; Sivakumar Pattathil; Jorge Lepikson Neto; Eduardo Leal Oliveira Camargo; Ana Alves; José Carlos Rodrigues; Fabio Squina; João Paulo Franco Cairo; Marcos S. Buckeridge; Michael G. Hahn; Gonçalo Amarante Guimarães Pereira (BioEnergy Research, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Whole genome and exome sequencing realignment supports the assignment of KCNJ12, KCNJ17, and KCNJ18 paralogous genes in thyrotoxic periodic paralysis locus: functional characterization of two polymorphic Kir2.6 isoforms - Rolf M. Paninka; Diego R. Mazzotti; Marina M. L. Kizys; Angela C. Vidi; Hélio Rodrigues; Silas P. Silva; Ilda S. Kunii; Gilberto K. Furuzawa; Manoel Arcisio-Miranda; Magnus R. Dias-da-Silva (Molecular Genetics and Genomics, 2016)

High efficacy on diclofenac removal by activated carbon produced from potato peel waste - M. Bernardo; S. Rodrigues; N. Lapa; I. Matos; F. Lemos; M. K. S. Batista; A. P. Carvalho; I. Fonseca (International Journal of Environmental Science and Technology, 2016)

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Agmatine, by Improving Neuroplasticity Markers and Inducing Nrf2, Prevents Corticosterone-Induced Depressive-Like Behavior in Mice - Andiara E. Freitas; Javier Egea; Izaskun Buendia; Vanessa Gómez-Rangel; Esther Parada; Elisa Navarro; Ana Isabel Casas; Aneta Wojnicz; José Avendaño Ortiz; Antonio Cuadrado; Ana Ruiz-Nuño; Ana Lúcia S. Rodrigues; et al. (Molecular Neurobiology, 2016)

Involvement of PI3K/Akt Signaling Pathway and Its Downstream Intracellular Targets in the Antidepressant-Like Effect of Creatine - Mauricio P. Cunha; Josiane Budni; Fabiana K. Ludka; Francis L. Pazini; Julia Macedo Rosa; Ágatha Oliveira; Mark W. Lopes; Carla I. Tasca; Rodrigo B. Leal; Ana Lúcia S. Rodrigues (Molecular Neurobiology, 2016)

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

Using the mini-VIDAS® Easy Salmonella protocol to assess contamination in transitional and coastal waters - M. J. Rodrigues; K. Martins; D. Garcia; S. M. F. Ferreira; S. C. Gonçalves; S. Mendes; M. F. L. Lemos (Archives of Microbiology, 2016)

Aspects of fish conservation in the upper Patos Lagoon basin - N. F. Fontoura; J. P. Vieira; F. G. Becker; L. R. Rodrigues; L. R. Malabarba; U. H. Schulz; O. O. Möller; A. M. Garcia; F. S. Vilella (Journal of Fish Biology, 2016)
The Patos Lagoon basin is a large (201 626 km 2 ) and complex drainage system in southern Brazil. The lagoon is 250 km long and 60 km wide, covering an area of 10 360 km 2 . The exchange of water with the Atlantic Ocean occurs through a 0·8 km wide and 15 m deep inlet, fixed by 4 km long jetties, at the southernmost part of the Patos Lagoon. The estuarine area is restricted to its southern portion (10%), although the upper limit of saline waters migrates seasonally and year to year, influenced by the wind regime and river discharge. The known number of recorded limnetic fish species is 200, but this number is expected to increase. A higher endemism is observed in fish species occurring in upper tributaries. The basin suffers from the direct impact of almost 7 million inhabitants, concentrated in small to large cities, most with untreated domestic effluents. There are at least 16 non‐native species recorded in natural habitats of the Patos Lagoon basin, about half of these being from other South American river basins. Concerning the fishery, although sport and commercial fisheries are widespread throughout the Patos Lagoon basin, the lagoon itself and the estuarine area are the main fishing areas. Landing statistics are not available on a regular basis or for the whole basin. The fishery in the northern Patos Lagoon captures 31 different species, nine of which are responsible for most of the commercial catches, but only three species are actually sustaining the artisanal fishery: the viola Loricariichthys anus : 455 kg per 10 000 m 2 gillnet per day, the mullet Mugil liza : 123 kg per 10 000 m 2 gillnet per day and the marine catfish Genidens barbus : 50 kg per 10 000 m 2 gillnet per day. A decline of the fish stocks can be attributed to inadequate fishery surveillance, which leads to overfishing and mortality of juveniles, or to decreasing water quality because of urban and industrial activities and power production. Global climatic changes also represent a major threat to the Patos system by changing the frequency of El Niño‐La Niña‐Southern Oscillation ( ENSO ).

Genetic pool structure of local apple cultivars from Portugal assessed by microsatellites - V. Ferreira; A. M. Ramos-Cabrer; V. Carnide; O. Pinto-Carnide; A. Assunção; A. Marreiros; R. Rodrigues; S. Pereira-Lorenzo; I. Castro (Tree Genetics & Genomes, 2016)

Leaf water potential and sap flow as indicators of water stress in Crimson ‘seedless’ grapevines under different irrigation strategies - S. Shahidian; P. Valverde; R. Coelho; A. Santos; M. Vaz; A. Rato; J. Serrano; S. Rodrigues (Theoretical and Experimental Plant Physiology, 2016)

Complete genome sequence of bean rugose mosaic virus, genus Comovirus - M. H. S. Picoli; A. Garcia; A. A. L. Barboza; Eliezer Rodrigues de Souto; A. M. R. Almeida (Archives of Virology, 2016)

“Watching the Detectives” report of the general assembly of the EU project DETECTIVE Brussels, 24–25 November 2015 - Ruani N. Fernando; Umesh Chaudhari; Sylvia E. Escher; Jan G. Hengstler; Jürgen Hescheler; Paul Jennings; Hector C. Keun; Jos C. S. Kleinjans; Raivo Kolde; Laxmikanth Kollipara; Annette Kopp-Schneider; Alice Limonciel; et al. (Archives of Toxicology, 2016)

Chronic Treatment with a Clinically Relevant Dose of Methylphenidate Increases Glutamate Levels in Cerebrospinal Fluid and Impairs Glutamatergic Homeostasis in Prefrontal Cortex of Juvenile Rats - Felipe Schmitz; Paula Pierozan; André F. Rodrigues; Helena Biasibetti; Daniella M. Coelho; Ben Hur Mussulini; Mery S. L. Pereira; Mariana M. Parisi; Florencia Barbé-Tuana; Diogo L. de Oliveira; Carmen R. Vargas; Angela T. S. Wyse (Molecular Neurobiology, 2016)

Exposure to different glyphosate formulations on the oxidative and histological status of Rhamdia quelen - Camila R. Murussi; Maiara D. Costa; Jossiele W. Leitemperger; Luciana Guerra; Cintia C. R. Rodrigues; Charlene C. Menezes; Eduardo S. Severo; Fábio Flores-Lopes; Joseânia Salbego; Vania L. Loro (Fish Physiology and Biochemistry, 2016)

How sensitive are the Pacific–tropical North Atlantic teleconnections to the position and intensity of El Niño-related warming? - A. S. Taschetto; R. R. Rodrigues; G. A. Meehl; S. McGregor; M. H. England (Climate Dynamics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Leaf gas exchange and multiple enzymatic and non-enzymatic antioxidant strategies related to drought tolerance in two oil palm hybrids - Priscilla A. Silva; Igor V. Oliveira; Kátia C. B. Rodrigues; Vanessa S. Cosme; Abel J. R. Bastos; Kelly S. C. Detmann; Roberto L. Cunha; Reginaldo A. Festucci-Buselli; Fábio M. DaMatta; Hugo A. Pinheiro (Trees, 2016)

Nellore cattle (Bos indicus) and ticks within the Brazilian Pantanal: ecological relationships - Vanessa N. Ramos; Ubiratan Piovezan; Ana Helena A. Franco; Vinicius S. Rodrigues; Santiago Nava; Matias P. J. Szabó (Experimental and Applied Acarology, 2016)

A novel N-acetyl-glucosamine lectin of Lonchocarpus araripensis attenuates acute cellular inflammation in mice - Alana F. Pires; Natália V. F. C. Rodrigues; Pedro Marcos G. Soares; Ronaldo de Albuquerque Ribeiro; Karoline S. Aragão; Márcia M. Marinho; Mayara T. L. da Silva; Benildo S. Cavada; Ana Maria S. Assreuy (Inflammation Research, 2016)

On the estimation of the bed-material transport and budget along a river segment: application to the Middle Loire River, France - B. Camenen; R. C. Grabowski; A. Latapie; A. Paquier; L. Solari; S. Rodrigues (Aquatic Sciences, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Fungi associated with rocks of the A tacama D esert: taxonomy, distribution, diversity, ecology and bioprospection for bioactive compounds - Vívian N. Gonçalves; Charles L. Cantrell; David E. Wedge; Mariana C. Ferreira; Marco Aurélio Soares; Melissa R. Jacob; Fabio S. Oliveira; Douglas Galante; Fabio Rodrigues; Tânia M. A. Alves; Carlos L. Zani; Policarpo A. S. Junior; et al. (Environmental Microbiology, 2016)
Summary This study assessed the diversity of cultivable rock‐associated fungi from A tacama D esert. A total of 81 fungal isolates obtained were identified as 29 Ascomycota taxa by sequencing different regions of DNA. C ladosporium halotolerans , P enicillium chrysogenum and P enicillium cf. citrinum were the most frequent species, which occur at least in four different altitudes. The diversity and similarity indices ranged in the fungal communities across the latitudinal gradient. The F isher‐α index displayed the higher values for the fungal communities obtained from the siltstone and fine matrix of pyroclastic rocks with finer grain size, which are more degraded. A total of 23 fungal extracts displayed activity against the different targets screened. The extract of P . chrysogenum afforded the compounds α‐linolenic acid and ergosterol endoperoxide, which were active against C ryptococcus neoformans and methicillin‐resistance S taphylococcus aureus respectively. Our study represents the first report of a new habitat of fungi associated with rocks of the A tacama D esert and indicated the presence of interesting fungal community, including species related with saprobes, parasite/pathogen and mycotoxigenic taxa. The geological characteristics of the rocks, associated with the presence of rich resident/resilient fungal communities suggests that the rocks may provide a favourable microenvironment fungal colonization, survival and dispersal in extreme conditions.

Changes in Cd and Zn bioavailability upon an experimental resuspension of highly contaminated coastal sediments from a tropical estuary - Christiane N. Monte; Ana P. C. Rodrigues; Renato C. Cordeiro; Aline S. Freire; Ricardo E. Santelli; W. Machado (Sustainable Water Resources Management, 2015)

Adenosine A2B receptor activation stimulates glucose uptake in the mouse forebrain - Cristina Lemos; Bárbara S. Pinheiro; Rui O. Beleza; Joana M. Marques; Ricardo J. Rodrigues; Rodrigo A. Cunha; Daniel Rial; Attila Köfalvi (Purinergic Signalling, 2015)

The biology and ecology of the Antarctic limpet Nacella concinna - Cecilia N. K. Suda; Gannabathula S. Vani; Mariana Feijó de Oliveira; Edson Rodrigues; Edson Rodrigues; Helena P. Lavrado (Polar Biology, 2015)

Effects of Agmatine on Depressive-Like Behavior Induced by Intracerebroventricular Administration of 1-Methyl-4-phenylpyridinium (MPP+) - Morgana Moretti; Vivian Binder Neis; Filipe Carvalho Matheus; Mauricio Peña Cunha; Priscila Batista Rosa; Camille Mertins Ribeiro; Ana Lúcia S. Rodrigues; Rui Daniel Prediger (Neurotoxicity Research, 2015)

The Size But not the Symmetry of the Wings of Eulaema nigrita Lepeletier (Apidae: Euglossini) is Affected by Human-Disturbed Landscapes in the Brazilian Cerrado Savanna - N S Pinto; D P Silva; J G Rodrigues; P De Marco (Neotropical Entomology, 2015)

Description of Dichelacera (Dichelacera) walteri n. sp. (Diptera: Tabanidae) with a Key to Related Species in the Subgenus Dichelacera Macquart - R R Guimarães; I S Gorayeb; R Rodrigues-Guimarães; G S Seppa; R W Carvalho (Neotropical Entomology, 2015)

Erratum to: Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Contribution to the study of deep coastal detritic bottoms: the algal communities of the continental shelf off the Balearic Islands, Western Mediterranean - S. JOHER; E. BALLESTEROS; C. RODRIGUES-PRIETO (Mediterranean Marine Science, 2015)
Three main algal-dominated coastal detritic communities from the continental shelf off Mallorca and Menorca (Balearic Islands, Western Mediterranean) are described herein: maërl beds dominated by Spongites fruticulosus and forests of Laminaria rodriguezii located in the Menorca channel, and Peyssonnelia inamoena beds found along the Southern coast of Menorca. There seems to be a gradient of disturbance from the highly disturbed Peyssonnelia beds to the almost undisturbed L. rodriguezii forests. Whether this gradient is the result of current and past anthropogenic pressure (e.g. trawling intensity) or is driven by natural environmental factors needs further assessment. Finally, the location of the target communities by means of ROV dives combined with the use of a Box-Corer dredge and beam trawl proved to be a good methodology in the study of the composition and structure of these deep water detritic communities.

Rainfall patterns in the Southern Amazon: a chronological perspective (1971–2010) - Nathan S. Debortoli; Vincent Dubreuil; Beatriz Funatsu; Florian Delahaye; Carlos Henke de Oliveira; Saulo Rodrigues-Filho; Carlos Hiroo Saito; Raquel Fetter (Climatic Change, 2015)

Respecification of structural equation models for the P cycle in tropical soils - M. V. S. Sales; A. C. Gama-Rodrigues; N. B. Comerford; W. P. Cropper; E. F. Gama-Rodrigues; P. H. G. Oliveira (Nutrient Cycling in Agroecosystems, 2015)

Sabotaging Behavior and Decision-Making in Larvae of the Queen Butterfly Danaus gilippus - Pedro P. S. Ferreira; Daniela Rodrigues (Journal of Insect Behavior, 2015)

Creatine, similarly to ketamine, affords antidepressant-like effects in the tail suspension test via adenosine A1 and A2A receptor activation - Mauricio P. Cunha; Francis L. Pazini; Julia M. Rosa; Ana B. Ramos-Hryb; Ágatha Oliveira; Manuella P. Kaster; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2015)

Agmatine Induces Nrf2 and Protects Against Corticosterone Effects in Hippocampal Neuronal Cell Line - Andiara E. Freitas; Javier Egea; Izaskun Buendía; Elisa Navarro; Patricia Rada; Antonio Cuadrado; Ana Lúcia S. Rodrigues; Manuela G. López (Molecular Neurobiology, 2015)

Assessing families’ and patients’ attitudes toward brain donation for research purposes in a Brazilian population sample - M. K. Fonseca; E. Rodrigues-Neto; A. S. R. Costa; M. A. B. C. Rockembach; R. S. Padilha; L. L. Fernandez; F. H. Oliveira; L. P. Garcia; A. Hilbig (Cell and Tissue Banking, 2015)

Why do birds migrate? A macroecological perspective - Marius Somveille; Ana S. L. Rodrigues; Andrea Manica (Global Ecology and Biogeography, 2015)
Aim Bird migration poses a challenge to macroecology, because with one in five species moving twice yearly between breeding and non‐breeding grounds, macroecological patterns in birds are dynamic rather than static. But migration is also a natural experiment for testing hypotheses about the ecological mechanisms driving species distributions. Here, we use macroecological patterns of migratory bird diversity to test whether seasonality, winter harshness and the cost of migration drive the global distribution of migratory birds. Location Global. Methods We used data on the distribution of the world's bird species to derive global empirical patterns of: the number of breeding migrants, the number of non‐breeding migrants and the difference in seasonal diversity. We built statistical models with ecologically meaningful predictors related to each of the hypotheses and investigated if they can significantly explain global empirical patterns of migratory bird diversity. We formally tested these models by training on one hemisphere (Western or Eastern) to predict the other hemisphere in turn. Model predictions were assessed in terms of match to the empirical data and their ability to predict the spatial features of patterns. Results We found strong support for the hypotheses that birds move to breeding grounds to exploit a surplus in resources, preferring areas with harsh winters (presumably to avoid competition). In contrast, distribution during the non‐breeding season seems driven by avoidance of harsh winters and connectivity to breeding grounds. Models integrating these hypotheses explain well the observed variance in the empirical patterns and reproduce key spatial features, even when models trained in one hemisphere are used to predict another. Main conclusions The strong predictive power of the models suggests that we have captured the main mechanisms that drive global patterns in bird migration. The fact that the models perform well despite being applied to species with very different ecologies suggests general mechanisms driving migration across taxa.

Limits to robustness and reproducibility in the demarcation of operational taxonomic units - Thomas S. B. Schmidt; João F. Matias Rodrigues; Christian von Mering (Environmental Microbiology, 2015)
Summary The demarcation of operational taxonomic units ( OTUs ) from complex sequence data sets is a key step in contemporary studies of microbial ecology. However, as biologically motivated ‘optimal’ OTU ‐binning algorithms remain elusive, many conceptually distinct approaches continue to be used. Using a global data set of 887 870 bacterial 16 S r RNA gene sequences, we objectively quantified biases introduced by several widely employed sequence clustering algorithms. We found that OTU ‐binning methods often provided surprisingly non‐equivalent partitions of identical data sets, notably when clustering to the same nominal similarity thresholds; and we quantified the resulting impact on ecological data description for a well‐defined human skin microbiome data set. We observed that some methods were very robust to varying clustering thresholds, while others were found to be highly susceptible even to slight threshold variations. Moreover, we comprehensively quantified the impact of the choice of 16 S r RNA gene subregion, as well as of data set scope and context on algorithm performance. Our findings may contribute to an enhanced comparability of results across sequence‐processing pipelines, and we arrive at recommendations towards higher levels of standardization in established workflows.

Sugar Ester Surfactants: Enzymatic Synthesis and Applications in Food Industry - Nair S. Neta; José A. Teixeira; Lígia R. Rodrigues (Critical Reviews in Food Science and Nutrition, 2015)

The effect of conventional mechanical periodontal treatment on red complex microorganisms and clinical parameters in Down syndrome periodontitis patients: a pilot study - M. H. Tanaka; T. O. Rodrigues; L. S. Finoti; S. R. L. Teixeira; M. P. A. Mayer; R. M. Scarel-Caminaga; E. M. A. Giro (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

REM Sleep Deprivation Reverses Neurochemical and Other Depressive-Like Alterations Induced by Olfactory Bulbectomy - Maira J. Maturana; Cláudia Pudell; Adriano D. S. Targa; Laís S. Rodrigues; Ana Carolina D. Noseda; Mariana H. Fortes; Patrícia dos Santos; Cláudio Da Cunha; Sílvio M. Zanata; Anete C. Ferraz; Marcelo M. S. Lima (Molecular Neurobiology, 2015)

Attention and working memory in elderly: the influence of a distracting environment - Pedro F. S. Rodrigues; Josefa N. S. Pandeirada (Cognitive Processing, 2015)

Oysters as hot spots for mimivirus isolation - Kétyllen R. Andrade; Paulo P. V. M. Boratto; Felipe P. Rodrigues; Lorena C. F. Silva; Fábio P. Dornas; Mariana R. Pilotto; Bernard La Scola; Gabriel M. F. Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2015)

Anatomical and ultrastructural adaptations of seagrass leaves: an evaluation of the southern Atlantic groups - Chirle Ferreira; Paulo A. Horta; Gabriela M. Almeida; Carmen S. Zitta; Eliana de M. Oliveira; Marietou B. Y. B. Gueye; Ana C. Rodrigues (Protoplasma, 2015)

Solar photocatalytic gas-phase degradation of n-decane—a comparative study using cellulose acetate monoliths coated with P25 or sol-gel TiO2 films - Sandra M. Miranda; Filipe V. S. Lopes; Caio Rodrigues-Silva; Susana D. S. Martins; Adrián M. T. Silva; Joaquim L. Faria; Rui A. R. Boaventura; Vítor J. P. Vilar (Environmental Science and Pollution Research, 2015)

Phylogeny and recombination analysis of Brazilian yellow passion fruit isolates of Cowpea aphid-borne mosaic virus: origin and relationship with hosts - Leilane K. Rodrigues; Leonardo A. Silva; Renata M. Garcêz; Alexandre L. R. Chaves; Ligia M. L. Duarte; José S. Giampani; Addolorata Colariccio; Ricardo Harakava; Marcelo Eiras (Australasian Plant Pathology, 2015)

Novel isomannide-based peptide mimetics containing a tartaric acid backbone as serine protease inhibitors - Bárbara Abrahim-Vieira; Emmerson C. B. da Costa; Pedro H. R. de A. Azevedo; Aline C. Portela; Luiza R. S. Dias; Sergio Pinheiro; Amilcar Tanuri; Anne M. Capaccia; Gustavo T. Ventura; Ronaldo Mohana-Borges; Carlos R. Rodrigues; Alessandra M. T. de Souza; et al. (Medicinal Chemistry Research, 2014)

Species distribution and in vitro antifungal susceptibility profiles of yeast isolates from invasive infections during a Portuguese multicenter survey - I. Faria-Ramos; J. Neves-Maia; E. Ricardo; J. Santos-Antunes; A. T. Silva; S. Costa-de-Oliveira; E. Cantón; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Fresh and vitrified bovine preantral follicles have different nutritional requirements during in vitro culture - S. V. Castro; A. A. Carvalho; C. M. G. Silva; F. W. Santos; C. C. Campello; J. R. Figueiredo; A. P. R. Rodrigues (Cell and Tissue Banking, 2014)

Nutrient stocks in litterfall and litter in cocoa agroforests in Brazil - A. G. Fontes; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. V. S. Sales; M. G. Costa; R. C. R. Machado (Plant and Soil, 2014)

A Clinico-Mycological Study of Dermatophytoses in Goa, India - Saleel V. Maulingkar; M. J. W. Pinto; S. Rodrigues (Mycopathologia, 2014)

Differential Effects of Fluoride During Osteoblasts Mineralization in C57BL/6J and C3H/HeJ Inbred Strains of Mice - Sandra S. Matsuda; Thelma L. Silva; Marília A. Buzalaf; Antonio C Rodrigues; Rodrigo Cardoso de Oliveira (Biological Trace Element Research, 2014)

Relative mRNA expression and immunolocalization for transforming growth factor-beta (TGF-β) and their effect on in vitro development of caprine preantral follicles - G. Q. Rodrigues; M. J. Bertoldo; I. R. Brito; C. M. G. Silva; A. D. Sales; S. V. Castro; N. Duffard; Y. Locatelli; P. Mermillod; C. H. Lobo; C. C. Campello; A. P. R. Rodrigues; et al. (In Vitro Cellular & Developmental Biology - Animal, 2014)

Exploring N-Acylhydrazone Derivatives Against Clinical Resistant Bacterial Strains - Andressa C. Lannes; Bruno Leal; Juliana S. Novais; Viviane Lione; Georgia C. T. S. Monteiro; André L. Lourenço; Plínio C. Sathler; Alessandro K. Jordão; Carlos R. Rodrigues; Lúcio M. Cabral; Anna Claudia Cunha; Vinicius Campos; et al. (Current Microbiology, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Early postnatal, but not late, exposure to chemical ambient pollutant 1,2-naphthoquinone increases susceptibility to pulmonary allergic inflammation at adulthood - Karen T. Santos; Juliana Florenzano; Leandro Rodrigues; Rodolfo R. Fávaro; Fernanda F. Ventura; Marcela G. Ribeiro; Simone A. Teixeira; Heloisa H. A. Ferreira; Susan D. Brain; Amílcar S. Damazo; Telma M. Zorn; Niels O. Câmara; et al. (Archives of Toxicology, 2014)

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

Acute ethanol intake induces mitogen-activated protein kinase activation, platelet-derived growth factor receptor phosphorylation, and oxidative stress in resistance arteries - Natália A. Gonzaga; Glaucia E. Callera; Alvaro Yogi; André S. Mecawi; José Antunes-Rodrigues; Regina H. Queiroz; Rhian M. Touyz; Carlos R. Tirapelli (Journal of Physiology and Biochemistry, 2014)

Alterations in the extracellular catabolism of nucleotides and platelet aggregation induced by high-fat diet in rats: effects of α-tocopherol - Jessié M. Gutierres; Fabiano B. Carvalho; Maria Rosa C. Schetinger; Marília V. Rodrigues; Juliano M. Vieira; Paula Maldonado; Maria do Carmo S. Araújo; Roberta Schmatz; Naiara Stefanello; Jeandre A. S. Jaques; Marcio Costa; Vera Morsch; et al. (Journal of Physiology and Biochemistry, 2014)

Land use change alters functional gene diversity, composition and abundance in Amazon forest soil microbial communities - Fabiana S. Paula; Jorge L. M. Rodrigues; Jizhong Zhou; Liyou Wu; Rebecca C. Mueller; Babur S. Mirza; Brendan J. M. Bohannan; Klaus Nüsslein; Ye Deng; James M. Tiedje; Vivian H. Pellizari (Molecular Ecology, 2014)
Land use change in the Amazon rainforest alters the taxonomic structure of soil microbial communities, but whether it alters their functional gene composition is unknown. We used the highly parallel microarray technology GeoChip 4.0, which contains 83 992 probes specific for genes linked nutrient cycling and other processes, to evaluate how the diversity, abundance and similarity of the targeted genes responded to forest‐to‐pasture conversion. We also evaluated whether these parameters were reestablished with secondary forest growth. A spatially nested scheme was employed to sample a primary forest, two pastures (6 and 38 years old) and a secondary forest. Both pastures had significantly lower microbial functional genes richness and diversity when compared to the primary forest. Gene composition and turnover were also significantly modified with land use change. Edaphic traits associated with soil acidity, iron availability, soil texture and organic matter concentration were correlated with these gene changes. Although primary and secondary forests showed similar functional gene richness and diversity, there were differences in gene composition and turnover, suggesting that community recovery was not complete in the secondary forest. Gene association analysis revealed that response to ecosystem conversion varied significantly across functional gene groups, with genes linked to carbon and nitrogen cycling mostly altered. This study indicates that diversity and abundance of numerous environmentally important genes respond to forest‐to‐pasture conversion and hence have the potential to affect the related processes at an ecosystem scale.

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Candida glabrata: a review of its features and resistance - C. F. Rodrigues; S. Silva; M. Henriques (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Light and temperature induce variations in the density and ultrastructure of the secretory spaces in the diesel-tree (Copaifera langsdorffii Desf.—Leguminosae) - T. M. Rodrigues; P. F. S. M. Buarque; A. G. Coneglian; D. C. Reis (Trees, 2014)

Lectin of Abelmoschus esculentus (okra) promotes selective antitumor effects in human breast cancer cells - Leonardo G. Monte; Tatiane Santi-Gadelha; Larissa B. Reis; Elizandra Braganhol; Rafael F. Prietsch; Odir A. Dellagostin; Rodrigo Rodrigues e Lacerda; Carlos A. A. Gadelha; Fabricio R. Conceição; Luciano S. Pinto (Biotechnology Letters, 2014)

Increasing the Added-Value of Onions as a Source of Antioxidant Flavonoids: A Critical Review - M. R. Pérez-Gregorio; J. Regueiro; J. Simal-Gándara; A. S. Rodrigues; D. P. F. Almeida (Critical Reviews in Food Science and Nutrition, 2014)

Effect of forced aeration on citric acid production by Aspergillus sp. mutants in SSF - Cristine Rodrigues; Luciana P. S. Vandenberghe; Wilerson Sturm; Dario E. A. Dergint; Michele Rigon Spier; Júlio Cesar de Carvalho; Carlos R. Soccol (World Journal of Microbiology and Biotechnology, 2013)

Interaction of warm acclimation, low salinity, and trophic fluoride on plasmatic constituents of the Antarctic fish Notothenia rossii Richardson, 1844 - E. Rodrigues; M. Feijó-Oliveira; G. S. Vani; C. N. K. Suda; C. S. Carvalho; L. Donatti; H. P. Lavrado; E. Rodrigues (Fish Physiology and Biochemistry, 2013)

Amoebas as mimivirus bunkers: increased resistance to UV light, heat and chemical biocides when viruses are carried by amoeba hosts - Paulo V. M. Boratto; Fábio P. Dornas; Kétyllen R. Andrade; Rodrigo Rodrigues; Felipe Peixoto; Lorena C. F. Silva; Bernard La Scola; Adriana Oliveira Costa; Gabriel Magno Freitas de Almeida; Erna G. Kroon; Jônatas S. Abrahão (Archives of Virology, 2013)

Mauritic acid: a new dammarane triterpene from the roots of Mauritia flexuosa L.f. (Arecaceae) - Hector H.F. Koolen; Elzalina R. Soares; Felipe M.A. da Silva; Aimêe A. de Oliveira; Antonia Q.L. de Souza; Lívia S. de Medeiros; Edson Rodrigues-Filho; Bruno C. Cavalcanti; Cláudia O. Pessoa; Manoel O. Moraes; Marcos J. Salvador; Afonso D.L. de Souza (Natural Product Research, 2013)

N(4)-Tolyl-2-acetylpyridine thiosemicarbazones and their platinum(II,IV) and gold(III) complexes: cytotoxicity against human glioma cells and studies on the mode of action - Karina S. O. Ferraz; Jeferson G. Da Silva; Flávia M. Costa; Bruno M. Mendes; Bernardo L. Rodrigues; Raquel G. dos Santos; Heloisa Beraldo (BioMetals, 2013)

Humpback whales washed ashore in southeastern Brazil from 1981 to 2011: stranding patterns and microbial pathogens survey - Jailson F. Moura; Dália P. Rodrigues; Emily M. Roges; Roberta L. Souza; Paulo H. Ott; Maurício Tavares; Leila S. Lemos; Davi C. Tavares; Salvatore Siciliano (Biologia, 2013)

The antidepressant-like effect of inosine in the FST is associated with both adenosine A1 and A2A receptors - Manuella P. Kaster; Josiane Budni; Marta Gazal; Mauricio P. Cunha; Adair R. S. Santos; Ana Lúcia S. Rodrigues (Purinergic Signalling, 2013)

Late Anxiety-Like Behavior and Neuroinflammation in Mice Subjected to Sublethal Polymicrobial Sepsis - Allan C. Calsavara; David H. Rodrigues; Aline S. Miranda; Priscila A. Costa; Cristiano X. Lima; Márcia C. Vilela; Milene A. Rachid; Antônio L. Teixeira (Neurotoxicity Research, 2013)

Biological impacts of ocean acidification: a postgraduate perspective on research priorities - Samantha L. Garrard; R. C. Hunter; A. Y. Frommel; A. C. Lane; J. C. Phillips; R. Cooper; R. Dineshram; U. Cardini; S. J. McCoy; M. Arnberg; B. G. Rodrigues Alves; S. Annane; et al. (Marine Biology, 2013)

Soil attributes and leaf nitrogen estimating sugar cane quality parameters: Brix, pol and fibre - F. A. Rodrigues; P. S. G. Magalhães; H. C. J. Franco (Precision Agriculture, 2013)

Are all eggs created equal? A case study from the Hawaiian reef-building coral Montipora capitata - Jacqueline L. Padilla-Gamiño; Robert R. Bidigare; Daniel J. Barshis; Ada Alamaru; Laetitia Hédouin; Xavier Hernández-Pech; Frederique Kandel; Sherril Leon Soon; Melissa S. Roth; Lisa J. Rodrigues; Andrea G. Grottoli; Claudia Portocarrero; et al. (Coral Reefs, 2013)

Protective Effects of Ascorbic Acid on Behavior and Oxidative Status of Restraint-Stressed Mice - Morgana Moretti; Josiane Budni; Danubia Bonfanti dos Santos; Alessandra Antunes; Juliana Felipe Daufenbach; Luana Meller Manosso; Marcelo Farina; Ana Lúcia S. Rodrigues (Journal of Molecular Neuroscience, 2013)

Derivation of soil to plant transfer functions for metals and metalloids: impact of contaminant’s availability - S. M. Rodrigues; E. Pereira; A. C. Duarte; P. F. A. M. Römkens (Plant and Soil, 2012)

Changes in Liver Proteome Expression of Senegalese Sole (Solea senegalensis) in Response to Repeated Handling Stress - Odete D. Cordeiro; Tomé S. Silva; Ricardo N. Alves; Benjamin Costas; Tune Wulff; Nadège Richard; Mahaut de Vareilles; Luís E. C. Conceição; Pedro M. Rodrigues (Marine Biotechnology, 2012)

Detection of Legionella pneumophila on clinical samples and susceptibility assessment by flow cytometry - I. Faria-Ramos; S. Costa-de-Oliveira; J. Barbosa; A. Cardoso; J. Santos-Antunes; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Autophagy is decreased in mesenteric fat tissue but not in intestinal mucosae of patients with Crohn’s disease - Raquel F. Leal; Cláudio S. R. Coy; Lício A. Velloso; Sushila Dalal; Mariana Portovedo; Viviane S. Rodrigues; Andressa Coope; Maria L. S. Ayrizono; João J. Fagundes; Marciane Milanski (Cell and Tissue Research, 2012)

Endoplasmic Reticulum Enrollment in Alzheimer’s Disease - Ricardo J. S. Viana; Ana F. Nunes; Cecília M. P. Rodrigues (Molecular Neurobiology, 2012)

Tuberculosis: Finding a New Potential Antimycobacterium Derivative in a Aldehyde–Arylhydrazone–Oxoquinoline Series - Fernanda C. Santos; Helena C. Castro; Maria Cristina S. Lourenço; Paula A. Abreu; Pedro N. Batalha; Anna C. Cunha; Guilherme S. L. Carvalho; Carlos R. Rodrigues; Cid A. Medeiros; Simone D. Souza; Vitor F. Ferreira; Maria C. B. V. Souza (Current Microbiology, 2012)

Carbon, nitrogen, organic phosphorus, microbial biomass and N mineralization in soils under cacao agroforestry systems in Bahia, Brazil - F. C. Zaia; A. C. Gama-Rodrigues; E. F. Gama-Rodrigues; M. K. S. Moço; A. G. Fontes; R. C. R. Machado; V. C. Baligar (Agroforestry Systems, 2012)

Long-Term Power Transmission Failures in Southeastern Brazil and the Geophysical Environment - Magda A. S. Duro; Pierre Kaufmann; Fernando C. P. Bertoni; Emilio C. N. Rodrigues; José Pissolato Filho (Surveys in Geophysics, 2012)

Revising the M235T Polymorphism Position for the AGT Gene and Reporting a Modifying Variant in the Brazilian Population with Potential Cardiac and Neural Impact - R. R. Lemos; S. G. de Lima; J. E. Gomes da Cunha; D. F. Oliveira; M. B. Rodrigues de Souza; C. F. J. Ayres; M. F. P. M. Albuquerque; J. R. M. Oliveira (Journal of Molecular Neuroscience, 2012)

Influence of soil water content and atmospheric conditions on leaf water potential in cv. “Touriga Nacional” deep-rooted vineyards - P. Rodrigues; V. Pedroso; J. P. Gouveia; S. Martins; C. Lopes; I. Alves (Irrigation Science, 2012)

Assessment of Biotic Integrity of the Coastal Freshwater Tidal Zone of a Temperate Estuary of South America through Multiple Indicators - N. Gómez; M. Licursi; D. E. Bauer; E. S. Ambrosio; A. Rodrigues Capítulo (Estuaries and Coasts, 2012)

First record of a whale shark Rhincodon typus in continental Europe - N. V. Rodrigues; J. P. S. Correia; J. T. C. Graça; F. Rodrigues; R. Pinho; M. Hirofumi (Journal of Fish Biology, 2012)
A whale shark Rhincodon typus was found in a set‐net in southern Portugal in October 2011. This was the first record for continental Europe and represents an increase of the species' known range. Upwelling events and increase in sea‐surface temperatures are possible reasons for this occurrence.

Occupational exposure to formaldehyde in an institute of morphology in Brazil: a comparison of area and personal sampling - Soraya de M. Ochs; Lucas de O. Grotz; Luciara S. Factorine; Mauro R. Rodrigues; Annibal D. Pereira Netto (Environmental Science and Pollution Research, 2012)

TUDCA, a Bile Acid, Attenuates Amyloid Precursor Protein Processing and Amyloid-β Deposition in APP/PS1 Mice - Ana F. Nunes; Joana D. Amaral; Adrian C. Lo; Maria B. Fonseca; Ricardo J. S. Viana; Zsuzsanna Callaerts-Vegh; Rudi D’Hooge; Cecília M. P. Rodrigues (Molecular Neurobiology, 2012)

Development of 14 microsatellite markers for a montane meadow frog (Bokermannohyla saxicola, Hylidae) in southeastern Brazil - Paula C. Eterovick; Ryan Franckowiak; Cibele Velloso-Rodrigues; João Bruno G. C. Santos; Rauber S. Garcia; Josiane A. Gomes (Conservation Genetics Resources, 2012)

Overexpression of inducible 70-kDa heat shock protein in mouse improves structural and functional recovery of skeletal muscles from atrophy - Elen H. Miyabara; Tabata L. Nascimento; Débora C. Rodrigues; Anselmo S. Moriscot; Wilmer F. Davila; Younss AitMou; Pieter P. deTombe; Ruben Mestril (Pflügers Archiv - European Journal of Physiology, 2012)

Identification of carotenoids with high antioxidant capacity produced by extremophile microorganisms - Fernanda Mandelli; Viviane S. Miranda; Eliseu Rodrigues; Adriana Z. Mercadante (World Journal of Microbiology and Biotechnology, 2012)

Microbial production of the drugs violacein and deoxyviolacein: analytical development and strain comparison - André L. Rodrigues; Yvonne Göcke; Christoph Bolten; Nelson L. Brock; Jeroen S. Dickschat; Christoph Wittmann (Biotechnology Letters, 2012)

Estimation of Small Reservoir Storage Capacities with Remote Sensing in the Brazilian Savannah Region - Lineu N. Rodrigues; Edson E. Sano; Tammo S. Steenhuis; Denílson P. Passo (Water Resources Management, 2012)

Statistical Optimization of Sugarcane Leaves Hydrolysis into Simple Sugars by Dilute Sulfuric Acid Catalyzed Process - R. O. Moutta; Anuj K. Chandel; R. C. L. B. Rodrigues; M. B. Silva; G. J. M. Rocha; S. S. Silva (Sugar Tech, 2012)

An integrated GIS for sedimentological and geomorphological analysis of a lagoon environment. Barra de Cananéia inlet region, (Southeastern Brazil) - Luis Américo Conti; Carlos Alberto S. Araujo; Fernando S. Paolo; Roberto L. Barcellos; Marcelo Rodrigues; Michel M. Mahiques; Valdenir V. Furtado (Journal of Coastal Conservation, 2012)

The dual crop coefficient approach using a density factor to simulate the evapotranspiration of a peach orchard: SIMDualKc model versus eddy covariance measurements - T. A. Paço; M. I. Ferreira; R. D. Rosa; P. Paredes; G. C. Rodrigues; N. Conceição; C. A. Pacheco; L. S. Pereira (Irrigation Science, 2012)

Effect of pH and Temperature on Enzyme Activity of Chitosanase Produced Under Solid Stated Fermentation by Trichoderma spp. - Luis C. A. da Silva; Talita L. Honorato; Rosane S. Cavalcante; Telma T. Franco; Sueli Rodrigues (Indian Journal of Microbiology, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

The habitat vegetational structure and the success of the blue alcon, Maculinea alcon (Denis & Schiffermüller) - P. O. Soares; A. L. Crespi; M. C. Rodrigues; P. S. Arnaldo (Plant Biosystems, 2012)

Capsicum annuum L. trypsin inhibitor as a template scaffold for new drug development against pathogenic yeast - Suzanna F. F. Ribeiro; Marciele S. Silva; Maura Da Cunha; André O. Carvalho; Germana B. Dias; Guilherme Rabelo; Érica O. Mello; Claudete Santa-Catarina; Rosana Rodrigues; Valdirene M. Gomes (Antonie van Leeuwenhoek, 2012)

Savanna soil fertility limits growth but not survival of tropical forest tree seedlings - Ricardo A. G. Viani; Ricardo R. Rodrigues; Todd E. Dawson; Rafael S. Oliveira (Plant and Soil, 2011)

Seasonal abundance of the Atlantic bobtail squid Sepiola atlantica in Galician waters (NE Atlantic) - Marcelo Rodrigues; Manuel E. Garci; Jesús S. Troncoso; Ángel Guerra (Marine Biology Research, 2011)

Karyotype and AFLP data reveal the phylogenetic position of the Brazilian endemic Hypochaeris catharinensis (Asteraceae) - Maikel Reck; Lucas M. Benício; Eduardo A. Ruas; Luana A. Rodrigues; Paulo M. Ruas; María A. Ortiz; Salvador Talavera; Estrella Urtubey; Tod Stuessy; Hanna Weiss-Schneeweiss; Karin Tremetsberger; Vanessa S. Michelan; et al. (Plant Systematics and Evolution, 2011)

Ultrastructural changes during early infection of Vigna unguiculata and Phaseolus vulgaris leaves by Xanthomonas axonopodis pv. phaseoli and an unexpected association between chloroplast and mitochondrion - André de O. Carvalho; Maura Da Cunha; Rosana Rodrigues; Cláudia P. Sudré; Izabela S. Santos; Kátia V. S. Fernandes; Guilherme R. Rabelo; Valdirene M. Gomes (Acta Physiologiae Plantarum, 2011)

Kanagawa-Negative, tdh- and trh-Positive Vibrio parahaemolyticus Isolated from Fresh Oysters Marketed in Fortaleza, Brazil - Regine H. S. F. Vieira; Renata A. Costa; Francisca G. R. Menezes; Giselle C. Silva; Grace N. D. Theophilo; Dália P. Rodrigues; Rodrigo Maggioni (Current Microbiology, 2011)

A new race of Puccinia psidii defeats rust resistance in eucalypt - Rodrigo N. Graça; Cristina P. Aun; Lúcio M. S. Guimarães; Bruno V. A. Rodrigues; Edival A. V. Zauza; Acelino C. Alfenas (Australasian Plant Pathology, 2011)

Chemical characterization and synergistic antibiotic activity of volatile compounds from the essential oil of Vanillosmopsis arborea - N. K. A. Santos; H. D. M. Coutinho; G. S. B. Viana; Fabíola F. G. Rodrigues; José G. M. Costa (Medicinal Chemistry Research, 2011)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Oxoquinoline Derivatives: Identification and Structure–Activity Relationship (SAR) Analysis of New Anti-HSV-1 Agents - Paula A. Abreu; Viveca A. G. G. da Silva; Fernanda C. Santos; Helena C. Castro; Cecília S. Riscado; Mariana T. de Souza; Camilly P. Ribeiro; Juliana E. Barbosa; Cláudio C. C. dos Santos; Carlos R. Rodrigues; Viviane Lione; Bianca A. M. Correa; et al. (Current Microbiology, 2011)

Base excision repair genes XRCC1 and APEX1 and the risk for prostate cancer - H. Kuasne; I. S. Rodrigues; R. Losi-Guembarovski; M. B. Reis; P. E. Fuganti; E. P. Gregório; F. Libos Junior; H. M. Matsuda; M. A. F. Rodrigues; M. O. Kishima; I. M. S. Cólus (Molecular Biology Reports, 2011)

The sensitivity of gap analysis to conservation targets - Ruppert Vimal; Ana S. L. Rodrigues; Raphaël Mathevet; John D. Thompson (Biodiversity and Conservation, 2011)

Distribution of oxidizable organic C fractions in soils under cacao agroforestry systems in Southern Bahia, Brazil - Patrícia A. B. Barreto; Emanuela F. Gama-Rodrigues; A. C. Gama-Rodrigues; Alexandre G. Fontes; José C. Polidoro; Maria Kellen S. Moço; Regina C. R. Machado; V. C. Baligar (Agroforestry Systems, 2011)

Unraveling new genes associated with seed development and metabolism in Bixa orellana L. by expressed sequence tag (EST) analysis - Virgínia L. F. Soares; Simone M. Rodrigues; Tahise M. de Oliveira; Talisson O. de Queiroz; Lívia S. Lima; Braz T. Hora-Júnior; Karina P. Gramacho; Fabienne Micheli; Júlio C. M. Cascardo; Wagner C. Otoni; Abelmon S. Gesteira; Marcio G. C. Costa (Molecular Biology Reports, 2011)

Identification of Nor-β-Lapachone Derivatives as Potential Antibacterial Compounds against Enterococcus faecalis Clinical Strain - André L. Lourenço; Paula A. Abreu; Bruno Leal; Eufrânio N. da Silva Júnior; Antonio V. Pinto; Maria do Carmo F. R. Pinto; Alessandra M. T. Souza; Juliana S. Novais; Marcela B. Paiva; Lucio M. Cabral; Carlos R. Rodrigues; Vitor F. Ferreira; et al. (Current Microbiology, 2011)

Wheat resistance to leaf blast mediated by silicon - M. S. Xavier Filha; F. A. Rodrigues; G. P. Domiciano; H. V. Oliveira; P. R. Silveira; W. R. Moreira (Australasian Plant Pathology, 2011)

A novel melanoma-targeting peptide screened by phage display exhibits antitumor activity - Alisson L. Matsuo; Aparecida S. Tanaka; Maria A. Juliano; Elaine G. Rodrigues; Luiz R. Travassos (Journal of Molecular Medicine, 2010)

Identification and distribution of mercury species in rat tissues following administration of thimerosal or methylmercury - Jairo L. Rodrigues; Juliana M. Serpeloni; Bruno L. Batista; Samuel S. Souza; Fernando Barbosa (Archives of Toxicology, 2010)

Estimating parameters of a forest ecosystem C model with measurements of stocks and fluxes as joint constraints - Andrew D. Richardson; Mathew Williams; David Y. Hollinger; David J. P. Moore; D. Bryan Dail; Eric A. Davidson; Neal A. Scott; Robert S. Evans; Holly Hughes; John T. Lee; Charles Rodrigues; Kathleen Savage (Oecologia, 2010)

A new method for the detection of Pneumocystis jirovecii using flow cytometry - J. Barbosa; C. Bragada; S. Costa-de-Oliveira; E. Ricardo; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Factorial analysis of the trihalomethane formation in the reaction of colloidal, hydrophobic, and transphilic fractions of DOM with free chlorine - Stefan Platikanov; Roma Tauler; Pedro M. S. M. Rodrigues; Maria Cristina G. Antunes; Dilson Pereira; Joaquim C. G. Esteves da Silva (Environmental Science and Pollution Research, 2010)

Molecular markers for the DNA fingerprinting of Paphiopedilum dayanum and Paphiopedilum lowii, two endangered slipper orchids - K. F. Rodrigues; Z. A. Aziz; S. V. Kumar; M. A. Latip (Conservation Genetics Resources, 2010)

Trade-offs underlying polyphagy in a facultative ant-tended florivorous butterfly: the role of host plant quality and enemy-free space - Daniela Rodrigues; Lucas A. Kaminski; André V. L. Freitas; Paulo S. Oliveira (Oecologia, 2010)

Seroprevalence of orthopoxvirus in an Amazonian rural village, Acre, Brazil - B. E. F. Mota; G. S. Trindade; T. C. Diniz; M. da Silva-Nunes; E. M. Braga; M. Urbano-Ferreira; G. O. L. Rodrigues; C. A. Bonjardim; P. C. P. Ferreira; E. G. Kroon (Archives of Virology, 2010)

Nitrogen aboveground turnover and soil stocks to 8 m depth in primary and selectively logged forest in southern Amazonia - TED R. FELDPAUSCH; EDUARDO G. COUTO; LUIZ CARLOS RODRIGUES; DANIELA PAULETTO; MARK S. JOHNSON; TIMOTHY J. FAHEY; JOHANNES LEHMANN; SUSAN J. RIHA (Global Change Biology, 2010)
Extensive areas of Amazonia undergo selective logging, modifying forest structure and nutrient cycles. Anthropogenic‐accelerated rates of nitrogen (N) turnover could increase N loss and affect regeneration, carbon sequestration and timber production. We quantified leaf area reduction, canopy opening and downed biomass and resultant N flux from reduced impact logging (RIL) activities. We compared canopy reduction, surface soil moisture and nitrate to 8 m depth between logged gaps and intact primary forest to determine if logging activities increase subsoil nitrate. To test long‐term logging effects, we evaluated surface N stocks along a 12‐year postlogging chronosequence. At the harvest rate of 2.6 trees ha −1 , total N additions in logging gaps, including leaves and wood from felled crowns (24.8 kg N ha −1 ) and other killed trees (41.9 kg N ha −1 ), accounted for over 80% of the total N addition to aboveground necromass from all logging activities (81.9 kg N ha −1 ). Despite this N turnover by logging, belowground nitrate storage to 8 m depth did not differ between logging gaps and primary forest at the low harvest rate and disturbance intensity of this study. Soil water depletion also did not differ between gaps and primary forest over 1 year, indicating the impact on belowground inorganic N was low. Compared with primary forest, nitrate concentrations to 8 m depth in logging gaps were only significantly higher at 60–100 cm, suggesting some N redistribution beyond the bulk of the fine roots in logging gaps. Extrapolated to the Amazon Basin scale, we provide a conservative estimate that logging damage and bole export under RIL would turn over 0.14 ± 0.07 to 0.23 ± 0.12 Tg N yr −1 based on 1999–2002 selective logging rates. Greater damage during conventional selective logging would cause higher N turnover throughout the Amazon Basin than our results based on RIL.

Butyltin levels in several Portuguese coastal areas - Pedro N. Carvalho; Pedro Nuno R. Rodrigues; M. Clara P. Basto; M. Teresa S. D. Vasconcelos (Environmental Monitoring and Assessment, 2009)

Isolation and characterization of microsatellites loci for “piramutaba” (Brachyplatystoma vaillantii, Siluriformes: Pimelodidae), one of the commercially most important migratory catfishes in the Amazon Basin - Fabiola C. Rodrigues; Izeni P. Farias; Jacqueline S. Batista; José Alves-Gomes (Conservation Genetics Resources, 2009)

The potential ecological costs and cobenefits of REDD: a critical review and case study from the Amazon region - CLAUDIA M. STICKLER; DANIEL C. NEPSTAD; MICHAEL T. COE; DAVID G. McGRATH; HERMANN O. RODRIGUES; WAYNE S. WALKER; BRITALDO S. SOARES‐FILHO; ERIC A. DAVIDSON (Global Change Biology, 2009)
The United Nations climate treaty may soon include a mechanism for compensating tropical nations that succeed in reducing carbon emissions from deforestation and forest degradation, source of nearly one fifth of global carbon emissions. We review the potential for this mechanism [reducing emissions from deforestation and degradation (REDD)] to provoke ecological damages and promote ecological cobenefits. Nations could potentially participate in REDD by slowing clear‐cutting of mature tropical forest, slowing or decreasing the impact of selective logging, promoting forest regeneration and restoration, and expanding tree plantations. REDD could also foster efforts to reduce the incidence of forest fire. Potential ecological costs include the accelerated loss (through displaced agricultural expansion) of low‐biomass, high‐conservation‐value ecosystems, and substitution of low‐biomass vegetation by monoculture tree plantations. These costs could be avoided through measures that protect low‐biomass native ecosystems. Substantial ecological cobenefits should be conferred under most circumstances, and include the maintenance or restoration of (1) watershed functions, (2) local and regional climate regimes, (3) soils and biogeochemical processes, (4) water quality and aquatic habitat, and (5) terrestrial habitat. Some tools already being developed to monitor, report and verify (MRV) carbon emissions performance can also be used to measure other elements of ecosystem function, making development of MRV systems for ecological cobenefits a concrete possibility. Analysis of possible REDD program interventions in a large‐scale Amazon landscape indicates that even modest flows of forest carbon funding can provide substantial cobenefits for aquatic ecosystems, but that the functional integrity of the landscape's myriad small watersheds would be best protected under a more even spatial distribution of forests. Because of its focus on an ecosystem service with global benefits, REDD could access a large pool of global stakeholders willing to pay to maintain carbon in forests, thereby providing a potential cascade of ecosystem services to local stakeholders who would otherwise be unable to afford them.

Overexpression of the Arabidopsis anaphase promoting complex subunit CDC27a increases growth rate and organ size - Cristian Antonio Rojas; Nubia Barbosa Eloy; Marcelo de Freitas Lima; Roberta Lopes Rodrigues; Luciana Ozório Franco; Kristiina Himanen; Gerrit T. S. Beemster; Adriana Silva Hemerly; Paulo Cavalcanti Gomes Ferreira (Plant Molecular Biology, 2009)

Effect of exposure time on the bioaccumulation of Cd, Mg, Mn and Zn in Cystoseira abies‐marina samples subject to shallow water hydrothermal activity in São Miguel (Azores) - Francisco M. Wallenstein; Daniel F. Torrão; Ana I. Neto; Martin Wilkinson; Armindo S. Rodrigues (Marine Ecology, 2009)
Shallow water hydrothermal vents can be compared to polluted places due to high concentrations of heavy metals, and are thus good models for bioaccumulation studies. The present study intended to estimate the time of exposure required for the accumulation of certain elements to stabilize in specimens of Cystoseira abies‐marina , to be used as a reference in future work. Cystoseira abies‐marina intertidal specimens were transplanted from Mosteiros (a non‐hydrothermal and pristine site) to Ferraria (with hydrothermal activity) and left there. Transplanted samples were collected after 1, 2, 4 and 8 weeks and the concentrations of Cd, Mg, Mn and Zn were measured through flame atomic absorption spectrophotometry. Although further studies with increased periods of exposure are needed because the concentration of these elements never stabilized in the collected samples, there is strong evidence that increased time of exposure led to increased concentrations of Cd, Mg, Mn, but not Zn. These results are consistent with the assumption that C. abies‐marina is bioaccumulating some of the heavy metals and can thus be a good indicator for polluted waters.

Evaluating the resistance to posaconazole by E-test and CLSI broth microdilution methodologies of Candida spp. and pathogenic moulds - R. Araujo; S. Costa-de-Oliveira; I. Coutinho; A. G. Rodrigues; C. Pina-Vaz (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment - M. E. Pereira; A. I. Lillebø; P. Pato; M. Válega; J. P. Coelho; C. B. Lopes; S. Rodrigues; A. Cachada; M. Otero; M. A. Pardal; A. C. Duarte (Environmental Monitoring and Assessment, 2009)

Influence of silicon on some components of resistance to anthracnose in susceptible and resistant sorghum lines - Renata S. Resende; Fabricio Á. Rodrigues; Juliana M. Soares; Carlos R. Casela (European Journal of Plant Pathology, 2009)

Isolation and characterization of microsatellite loci in Phalaenopsis gigantea - K. F. Rodrigues; S. V. Kumar (Conservation Genetics, 2009)

Conservation of dual-targeted proteins in Arabidopsis and rice points to a similar pattern of gene-family evolution - Carolina V. Morgante; Ricardo A. O. Rodrigues; Phellippe A. S. Marbach; Camila M. Borgonovi; Daniel S. Moura; Marcio C. Silva-Filho (Molecular Genetics and Genomics, 2009)

Spectrofluorimetric Determination of Second Critical Micellar Concentration of SDS and SDS/Brij 30 Systems - Ana Paula Romani; Antonio Eduardo da Hora Machado; Noboru Hioka; Divinomar Severino; Mauricio S. Baptista; Lúcia Codognoto; Maira R. Rodrigues; Hueder Paulo Moisés de Oliveira (Journal of Fluorescence, 2009)

Temperature-dependent development rates of Bracon vulgaris, a parasitoid of boll weevil - F. S. Ramalho; P. A. Wanderley; J. B. Malaquias; K. C. V. Rodrigues; J. V. S. Souza; J. C. Zanuncio (Phytoparasitica, 2009)

Isolation and characterization of 24 microsatellite loci in Paphiopedilum rothschildianum, an endangered slipper orchid - K. F. Rodrigues; S. V. Kumar (Conservation Genetics, 2009)

Foliar application of potassium silicate reduces the intensity of soybean rust - F. A. Rodrigues; H. S. S. Duarte; G. P. Domiciano; C. A. Souza; G. H. Korndörfer; L. Zambolim (Australasian Plant Pathology, 2009)

Identification of a Potential Lead Structure for Designing New Antimicrobials to Treat Infections Caused by Staphylococcus epidermidis-Resistant Strains - Luiz C. S. Pinheiro; Paula A. Abreu; Ilidio F. Afonso; Bruno Leal; Luiz C. D. Corrêa; Júlio C. Borges; Isakelly P. Marques; André L. Lourenço; Plinio Sathler; Andre L. dos Santos; Cid A. Medeiros; Lúcio M. Cabral; et al. (Current Microbiology, 2008)

Yeasts and filamentous fungi carried by the gynes of leaf-cutting ants - Fernando C. Pagnocca; André Rodrigues; Nilson S. Nagamoto; Maurício Bacci (Antonie van Leeuwenhoek, 2008)

A saponin tolerant and glycoside producer xylariaceous fungus isolated from fruits of Sapindus saponaria - Luciana S. Amaral; Michael Murgu; Edson Rodrigues-Fo; Antônia Q. L. de Souza; M. Inez de Moura Sarquis (World Journal of Microbiology and Biotechnology, 2008)

Effect of additives on the esterification activity of immobilized Candida antarctica lipase - Dasciana S. Rodrigues; George P. Cavalcante; Giovanilton F. Silva; Andrea L. O. Ferreira; Luciana R. B. Gonçalves (World Journal of Microbiology and Biotechnology, 2008)

Purification of polyhydroxybutyrate produced by Burkholderia cepacia IPT64 through a chemical and enzymatic route - Daniel V. Suzuki; José M. Carter; Maria Filomena A. Rodrigues; Elda S. da Silva; Alfredo E. Maiorano (World Journal of Microbiology and Biotechnology, 2008)

Benefits of membrane electrodes in the electrochemistry of metalloproteins: mediated catalysis of Paracoccus pantotrophus cytochrome c peroxidase by horse cytochrome c: a case study - P. M. Paes de Sousa; S. R. Pauleta; D. Rodrigues; M. L. Simões Gonçalves; G. W. Pettigrew; I. Moura; J. J. G. Moura; M. M. Correia dos Santos (JBIC Journal of Biological Inorganic Chemistry, 2008)

A first Portuguese epidemiological survey of fungaemia in a university hospital - S. Costa-de-Oliveira; C. Pina-Vaz; D. Mendonça; A. Gonçalves Rodrigues (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Preliminary data on microcharacters and chromosome number in Tornabenea species (Apiaceae) from Cape Verde Islands - A. C. Grosso; L. Rodrigues; I. Gomes; E. S. Martins; G. Teixeira (Plant Biosystems, 2008)

Time sequence of the damage to the acceptor and donor sides of photosystem II by UV-B radiation as evaluated by chlorophyll a fluorescence - Jack J. S. van Rensen; Wim J. Vredenberg; Gustavo C. Rodrigues (Photosynthesis Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Spatial heterogeneity recognition in estuarine intertidal benthic macrofaunal communities: influence of sieve mesh-size and sampling depth - Ana Maria Rodrigues; S. Meireles; T. Pereira; V. Quintino (Hydrobiologia, 2007)

Automatic identification of erosion gullies with ASTER imagery in the Brazilian Cerrados - A. Vrieling; S. C. Rodrigues; H. Bartholomeus; G. Sterk (International Journal of Remote Sensing, 2007)

Repeated-Batch Xylitol Bioproduction Using Yeast Cells Entrapped in Polyvinyl Alcohol–Hydrogel - M. A. A. Cunha; R. C. B. Rodrigues; J. C. Santos; A. Converti; S. S. da Silva (Current Microbiology, 2007)

Acute heat exposure increases high-intensity performance during sprint cycle exercise - Ana Cristina R. Lacerda; Fernando Gripp; Luiz Oswaldo C. Rodrigues; Emerson Silami-Garcia; Cândido C. Coimbra; Luciano S. Prado (European Journal of Applied Physiology, 2006)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

Enhanced Xylitol Production by Precultivation of Candida guilliermondii Cells in Sugarcane Bagasse Hemicellulosic Hydrolysate - Rita C.L.B. Rodrigues; Luciane Sene; Gilvane S. Matos; Inês C. Roberto; Adalberto Pessoa; Maria G.A. Felipe (Current Microbiology, 2006)

Effect of Heat and pH Stress in the Growth of Chickpea Mesorhizobia - Carla S. Rodrigues; Marta Laranjo; Solange Oliveira (Current Microbiology, 2006)

Characterization of an ecto-ATPase activity in Fonsecaea pedrosoi - Ítalo Collopy-Junior; Lucimar F. Kneipp; Fernanda C. da Silva; Marcio L. Rodrigues; Celuta S. Alviano; José Roberto Meyer-Fernandes (Archives of Microbiology, 2006)

Contamination Levels and Preliminary Assessment of the Technical Feasibility of Employing Natural Attenuation in 5 Priority Areas of Presidente Bernardes Refinery in Cubatão, São Paulo, Brazil - René P. Schneider; Sandra C. Morano; Maria Alejandra C. Gigena; Silvia K. Missawa; Rafael C. S. Rocha; Lucimara Rodrigues Da Silva; Nelson Ellert; Sérgio Kataoka; Carlos Katsuragi; Carlos Da Silva Rosa; Luiz Calixto De Oliveira Filho (Environmental Monitoring and Assessment, 2006)

In situ probing of Xylella fastidiosa in honeydew of a xylem sap‐feeding insect using 16S rRNA‐targeted fluorescent oligonucleotides - Jorge L. M. Rodrigues; Maria E. Silva‐Stenico; Adriane N. De Souza; João R. S. Lopes; Siu M. Tsai (Environmental Microbiology, 2006)
Summary Xylella fastidiosa is a plant pathogen that threatens a US$ 4.6 billion worldwide wine and citrus industry. Monitoring its presence and distribution in plants and vectors is crucial for designing control strategies, as well as for understanding its ecological role and fate. We developed two fluorescent oligonucleotide probes complementary to different regions of the 16S rRNA gene of X. fastidiosa . The specificity of the newly designed probes S‐S‐X.fas‐0067‐a‐A‐18 and S‐S‐X.fas‐1439‐a‐A‐18 was demonstrated using fluorescence in situ hybridization (FISH) for 12 Xylella isolates, 15 closely related microorganisms and three plant endophytes. These probes were used to detect and quantify X. fastidiosa in plant sap (average value of 2.9 ± 0.3 × 10 6 cells ml −1 ) from three different citrus orchards. In a second experiment, cells were quantified in honeydew (2.2 ± 0.2 × 10 4 cells ml −1 ) collected from the insect vector Bucephalogonia xanthophis during the acquisition access period on an infected plant. The number of pathogen cells retained or digested by the insect is 10 000 times greater than the estimated minimum value to ensure an efficient transmission. Polymerase chain reaction (PCR) amplification using specific primers with plant sap and honeydew samples, followed by sequencing, confirmed the presence of the plant pathogen. This is the first demonstration of FISH being used for environmental samples, such as plant sap and insect honeydew, to estimate the abundance of a plant pathogen during infection.

Osteopontin expression in coculture of differentiating rat fetal skeletal fibroblasts and myoblasts - Renata O. Pereira; Simone N. Carvalho; Ana Carolina Stumbo; Carlos A. B. Rodrigues; Luis Critóvão Porto; Anibal S. Moura; Laís Carvalho (In Vitro Cellular & Developmental Biology - Animal, 2006)

OSTEOPONTIN EXPRESSION IN COCULTURE OF DIFFERENTIATING RAT FETAL SKELETAL FIBROBLASTS AND MYOBLASTS - RENATA O. PEREIRA; SIMONE N. CARVALHO; ANA CAROLINA STUMBO; CARLOS A. B. RODRIGUES; LUIS CRITÓVÃO PORTO; ANIBAL S. MOURA; LAÍS CARVALHO (In Vitro Cellular & Developmental Biology - Animal, 2006)

Decreased Susceptibility to Nitroimidazoles Among Bacteroides Species in Brazil - Jessica Manya B. D. Vieira; Renata F. Boente; Karla Rodrigues Miranda; Kátia E. S. Avelar; Regina M. C. P. Domingues; Maria Candida de S. Ferreira (Current Microbiology, 2006)

Endosperm-preferred Expression of Maize Genes as Revealed by Transcriptome-wide Analysis of Expressed Sequence Tags - Natalia C. Verza; Thaís Rezende e Silva; Germano Cord Neto; Fábio T. S. Nogueira; Paulo H. Fisch; Vincente E. de Rosa; Marcelo M. Rebello; André L. Vettore; Felipe Rodrigues da Silva; Paulo Arruda (Plant Molecular Biology, 2005)

Vasopressin release during endotoxaemic shock in mice lacking inducible nitric oxide synthase - Evelin C. Carnio; Angelita M. Stabile; Marcelo E. Batalhão; João Santana Silva; José Antunes-Rodrigues; Luiz G. S. Branco; Sheldon Magder (Pflügers Archiv - European Journal of Physiology, 2005)

Degradation of Leaf Litter Phenolics by Aquatic and Terrestrial Isopods - Martin Zimmer; Ricardo Oliveira; Elsa Rodrigues; Manuel A. S. Graça (Journal of Chemical Ecology, 2005)

Anther culture and cold treatment of floral buds increased symmetrical and extra nuclei frequencies in soybean pollen grains - Lia R. Rodrigues; Joo Marcelo S. Oliveira; Jorge E. A. Mariath; Leandro B. Irano; Maria Helena Bodanese-Zanettini (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Histology of embryogenic responses in soybean anther culture - Lia R. Rodrigues; Joo Marcelo S. Oliveira; Jorge E.A. Mariath; Maria Helena Bodanese-Zanettini (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Comparison between C57Bl/6 and C57Bl/10 mycobacterial mouse pleurisy with respect to cellular migration and nitric oxide production - Ana Paula M Rodrigues-Bastos; Camila X Nascimento; Eduardo Werneck-Barroso; Renato S B Cordeiro; Maria das Graças M O Henriques; Aparecida Cristina N Moura (Inflammopharmacology, 2004)

Species, Data, and Conservation Planning - THOMAS BROOKS; GUSTAVO A. B. Da FONSECA; ANA S. L. RODRIGUES (Conservation Biology, 2004)

Effect of dietary iron overload on Photobacterium damselae ssp. piscicida pathogenicity in sea bass, Dicentrarchus labrax (L.) - P N S Rodrigues; F A Pereira (Journal of Fish Diseases, 2004)

Spatial and temporal variability in forest–atmosphere CO 2 exchange - D. Y. Hollinger; J. Aber; B. Dail; E. A. Davidson; S. M. Goltz; H. Hughes; M. Y. Leclerc; J. T. Lee; A. D. Richardson; C. Rodrigues; N.A. Scott; D. Achuatavarier; et al. (Global Change Biology, 2004)
Seven years of carbon dioxide flux measurements indicate that a ∼90‐year‐old spruce dominated forest in Maine, USA, has been sequestering 174±46 g C m −2 yr −1 (mean±1 standard deviation, nocturnal friction velocity ( u * ) threshold >0.25 m s −1 ). An analysis of monthly flux anomalies showed that above‐average spring and fall temperatures were significantly correlated with greater monthly C uptake while above‐average summer temperatures were correlated with decreased net C uptake. Summer months with significantly drier or wetter soils than normal were also characterized by lower rates of C uptake. Years with above‐average C storage were thus typically characterized by warmer than average spring and fall temperatures and adequate summer soil moisture. Environmental and forest–atmosphere flux data recorded from a second tower surrounded by similar forest, but sufficiently distant that flux source regions (‘footprints’), did not overlap significantly showed almost identical temperature and solar radiation conditions, but some differences in energy partitioning could be seen. Half‐hourly as well as integrated (annual) C exchange values recorded at the separate towers were very similar, with average annual net C uptake differing between the two towers by

Protected Areas and Species - Thomas M. Brooks; Gustavo A. B. Da Fonseca; Ana S. L. Rodrigues (Conservation Biology, 2004)

Differential expression of sialylglycoconjugates and sialidase activity in distinct morphological stages of Fonsecaea pedrosoi - Jos N. S. S. Couceiro; Rosangela M. A. Soares; Celuta S. Alviano; Andr L. S. Santos; Marcio L. Rodrigues; Daniela S. Alviano; Catia A. Almeida; Luiz R. Travassos (Archives of Microbiology, 2004)

Trenching Behavior by Caterpillars of the Euphorbia Specialist, Pygarctia roseicapitis: A Field Study - E. A. Bernays; M. S. Singer; D. Rodrigues (Journal of Insect Behavior, 2004)

Role of nitric oxide in thermoregulation during septic shock: involvement of vasopressin - Alexandre Giusti-Paiva; Luiz G. S. Branco; Margareth de Castro; José Antunes-Rodrigues; Evelin C. Carnio (Pflügers Archiv - European Journal of Physiology, 2003)

Impairment of inflammatory response in adult rats submitted to maternal undernutrition during early lactation: Role of insulin and glucocorticoid - C. Barja-Fidalgo; E. P. G. Souza; S. V. Silva; A. L. Rodrigues; E. A. Anjos-Valotta; P. Sannomyia; M. S. DeFreitas; A. S. Moura (Inflammation Research, 2003)

Electrophysiological Responses of Female and Male Hypsipyla grandella (Zeller) to Swietenia macrophylla Essential Oils - Marisi G. Soares; Luciane G. Batista-Pereira; João B. Fernandes; Arlene G. Corrêa; M. Fátima G. F. Da Silva; Paulo C. Vieira; Edson Rodrigues Filho; Orlando S. Ohashi (Journal of Chemical Ecology, 2003)

Chromosomal studies in Callicebus donacophilus pallescens, with classic and molecular cytogenetic approaches: Multicolour FISH using human and Saguinus oedipus painting probes - R. M. S. Barros; C. Y. Nagamachi; J. C. Pieczarka; L. R. R. Rodrigues; M. Neusser; E. H. de Oliveira; J. Wienberg; J. A. P. C. Muniz; J. D. Rissino; S. Muller (Chromosome Research, 2003)

Status of a seagrass ecosystem: An ecologically sensitive wetland habitat from India - Tanaji G. Jagtap; Deepali S. Komarpant; Rouchelle S. Rodrigues (Wetlands, 2003)

Reserve Selection in Regions with Poor Biological Data - Kevin J. Gaston; Ana S. L. Rodrigues (Conservation Biology, 2003)
New approaches to the identification of priority areas for conservation are gaining popularity for their efficiency in maximizing species representation. However, their dependence on detailed distributional data severely hinders their application to regions where such information is limited, although these are commonly also the regions where conservation planning and action are most urgently required. We used exemplar data on the distribution of southern African birds to assess how sampling effort affects the performance of reserve networks selected by methods based on complementarity. We derived four scenarios of data availability from the initial data, resulting from different levels of sampling effort: abundance data, presence/absence data, low sampling effort, and absence of data. Reserve selection based on data obtained with low sampling effort can be highly effective in the representation of species, with a good relative performance also in terms of representation of species in peaks of abundance. This is because although the data on low sampling effort represent far fewer records than the original data, the records retained are biased toward the selection of peaks of abundance, even for the restricted‐range species. Although the best results were naturally obtained from the most effort‐intensive data set (with abundance data), these results suggest that methods based on complementarity are potentially valuable tools for reserve selection in regions for which biological data are poor.

Dam-Break Flood Emergency Management System - Armanda S. Rodrigues; Maria A. Santos; A. D. Santos; Fernanda Rocha (Water Resources Management, 2002)

Tissue-specific regulation of BiP genes: a cis-acting regulatory domain is required for BiP promoter activity in plant meristems - Reginaldo A.A. Buzeli; Júlio C.M. Cascardo; Leonardo A.Z. Rodrigues; Maxuel O. Andrade; Raul S. Almeida; Marcelo E. Loureiro; Wagner C. Otoni; Elizabeth P.B. Fontes (Plant Molecular Biology, 2002)

Threatened and endemic species: are they good indicators of patterns of biodiversity on a national scale? - Aletta Bonn; Ana S. L. Rodrigues; Kevin J. Gaston (Ecology Letters, 2002)
Endemic and/or threatened species are often targeted to set conservation priorities. It is tempting to assume that a reserve network focusing on these species will be an effective umbrella for overall species richness of a country. For South Africa and Lesotho we tested whether complementary networks selected for threatened and/or endemic bird species satisfactorily represent all bird species, both in terms of capturing areas where other species are present or areas where they are more abundant (and, presumably, more viable). We found that areas selected for threatened and endemic species perform considerably better than areas selected at random. However, they do not guarantee the representation of overall bird species diversity, particularly not in peak abundance locations. Although nationally threatened and endemic species are important conservation targets, our results indicate that reserve networks focusing solely on these species may not be sufficient to preserve overall species diversity in a country.

Rarity and Conservation Planning across Geopolitical Units - Ana S. L. Rodrigues; Kevin J. Gaston (Conservation Biology, 2002)
Conservation planning is usually done within geopolitical units that tend to encompass only part of the geographic range of most species. Consequently, the relative rarity of a species within the study area considered does not necessarily reflect its relative global rarity or its conservation relevance. We investigated the implications of species' rarity in complementary reserve selection across geopolitical boundaries based on data on the distribution of birds in southern Africa. Our results demonstrate that restricted‐range species have a disproportionate effect on the number and identity of the cells selected by complementarity. The most extreme situation occurs when species whose ranges occupy single cells impose the selection of those particular sites as irreplaceable cells. Not all restricted‐range species are equally important. Some are “apparent rarities” in the study area because they are vagrants, occur very marginally to their range, or have been introduced, and these are mainly irrelevant to conservation planning in a region. Filtering rare nontarget species from the data before reserve selection results in a significant increase in the efficiency of minimum complementary sets. It is particularly recommended for taxa with high mobility, in which vagrancy is more likely. Dividing the study area into geopolitical units has a profound effect on the sites selected by complementarity. It results in loss of overall efficiency, in a tendency for selection of sites at the periphery of the units, and in some species receiving more protection at the edge of their ranges than at the center. Geopolitical coordination in conservation planning may not only result in improved overall efficiency but also a better allocation of resources that improves the long‐term robustness of reserve networks.

Co-selection of the H63D mutation and the HLA-A29 allele: a new paradigm of linkage disequilibrium? - Carla S. Cardoso; Helena Alves; Mónica Mascarenhas; Ricardo Gonçalves; Pedro Oliveira; Pedro Rodrigues; Eugénia Cruz; Maria de Sousa; Graça Porto (Immunogenetics, 2002)

Sialylglycoconjugates and sialyltransferase activity in the fungus Cryptococcus neoformans - Marcio L. Rodrigues; Andrey S. S. Dobroff; José Nelson dos S. S. Couceiro; Celuta S. Alviano; Roland Schauer; Luiz R. Travassos (Glycoconjugate Journal, 2002)

How large do reserve networks need to be? - Ana S. L. Rodrigues; Kevin J. Gaston (Ecology Letters, 2001)
Reserve networks are essential for the long‐term persistence of biodiversity. To fulfil this goal, they need not only to represent all species to be conserved but also to be sufficiently large to ensure species’ persistence over time. An extensive literature exists on the required size of individual reserves, but to date there has been little investigation regarding the appropriate size of entire networks. The IUCN’s proposal that 10% of each nation be reserved is often presented as a desirable target, but concerns have been raised that this is insufficient and is dictated primarily by considerations of feasibility and politics. We found that the minimum percentage of area needed to represent all species within a region increases with the number of targeted species, the size of selection units, and the level of species’ endemism. This has important implications for conservation planning. First, no single universal target is appropriate, as ecosystems or nations with higher diversity and/or higher levels of endemism require substantially larger fractions of their areas to be protected. Second, a minimum conservation network sufficient to capture the diversity of vertebrates is not expected to be effective for biodiversity in general. Third, the 10% target proposed by the IUCN is likely to be wholly insufficient, and much larger fractions of area are estimated to be needed, especially in tropical regions.

Identification of microsatellite loci in olive ( Olea europaea ) and their characterization in Italian and Iberian olive trees - K. M. Sefc; M. S. Lopes; D. Mendonça; M. Rodrigues Dos Santos; M. Laimer Da Câmara Machado; A. Da Câmara Machado (Molecular Ecology, 2000)

Integrating Costs of Conservation into InternationalPriority Setting - Andrew Balmford; Kevin J Gaston; Ana S. L. Rodrigues; Alexander James (Conservation Biology, 2000)

Vasoactive intestinal peptide stimulates apical secretion in hamster seminal vesicle epithelial cells in culture - G. Rodrigues; A. S. Cachaço; S. Gulbenkian; L. Mata (Cell and Tissue Research, 1999)

Identification of two novel mutations in OCTN2 of three patients with systemic carnitine deficiency - F.M. Vaz; H.R. Scholte; J. Ruiter; L.M. Hussaarts-Odijk; R. Rodrigues Pereira; S. Schweitzer; J.B.C. de Klerk; H.R. Waterham; R.J.A. Wanders (Human Genetics, 1999)

Identification of two novel mutations in OCTN2 of three patients with systemic carnitine deficiency - F.M. Vaz; H.R. Scholte; J. Ruiter; L.M. Hussaarts-Odijk; R. Rodrigues Pereira; S. Schweitzer; J.B.C. de Klerk; H.R. Waterham; R.J.A. Wanders (Human Genetics, 1999)

Air pollution and mortality in Madrid, Spain: a time-series analysis - J. C. Alberdi Odriozola; J. Díaz Jiménez; J. C. Montero Rubio; I. J. Mirón Pérez; M. S. Pajares Ortíz; P. Ribera Rodrigues (International Archives of Occupational and Environmental Health, 1998)

Effect of selenium supplementation on some blood biochemical parameters in male rats - A. M. Viegas Crespo; M. J. Lança; S. Vasconcelos; V. Andrade; H. Rodrigues; M. C. Santos (Biological Trace Element Research, 1995)

The effect of age and selenium on some biochemical parameters in rat liver - M. C. Santos; H. Rodrigues; S. Vasconcelos; V. Andrade; M. J. Lança; A. M. Viegas Crespo (Biological Trace Element Research, 1995)

Horizontal biosedimentary gradients across the Sado estuary, W. Portugal - Ana Maria J. Rodrigues; Victor M. S. Quintino (Aquatic Ecology, 1993)

Antifungal properties of I.2.3.4-tetrahydro-9-fluorenone - Fred Quak; A. S. Rodrigues Pereira (Antonie van Leeuwenhoek, 1956)